A review on carbon dioxide sequestration in deep saline aquifers: Experiments, simulations, and field applications - Grant Charles Mwakipunda; Long Yu; Junwei Huang; Jinyu Tang; Riyadh I. Al-Raoush (Fuel, 2027)

Phytochemical profiling of Manglietia chevalieri and its potential in attenuating pulmonary fibrosis: Insights into bioactive constituents - Zi-Jie Long; Mao-Mao Zheng; Yu-Hang He; Bi-Xi Tang; Zhi-Xuan Wang; Xian-Neng Lu; Xi Chen; Jia Li; Yi Zang; Juan Xiong (Phytochemistry, 2027)

In situ CT imaging and discrete element modeling of seedling emergence mechanics - Hao Gong; Zhiwei Zeng; Long Qi; Jiajun Zhong; Shihao Yang; Zhenyu Tang; Yu Jiang (Soil and Tillage Research, 2026)

Application of molasses improves strawberry marketability by enhancing fruit flavor and aroma - Yuanxiu Lin; Yu Long; Zimeng Cui; Siqi Dai; Yunting Zhang; Mengyao Li; Qing Chen; Yong Zhang; Haoru Tang; Yifei Zhou; Ya Luo (Postharvest Biology and Technology, 2026)

Small lakes in the Dongting Lake floodplain: Trace metal contamination, water quality status, and non-carcinogenic health risks - Shilin Tang; Yuannan Long; Xiaofeng Wen; You Zhang (Journal of Geochemical Exploration, 2026)

Computational modeling and experimental data collection for Salmonella Enteritidis PT 30 cross-contamination and dry cleaning interventions in milk powder production environments: A multi-scenario analysis - Jincheng Ma; Yingwen Tang; Shaojin Wang; Byron D. Chaves; Long Chen (Food Microbiology, 2026)

Improving variant interpretation and diagnosis in Koolen-de Vries syndrome through a curated genotype–phenotype repository - Hailin Huang; Jia Geng; Yang Long; Wenyu Xiong; Xiaolu Wang; Chao Wang; Qian Zhang; Ting Tang; Yuxin Chen; Yu Zhao; Jing Cheng; Yu Lu; et al. (Molecular Genetics and Genomics, 2026)

Combined single-cell RNA sequencing and mendelian randomization to identify biomarkers associated with circadian rhythm in sarcopenia - Yuli Huang; Lifeng Tang; Daoyuan Li; Long Chen; Wenjuan Wu; Dingcheng Zeng; Yanbiao Zhong; Maoyuan Wang (Mammalian Genome, 2026)

Overexpression, clinical significance and potential mechanisms of protein kinase D1 in hepatocellular carcinoma: multi-omic analyses and pharmacological insights - Zhen-dong Chen; Hui-ping Lu; Yan-ting Zhan; Fei-yan He; Liang-qin Zhu; Yu-long Deng; Xi-ni Wei; Min-ying Yang; Kai Qin; Yu-xing Tang; Ke-jun Wu; Zhi-guang Huang; et al. (Functional & Integrative Genomics, 2026)

Radio frequency pasteurization of spices under stationary, moving, and mixing conditions: Linking temperature distribution with microbial inactivation, and moisture uniformity - Yingwen Tang; Shangjiayi Bai; Jincheng Ma; Jingfang Ao; Shaojin Wang; Long Chen (Food Control, 2026)

Long-term (>7-year) parental consumption of genetically modified maize (Cry1Ab/Cry2Aj and EPSPS) induces no adverse sperm DNA methylation alterations across two generations of cynomolgus monkeys - Minghao Li; Chenyun Wang; Zheli Li; Weihu Long; Kuanchao Sun; Yunguang Hu; Peixuan Sun; Donghong Tang (Food and Chemical Toxicology, 2026)

Inverse design of metaconcrete surface wave barriers via response surface method and genetic algorithm for broadband vibration isolation - Jiebo Peng; Xiaohui Zeng; Guangcheng Long; Kai Yang; Pengcheng Lv; Huasheng Zhu; Zhuo Tang (Engineering Structures, 2026)

Core–shell microcapsule-enabled electret microdomains in electrospun PVA/SiO2@PMMA membranes for wireless self-powered biomechanical sensing - Yihao Long; Lingling Chen; Kexin Zhang; Wenwu Wang; Fuhao Wu; Qi Shao; Hui Tang; Liang He; Shengyou Yang (Chemical Engineering Journal, 2026)

Highly selective CO2/H2 separation by isomeric CALF-20-based porous slurry - Han Tang; Jin Cai; Zi-Ying Zhao; Long-Long Xie; Ping-Xiang Wang; Yang Meng; Hai-Hang Qin; Peng Xiao; Bei Liu; Yun-Lei Peng; Chang-Yu Sun; Zhi Li; et al. (Chemical Engineering Journal, 2026)

Machine learning-guided discovery of poly(ethylene terephthalate)-binding modules to enhance durable whole-cell degradation - Rui Long; Yaxin Tang; Chengyong Wang; Tangli Yang; Wei Liu; Ling Jiang (Bioresource Technology, 2026)

2(3→20)-abeo-taxoids with adipogenesis inhibitory activity from the leaves and twigs of Taxus chinensis var. mairei - Li-Ping Long; Xin-Yu Fan; Yuan-Hui Yu; Yuan-Liang Xu; Lin-Xi Mao; Xue Tang; Kai Guo; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Centrifugal model tests on negative skin friction of single pile influenced by initial water content - Jun Wang; Xinzhe Tang; Long Wang; Mengjie Ying; Junfeng Ni; Xiaoxiao Zhu; Rila Anda; Ziyang Gao (Ocean Engineering, 2026)

Developing a vertical mixing device to enhance radio frequency heating uniformity of black peppercorns via discrete element method - Shangjiayi Bai; Yingwen Tang; Long Chen (Innovative Food Science & Emerging Technologies, 2026)

The role of intraspecific trait variation in understory responses to simulated nitrogen deposition - Lingbo Ji; Songbo Tang; Jing Long; Siyu Liu; Nan Liu; Shuguang Jian; Bo Tang; Liping Wei; Hai Ren (Forest Ecology and Management, 2026)

Selective and sensitive colorimetric sensing of carbosulfan based on BiO2-x/Bi2O2.75 nanosheets with excellent haloperoxidase-like activity - Yang Yin; Yixin Zeng; Lan Tang; Huzhi Zheng; Yijuan Long (Food Chemistry, 2026)

Unraveling photocatalytic CO2 reduction mechanisms via in situ/operando characterization: From dynamic active sites to reaction pathways - Liye Tang; Wenhui Shi; Hongying Ruan; Xinglin Yu; Wentao Li; Sihan Ma; Guolin Qian; Deng Long (Environmental Research, 2026)

Regulatory mechanisms of N2O emissions from latosolic red soil by different ecotypes of earthworms: Insights from microbial diversity and metagenomic analysis - Chang Wei; Chang-Wen Yun; Xiao-Qing Li; Lang-Hao Lai; Jian-Peng Gao; Meng-Ping Tang; Chun-Na Zhou; Yu-Long Zhang; Hui-Juan Xu (Environmental Pollution, 2026)

Optimized fertilization boosts maize yield and soil multifunctionality in acidic red soils via microbial function modulation - Sheng Zhao; Mei Sun; Geng Sun; Shanpeng Liu; Yuqing Tang; Yu Jiang; Zedong Long; Kai Ouyang (European Journal of Agronomy, 2026)

From area amplification to area retention: Carbon-sheathed bismuth nanoflowers for mechanistically durable vanadium redox flow batteries - Enkang Fu; Xiaoyu Huo; Mingcong Tang; Yuran Bai; Xin Long; Xusong Gong; Xingyi Shi; Liang An (Chemical Engineering Journal, 2026)

Intrinsic alkalinity of the reactive media regulates the differential immobilization of As(V) and Sb(V) in co-contaminated groundwater - Wen Zhang; Kai-hua Bai; Jun Tang; Yi-long Zhao; Jun Jiang (Applied Geochemistry, 2026)

Combined Salinity–Flooding Stress Reveals Wide Phenotypic Variation and Candidate Genomic Loci Associated With Survival in Rice at the Tillering Stage - Nhung Thi Hong Phan; Loc Van Nguyen; Hanh Thi Tang; Ngoc Thi Minh Tran; Hoai Thi Thu Tran; Long Viet Nguyen; Cuong Van Pham (Journal of Crop Health, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

MEHP exposure disrupts the self-renewal and differentiation of GC-1 cells by up-regulating m6A levels, leading to reproductive damage in immature rats - Yanjun Ding; Xiazhu Zhou; Yifan Hong; Jing Chen; Haohui Tang; Binrong Sun; Chunlan Long; Lianju Shen; Shengde Wu; Yuexin Wei; Guanghui Wei (Toxicology, 2026)

An entomopathogen-based small-RNA delivery system promotes the biocontrol efficacy against termites - Chen-Chen Zhao; Hang Lu; Xiao-Long Mao; Long-Long Sun; Fang-Chan He; Zheng-Xun Lv; Qing-Bo Tang; Cheng-Wei Li; Long Liu (Pesticide Biochemistry and Physiology, 2026)

A composite sensitivity and auto-calibration framework for extended ASM2d: Application to SMP/EPS dynamics and HRT optimization in AAMO processes - Xinhui Zhang; Long Tang; Junwu Ma; Jun Nan; Bohan Liu; Zhiqin Li (Journal of Water Process Engineering, 2026)

Microbial sulfur metabolism affects methane oxidation efficiency of anaerobic methane oxidation in different medium environments - Xunsen Chen; Peng Huang; Wenwen Huang; Zhenzhen Peng; Shubing Li; Yi Tang; Mengchen Lu; Teng Guo; Fangrong Wei; Jinshao Ye; Huaming Qin; Yan Long (International Biodeterioration & Biodegradation, 2026)

Engineered microbial consortium for coordinated production and delivery of siRNA and tumor neoantigen to suppress tumor immune evasion - Dawei Sun; Long Li; Xin Huang; Xiaofang Tang; Hui Liu; Hanyan Zhou; Xinran Li; Guijie Bai; Zhijie Feng; Duo Liu; Hanjie Wang (Chemical Engineering Journal, 2026)

A hierarchical biomimetic coating mitigates bending-accelerated corrosion and enhances osteogenesis of biodegradable Zn membranes for guided bone regeneration - He Zhang; Shengzhao Xiao; Yuantao Bu; Luoxin Long; Yuan Zhang; Hongyan Tang; Hongtao Yang; Xiaoming Li; Xuenan Gu; Huawei Liu (Chemical Engineering Journal, 2026)

Integrated pan-cancer analysis reveals a cancer-associated fibroblast oxidative stress response signature predicting immunotherapy response and prognosis - Jun Tang; Cairui Lv; Shuai Dong; Luhao Song; Yiyang Liu; Dong Luo; Yiqian Long; Desheng Xiao; Yongguang Tao; Shuang Liu (Apoptosis, 2026)

Improving short-term rainfall prediction with PSO-FD-LSTM deep learning - Zhuo Chen; Zhiming Tang; Xiping Wei; Long Liu; Yonggui Wang (Hydrological Sciences Journal, 2026)

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Corrigendum to “A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice” [Sci. Bull. 71(11) (2026), 2701-2705] - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Arbuscular mycorrhizal symbiosis decouples arsenic risk from saponin biosynthesis in Panax notoginseng (Araliaceae) by reprogramming rhizosphere and root processes - Xing-Kai Zhang; Xian-Nv Long; Shu-Shuang Tang; Tai-Xiong Zheng; Di Chen; Fu-Gang Wei; Yan-Lin Wang; Yue Wu; Kai Dai; Guan-Hua Cao; Sen He (Journal of Hazardous Materials, 2026)

Influence of pyoverdine on plutonium-239 speciation evolution in contaminated soils - Teqi Ma; Yanan Yin; Jianlong Wang; Haisong Tang; Hui Xu; Guorun Jiang; Long Wen (Journal of Environmental Radioactivity, 2026)

MIL-125-NH2@Co-HHTP based solid phase microextraction for vulcanization accelerators determination in water samples by gas chromatography - Long Pang; Haiyang Feng; Xingru Hu; Shujie Tang; Xuan Wang; Li Guo; Yaxuan Xu; Meiqi Xie (Environmental Research, 2026)

Electron injection-induced MoS2 phase transition from 2H to 1T via alkylamine intercalation for enhanced sodium-ion storage - Xinglong Gao; Chong Hu; Long Zhang; Wenxin Tang; Mingzhi Wei; Lingli Cheng; Zhen Li (Chemical Engineering Journal, 2026)

Permian crustal growth in the Chinese Altai orogen: Constraints from Sr-Nd-Hf-O-Mg multi-isotope systematics - Xin Zhang; Yong Tang; Zhan-Long Ma (Chemical Geology, 2026)

Preparation of low-molecular-weight fucoidan via TEMPO/NaClO/NaBr-mediated oxidative degradation under alkaline conditions - Ziqi Yu; Shiying Tang; Ming Du; Yong Zhao; Xiangrong Li; Ruihan Xu; Qixiang Zhou; Hui Zhou; Dandan Ren; Xiaoting Yu; Long Wu (Algal Research, 2026)

Failure behavior of composite curved sandwich structures with 3D-printed reinforced-truss pyramidal lattice core - Jian Tang; Zhihao Xie; Long Zhang; Yiru Ren; Fei Cheng; Hongyong Jiang (Ocean Engineering, 2026)

Hydrochemical and isotopic tracers reveal mining-induced changes in river water quality and carbon flux in the karst catchment of Daiyang river - Yeye Ren; Xingxing Cao; Pan Wu; Quanzhou Gao; Changmei Yao; Guangxi Long; Weihua Tang; Deshuai Zhang; Haicheng Zhang (Journal of Hydrology, 2026)

Novel non-thermal plasma based strategy to synthesize high-performance multistage mesoporous cobalt-ceria oxides for plasma-catalytic decomposition of environmentally hazardous acetone - Lu Liu; Jian-hua Liu; Zhen-yun Wang; Guang-cai Shao; Yan-gang Hu; Karen Leus; Jian-li Mi; Chuan-long Ma; Rui-tang Guo; Qing-shan Wang; Anton Nikiforov; Pascal Van Der Voort; et al. (Journal of Hazardous Materials, 2026)

Controlling mechanisms and health risk assessment of high fluoride geothermal water in the Pearl River Delta region, South China - Zhengan Wei; Xianrui Li; Chao Yuan; Ke Tang; Lu Liu; Xiting Long; Chengshan Wang (Journal of Hazardous Materials, 2026)

Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Nanoconfinement-assisted interfacial engineering for reliable intelligent κ-carrageenan/Zein films - Huihui Li; Shunchang Wang; Chenglong Zhang; Zhendong Long; Xichao Yin; Hongjin Tang (Innovative Food Science & Emerging Technologies, 2026)

Temperature-dependent regulation of benzeneacetaldehyde formation during black tea drying: Evidence from non-targeted metabolomics and an EGCG-modulated Maillard reaction model - Zisheng Han; Shengxiao Su; Wen Li; Tong Jia; Piaopiao Long; Jia-Ping Ke; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2026)

Multi-omics identifies key genes regulating intramuscular metabolites to affect age- and gender-specific meat quality in sheep - Yali Song; Tianshu Dai; Shijie Tang; Zehu Yuan; Fadi Li; Weiwei Fu; Long Guo; Xueying Zhang; Xiangpeng Yue (Food Bioscience, 2026)

Unveiling optical isomerism as a new dimension for electrolyte design in aqueous zinc-ion batteries - Ruyi Zhou; Yuqing Rang; Yingkang Liu; Yunyu Shi; Xiangyang Zhou; Jingjing Tang; Yaguang Zhang; Zheng-Long Xu; Juan Yang (Chemical Engineering Journal, 2026)

Molecular mapping of a novel non-canonical gibberellin-sensitive dwarfing gene Rht29 in wheat (Triticum aestivum) - Fuqiao Deng; Juanyu Zhang; Yanyan Tang; Furong Huang; Tao Li; Haili Zhang; Jinhui Wang; Junjun Liang; Guangbing Deng; Hai Long (Theoretical and Applied Genetics, 2026)

Exploring primate immune responses to SLA-I/II knockdown pig xenografts in humanized mice and rhesus monkeys - Ming-Hui Fang; Hao Feng; Kai Xu; Tang Hai; Song Chen; Ji-Long Ren; Wei-Gang Wang; Yuan-Tao Wang; Jun Zou; Fei Xu; Zi-Yue Wang; Yi-Wei Yao; et al. (Science China Life Sciences, 2026)

Differential analysis of lipid profiles in natural Calculus Bovis and Bovis Calculus Sativus by UHPLC-MS/MS - Qiang Mao; Huan Zhong; Wan-Li Liang; Jin Dai; Rui-Ting Huang; Yi-Di Wang; Di-Yang Sun; Kai Tang; Long-Fei Xia; Hai-Biao Gong; Yi-Fang Li; Wan-Yang Sun; et al. (Journal of Natural Medicines, 2026)

Experimental Studies on the Shear Behaviours of Rock Materials Containing Double Joints Under Constant Normal Stiffness Boundary Condition - Guansheng Han; Yuqian Wang; Xiaoqin Long; Xuepeng Zhang; Qiongqiong Tang (Geotechnical and Geological Engineering, 2026)

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

A novel UAV-based fusion of spectral and textural features with canopy stratification for accurate estimation of vertical nitrogen distribution in cotton - Guldana Sarsen; Qiu-xiang Tang; Ya-bin Li; Long-long Bao; Yu-hang Xu; Guang-yun Sun; Jian-wen Wu; Yierxiati Abulaiti; Qing-qing Lv; Fubin Liang; Na Zhang; Ren-song Guo; et al. (Computers and Electronics in Agriculture, 2026)

A phospho-switch centered on OsAHL23 orchestrates immune homeostasis in rice - Zhaotang Ma; Qi He; Haicheng Liao; Junjie Yin; Xiaobo Zhu; Xiang Lu; Li Song; Long Wang; Hai Qing; Yu Fang; Kangjian Niu; Langqing Chen; et al. (Science Bulletin, 2026)

Multi-time scale energy management and optimization for hybrid power ships considering lifetime balance and extension of multi-stack fuel cell systems - Xiangguo Yang; Xingwei Zhou; Xin Li; Yufan Wang; Fei Long; Telu Tang; Lin Liu; Yifan Liu (Ocean Engineering, 2026)

Sustainable treatment and valorization of MSWIFA for construction materials: Technologies, mechanisms, and challenges - Zhiyuan Han; Guangcheng Long; Fan Wang; Kunlin Ma; Zhuo Tang; Youjun Xie; Ming Chen; Ding Jiang; Wenxiang Xie; Yan Liu (Journal of Environmental Chemical Engineering, 2026)

Constructing core-shell BaTiO3@ZIF-67 derived composites for boosted piezocatalytic H2O2 production - Qiuchan Zhong; Yuyuan Liu; Guanghuan Li; Kexin Sun; Meien Chen; Yaoyao Tang; Bingyi Yan; Tao Long (Journal of Environmental Chemical Engineering, 2026)

Sustainable solidification/stabilization of chromium (VI)-contaminated soil using enzyme-carbonated reactive magnesia cement: a novel eco-friendly approach - Min Shi; Dian-Long Wang; Jin-Yu Shi; Wen-Bo Chen; Hai-Long Li; Yue-Suo Yang; Chao-Sheng Tang (Journal of Environmental Management, 2026)

Hydrothermal transport characteristics in mining-induced space of geothermal anomaly mines and risk management of thermal environment deterioration - Hongbin Zhao; Shihao Tu; Hongsheng Tu; Kaijun Miao; Long Tang; Benhuan Guo; Ke Lv; Yihang Ma (Geothermics, 2026)

Beyond traditional SERS: Integrating pH control and renewable screen-printed electrode for EC-SERS detection - Rongyu Mao; Xuemei Tang; Ruiming Wen; Sihang Zhang; Heling Ren; Jiawei Liu; Yu Han; Long Wu (Food Chemistry, 2026)

Optimized hot-air drying enhances gastrodin content and antioxidant activity in Gastrodia elata: insights from chemical and microstructural analyses - Jianduo Shen; Long Zhang; Qingxing Dong; Yuqian Jiang; Xuejin Li; Mengru Li; Rameesha Anjum; Wenju Ji; Shiming Li; Xiaoying Zhang; Yao Tang (Food Chemistry, 2026)

Smart autologous plasma-ICG self-assembled carriers prolong half-life of growth factors and enhance antibacterial effect for periodontitis therapy - Hailun Zhou; Jun Zhou; Xiaoqi Wang; Li Tang; Cong Liu; Chunyun Liang; Hejia Qin; Shufang Zhuo; Ao Long; Fengyuan Zhou; Lu Liu; Wenjin Chen; et al. (Chemical Engineering Journal, 2026)

Anion-inverted coordination: An “ice-breaking” ether electrolytes for low temperature sodium battery - Jidao Li; Junli Long; Hao Gong; Shuyu Zhou; Jingshu Wang; Zhenming Jiang; Sisi Huang; Qinlin Zhou; Feng Wang; Jie Shi; Yanyan Zhang; Zhengshuai Bai; et al. (Chemical Engineering Journal, 2026)

Elucidating β-ocimene ozonolysis through combined experiments and theoretical calculations: The Criegee intermediate and peroxy radical pathways - Yu Xia; Xiaofeng Tang; Xiaoxiao Lin; Bo Long; Christa Fittschen; Weijun Zhang (Atmospheric Environment, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

Nighttime Atmospheric Pressure Measurement at 80–110 km Altitude over Xi’an by GBAVTII - Cun-Xia Li; Yang-He Liu; Yan Fang; Ning-Ju Hui; Yan-Long Wang; Yi-Shan Zhang; Di-Di Fu; Yuan-He Tang (Applied Geophysics, 2026)

A New Species of Wongia ( Papulosaceae , Sordariomycetes ) From Nujiang River Basin, Yunnan Province, China - De‐Qing Tang; Hong‐Wei Shen; Feng‐Xiang Ma; Ya‐Min Yang; Zong‐Long Luo (New Zealand Journal of Botany, 2026)
Lignicolous freshwater fungi, which colonize submerged decaying woody substrates in freshwater habitats, play vital roles in nutrient cycling, carbon turnover, and ecosystem functioning. Yunnan Province is one of the fungal diversity research hotspots, with numerous studies focusing on lignicolous freshwater fungi conducted in this region. During an ongoing investigation of diversity of lignicolous freshwater fungi in the Nujiang River basin, China, two Wongia species were collected and examined. Based on morphological characteristics and multigene phylogenetic analyses of combined ITS, LSU, rpb 2, SSU and tef 1‐α sequence data, a new species, Wongia nujiangensis sp. nov. is introduced, and a previously described species, W. bambusae is also identified. Comprehensive morphological descriptions, phylogenetic evidence, and microphotographs are provided to support their taxonomic placement and to enhance understanding of the diversity and distribution of Wongia .

Lipid metabolism, neuroinflammation, and oxidative stress in Alzheimer disease: an integrated mechanistic review - Lijuan Lai; Yanfen Tang; Guojun Song; Yongmei Long; Cuiyu Chen; Chao Chen; Wei Li (Acta Neurologica Belgica, 2026)

A >8-year two-generation study on the long-term effects of genetically modified maize (Zea mays) containing cry1Ab/cry2Aj and EPSPS genes on cardiac function and arrhythmia risk of cynomolgus macaques - Chenyun Wang; Minghao Li; Yulong Guo; Zheli Li; Weihu Long; Kuanchao Sun; Feiling Song; Yunguang Hu; Anguo Yin; Yuping Zhang; Jiye Yin; Qing Xia; et al. (Food and Chemical Toxicology, 2026)

A bipolar membrane-driven proton self-supply strategy for the sustained and efficient electrosynthesis of Na2S2O4 from desulfurization byproduct - Yingxue Fu; Jun Wu; Hao Chen; Lin Wu; Zhujiang Wang; Yelin Zhu; Jiaqi Long; Zhipeng Tang; Fenghua Shen; Kaisong Xiang; Hui Liu (Chemical Engineering Journal, 2026)

Tetrahydroberberine targets the bcl-2 promoter G-quadruplex to trigger mitochondrial apoptosis and inhibit nasopharyngeal carcinoma progression - Yiyin Long; Bingyi Xiao; Yanhong Hou; Liduan Huang; Xiangyue Hu; Xinyi Liu; Yuxun Lin; Tianfen Xu; Guosheng Tang; Yuqing Wang; Yi Cai (Chemico-Biological Interactions, 2026)

A mixed-fluid genetic model for the baiceng fluorite deposit, SW China: Deciphering the magmatic thermal driver and basinal fluid sources - Xi-Wen Zhang; Zhong-guo Jin; Ming-hong Zheng; Jun Chen; Ze-liang Yu; Long Luo; Yong-hu Su; Lin Ye; Yan-wen Tang; Min-shan Gun (Earth Science Informatics, 2026)

Blackwellomyces napialus (Cordycipitaceae, Hypocreales), a Novel Species Parasitic on Napialus hunanensis from China - Jin-Long Jia; Cui-Yuan Wei; Mei Tang; Zhu-Yu Cheng; Ya-Nan Wang; Zhu-Liang Yang; Gang Deng; Yuan-Bing Wang (Current Microbiology, 2026)

Metabarcoding Chironomid Pupal Exuviae Enables Scalable Biomonitoring With High Comparability to Morphotaxonomy - Wu Han; Chu‐Ming Zhang; Cheng Qian; Tsz‐Ying Chan; Thilina S. Nimalrathna; Bai‐an Lin; Xiao‐Long Lin; Hong‐Qu Tang; Peter S. Cranston; Mathew Seymour (Molecular Ecology, 2026)
Conventional morphotaxonomy‐based biomonitoring requires modernization to enable timely assessments in the face of an accelerating freshwater biodiversity crisis. The Chironomid Pupal Exuviae Technique (CPET) is an established biomonitoring approach with considerable potential for integration with molecular methods, as the shed pupal skins of emerging adults provide a source of DNA. We tested the performance of DNA metabarcoding for detecting species richness, recovering beta‐diversity patterns and assessing biodiversity responses to environmental gradients using 15 mock communities and 12 natural chironomid pupal exuviae samples collected from Hong Kong streams. Additionally, the effects of primer choice were assessed by comparing a chironomid‐specific primer set (COI‐S) against a universal, highly degenerate primer set (COI‐V). Our results show that both primer sets achieved high species detection rates in mock communities (86% and 84%, respectively) and consistently recovered predefined community dissimilarities. In natural community samples, however, only COI‐S produced beta‐diversity patterns significantly congruent with that of the morphological dataset (Procrustes r = 0.74, p = 0.003). Both metabarcoding datasets effectively captured seasonal community shifts and demonstrated greater sensitivity to environmental gradients than traditional morphological identification. Notably, the COI‐S dataset explained the highest proportion of community variation (adjusted R 2 = 44.3%), along the environmental gradient, outperforming both the morphotaxonomy (32.5%) and the COI‐V (29.0%) analyses. Here we propose Meta‐CPET, an integrated framework that combines the ecological relevance of CPET with the efficiency, scalability, and resolution of DNA metabarcoding. Our findings show that bulk‐sample metabarcoding enables practical, standardized and large‐scale freshwater biomonitoring while maintaining strong comparability with conventional methods.

A comparative study of radiation resistance and exposure history from Chang'e-6 lunar minerals - Haiyan Long; Hong Tang; Tian Zhang; Bing Mo; Chuanjiao Zhou; Yuanyun Wen; Xiongyao Li; Jianzhong Liu (Acta Geochimica, 2026)

WTAP-Driven m6A Modification of TIMP1 mRNA Promotes Sepsis-Induced Cardiomyocytes Injury - Ying Tang; Zhaoquan Yi; Bo Huang; Jingxin Wu; Biao Tian; Guoliang Long (Biochemical Genetics, 2026)

Slope and grain size control on channel-levee development in mixed turbidite-contourite systems - Long He; Tao Jiang; Man Tang; Dongmei Tian; Licheng Cao; Cong Cheng (Marine Geology, 2026)

Model-based assessment of impacts of aeration intensity on the water-energy-carbon nexus of a full-scale wastewater treatment plant - Xinhong Han; Lu-Man Jiang; Lifeng Lin; Long Wang; Peng Peng; Jiaming Hu; Jiguang Ying; Yi Yang; Rui Tang; Zhen Zhou (Journal of Environmental Management, 2026)

Fe-CN activated peracetic acid system achieving hydroxyl radical-dominated degradation of organic pollutants - Wei Ren; Xiao-Wen Huang; Dongmei Hou; Zhuoyuan Li; Jingenqi Li; Denglong Chen; Yuehong Ma; Chongli Wu; Qian-Qian Tang; Yi Hu; Long-Shuai Zhang; Jian-Ping Zou (Journal of Environmental Chemical Engineering, 2026)

Microbial community responses to per- and polyfluoroalkyl substances (PFAS) across the soil–stream–sediment continuum in the lower Beiluo River, loess plateau, China - Bin Tang; Jinxi Song; Nan Li; Yulu Tian; Yongqing Long; Chenxi Yang; Bingjie Li (Journal of Contaminant Hydrology, 2026)

Electrochemically highly selective removal of lead ions from multicomponent water via synergy from covalent organic framework and hollow mesoporous carbon sphere - Shengyu Wu; Wenle Xing; Kunyue Luo; Yong Long; Jiao Yi; Xinnian Wang; Wangwang Tang (Desalination, 2026)

Experimental Study on Cyclic Shear Behavior of Saw-Tooth Filled Structural Planes - Xu-tang Xu; Zi-Long Dai; Tong-Shu Wu; Ye-qing Cai; Xiang Xu; Wen-bin Jian (Geotechnical and Geological Engineering, 2026)

Description and Comparative Genomic Analysis of Salipiger Bruguierae sp. nov., a Novel Member of the Family Roseobacteraceae Isolated from Mangrove Sediments - Qiangcai He; Shaoshuai Tang; Zhen Gan; Dakun Chen; Huimin Fan; Yishan Lu; Meng Long (Current Microbiology, 2026)

In-situ vacuum-assisted fabrication of highly selective hollow fiber nanofiltration membranes for removing polyfluoroalkyl substances - Chenyue Wu; Shuaiyu Chen; Wenyu Liu; Li Long; Yaowen Hu; Pulak Sarkar; Chuyang Y. Tang (Water Research, 2026)

High-loading single-atom photocatalysts for high-selectivity conversion of CO2 to ethanol - Long-Shuai Zhang; Feiyao Wu; Shenrui Liang; Qianqian Tang; Hui Li; Huang Zhou; Fanqi Meng; Xunheng Jiang; Haiyan Liu; Qing Sun; Meifeng Wu; Yitao Cui; et al. (Science Bulletin, 2026)

Subspecies-specific epigenetic remodeling drives differential cold adaptation in geng/xian rice - Dong-Ao Li; Xiao-Long Xu; Yu-Hong Luo; Zu-Wen Zhou; Yong-Qing Qian; Qian Tang; Xi-Tong Zhu; Jia-Ming Song; Ling-Ling Chen (Plant Science, 2026)

Disentangling the roles of new and young water fractions in stream water quality across catchments - Long Sun; Jianfeng Tang; Lei Yang; Liding Chen (Journal of Hydrology, 2026)

Association of plasma metals with total burden of cerebral small vessel disease: Evidence from China - Lei Zheng; Hao-Long Zeng; Ying Hui; Feipeng Cui; Yudiyang Ma; Jianing Wang; Linxi Tang; Meiqi Xing; Shuohua Chen; Liming Cheng; Shouling Wu; Zhenchang Wang; et al. (Journal of Hazardous Materials, 2026)

Molecular shifts in dissolved organic matter and microbial community assembly during vegetation restoration in karst ecosystems - Yuntian Long; Qian Tang; Wanglan Tao; Jianxing Li; Xiankun Li; Fuzhao Huang; Chuifan Zhou (Journal of Environmental Management, 2026)

Ba isotope unmasks recycling processes of fluid mobile elements in subduction zones - Yang Yu; Xiao-Long Huang; Betchaida D. Payot; Hai-Quan Liu; Ying-De Jiang; Yu Wang; Carla B. Dimalanta; Xin-Feng Ou; Gabriel Theophilus V. Valera; Fan Yang; Graciano P. Yumul; Yi-Gang Xu; et al. (Geochimica et Cosmochimica Acta, 2026)

Visualization study on combustion characteristics of direct-injection methanol ignited by micro-injection diesel in a hydrogen-rich syngas atmosphere - Yuanyou Tang; Wuqiang Long; Zhizhuo Dai; Zechuan Cui; Yang Wang; Ge Xiao; Pengbo Dong; Hua Tian (Fuel, 2026)

Solidification of high water content marine deposits by a novel in-situ treatment of magnesia-based bio-cement: Insight from clay content effect - Dian-Long Wang; Wen-Bo Chen; Hao-Yu Fang; Zhen-Yu Yin; Xiao-Hua Pan; Chao-Sheng Tang (Engineering Geology, 2026)

A net-like colloid with peculiar CO2 sorption behavior formed by aggregation of organic ligand molecules in water - Jin Cai; Wan Chen; Hai Li; Xin Zheng; Han Tang; Ming-Ke Yang; Zi-Xuan Huang; Zi-Ying Zhao; Peng Xiao; Yun-Lei Peng; Xian-Ren Zhang; Long-Long Xie; et al. (Chemical Engineering Journal, 2026)

Metabolic reprogramming-based therapeutic strategy for refractory deep bacterial keratitis with antibiotic resistance - Miaomiao Chi; Wenyue Xie; Long Lin; Guoguo Tang; Yang Zhai; Yinghan Zhao; Yiming Han; Shaofeng Gu; Ying Li; Yaning Zhao; Chengjie Feng; Yi Qu; et al. (Chemical Engineering Journal, 2026)

Characterizing extreme climate events at different time scales and their contributions to agricultural drought and flooding areas - Rong Tang; Ying Xia; Junda Du; Long Qian; Hui Wang; Yangzan Ou (Natural Hazards, 2026)

Seismic data processing key technology for coalbed methane reservoir - Ming Zhang; Bao-yin Zhao; Zhi-fang Ran; Wen-wu Shi; Hao Li; Kai-long Wu; Gen-yang Tang (Applied Geophysics, 2026)

Bioassay-guided isolation and characterisation of anti-proliferative compounds from Coelogyne kouytcheensis (Gagnep.) M.W.Chase & Schuit. using human lung cancer cell lines - Changwei Song; Qinghong Kong; Lingjie Meng; Jianda Long; Xuan Yu; Xingju Chen; Lulu Tang; Guoyong Ruan; Yun Liu (Natural Product Research, 2026)

Colletotrichum nymphaeae causes leaf blight in rose-scented Pelargonium in China - Jiabao Wei; Ran Tang; Jicheng Gu; Qiaoxia Shang; Linfang Long; Yan Chen (Journal of Plant Pathology, 2026)

PRSGNet: A robust framework for crop row detection in complex field scenarios - Dengbin Fu; Yinghu Cai; Zhanpeng Liang; Zhenyu Tang; Zhiqiang Yao; Hao Gong; Renjun Hu; Jiating Li; Long Qi (Computers and Electronics in Agriculture, 2026)

Ecological impacts of offshore wind power construction and operation on zooplankton communities in South China sea - Zhenzhen Peng; Mengchen Lu; Wenwen Huang; Yi Tang; Shubing Li; Huaming Qin; Lili Wang; JinShao Ye; Yan Long (Marine Pollution Bulletin, 2026)

Topological and source–sink integrated analysis of urban thermal environment networks in a megacity: Longitudinal insights from Guangzhou - Liang Tang; Runyu Shao; Xinran Zhou; Yali Zhang; Ziyi Chen; Long Yang; Hui Li (Sustainable Cities and Society, 2026)

Study on the dynamic interaction between buried bent pipes and soil under the influence of oblique incidence of SV waves - Chang-lu Xu; De-long Huang; Hui-yue Wang; Sha-sha Yu; Huan-qing Song; Hang Cen; Zi-yuan Huang; Qiang Liu; Ai-ping Tang (Soil Dynamics and Earthquake Engineering, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A tripartite pollen killer–protector system confers temperature-sensitive inter-subspecific reproductive isolation in rice - Gousi Li; Yaling Zhang; Haixin Yu; Yongyao Xie; Hao Luo; Yuzhu Wang; Jintao Tang; Jia Zhang; Xianrong Xie; Wubei Zong; Kehong Liu; Xinhe Wang; et al. (Molecular Plant, 2026)

Electrostatic enrichment at nanoporous hotspots: A general strategy for charge-selective SERS detection in complex matrices - Xuemei Tang; Wei Zeng; Mengyun Shen; Chunlei Shi; Heling Ren; Jiawei Liu; Long Wu (Journal of Hazardous Materials, 2026)

New insights into mechanisms of valproic acid-induced neurodevelopmental toxicity in autism spectrum disorder: An integrative network toxicology approach combined with in vivo validation - Junzi Long; Xingxing Liao; Jiarou Chen; Kaiyue Han; Zhiqing Tang; Linghui Dong; Xianna Wang; Jianjun Liu; Yan Zhang; Hao Zhang (Food and Chemical Toxicology, 2026)

Hydrological restoration reshapes nitrogen cycling in alpine wetlands: Contrasting denitrification and anammox responses to rewetting - Niu Li; Jianqing Zhou; Chengchai Zhang; Yaoyao Tang; Ming Wu; Xuexin Shao; Peipei Cao; Youzheng Zhang; Long Zhang (Ecological Engineering, 2026)

High-efficiency PVP-PVDF/MXene membranes for dyeing wastewater nanofiltration: A dual strategy of tuning nanochannels and enhancing electrostatic adsorption - Zhongyi Lv; Shixin Zhang; Jie Zhang; Hailin Yang; Liangjun Long; Xiaomin Tang; Huaili Zheng (Chemical Engineering Journal, 2026)

Function and mechanisms of polyethylene glycol-modified sodium acrylate-acrylamide hydrogel for microalgal biomass enrichment and purification - Cong-Cong Tang; Qiao Zhong; Yi Liu; Yong-Qi Cheng; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2026)

miR-19b-3p regulates autophagy of BMSCs in hypoxia through PTEN/Akt/mTOR pathway to promote fracture healing - Shouyu Xiang; Wei Liu; Cheng Tang; Chuhai Xie; Hailan Hu; Jianhui Zhou; Yanming Cao; Long Ling (Journal of Molecular Histology, 2026)

Precise point positioning with an adaptive geometry-free cycle slip detection threshold under complex ionospheric conditions - Long Tang; Luheng Zhou; Fan Xu; Jiahuan Hu; Xiaohong Zhang (GPS Solutions, 2026)
Global navigation satellite system (GNSS) precise point positioning (PPP) performance experiences significant degradation under complex ionospheric conditions, particularly during geomagnetic storm events. To address this challenge, this study develops an adaptive geometry-free (GF) cycle slip detection threshold model, leveraging GNSS Doppler measurements to reduce the incorrect cycle slip detection, thereby enhancing the accuracy and reliability of GNSS PPP. The proposed threshold model is fitted using Doppler index data extracted from 110 International GNSS Service (IGS) stations on the 11th May 2024 when an extreme geomagnetic storm occurred. 72 IGS stations which are not used in modeling on the same day are employed to validate its performance. The results show that PPP with adaptive GF cycle slip detection threshold can achieve positioning accuracy improvements by 42.4% and 37.2% in horizontal and vertical directions, respectively, compared with traditional strategy. Furthermore, positioning accuracy improvements of 63.1% and 50.1% in horizontal and vertical are obtained with data from another geomagnetic storm event on the 11th October 2024, which further demonstrates the efficiency and uniformity of proposed model. Comparison of positioning accuracy with tight and loose thresholds during the ionospheric quiescence periods also verifies the adaptability of the built model.

Probing selective pollutant removal in nanofiltration processes: Critical insights from separation factor and removal difference - Senlin Shao; Chu Zhou; Juntao Xing; Li Long; Yuhua Zhu; Zhe Yang; Yongwang Liu; Chuyang Y. Tang (Water Research, 2026)

Investigation of brake wear particle emissions via single particle mass spectral signatures: Comparison of laboratory and ambient measurements - Seongho Jeong; Chi-Long Tang; Carsten Neukirchen; Gary Sean Cooney; Julian Schade; Patrick Martens; Michael Mäder; Heinrich Ruser; Thomas Adam (Science of The Total Environment, 2026)

Recombinant defense protease inhibitors from Vigna unguiculata show bioactivity against non-host related pests - Jia Liu; XinYue Tang; KeQian Long; ShiQi Zhou; LiLong Pan; WenJia Yang; GuangMao Shen (Pesticide Biochemistry and Physiology, 2026)

Pathogen-induced H2O2 triggers phosphorylation of the RNA-binding protein RRM2R to suppress OsMAPKKK18 intron retention for orchestrating rice immunity and growth - Xiang Lu; Yibang An; Wenxiu Lu; Jing Li; Qing Xiong; Miaomiao Zhu; Yao He; Jia Yang; Yue Wang; Zeming Zhang; Xiaorong Gong; Yulong Qian; et al. (Molecular Plant, 2026)

Evaluation of deconvolution methods and loading parameters in nanoindentation characterization of sodium aluminosilicate hydrate gel in fly ash based geopolymers - Wenrui Xu; Youjun Xie; Fan Wang; Zhiyu Luo; Gang Ma; Yiran Li; Yingjie Li; Guangcheng Long; Zhuo Tang (Journal of Cleaner Production, 2026)

Degassing from Chang’e-6 ilmenite surfaces revealed by a foamy texture: insights for volatile cycles on the Moon - Tian Zhang; Hong Tang; Xiongyao Li; Bing Mo; Yuanyun Wen; Sheng Zhang; Wen Yu; Chuanjiao Zhou; Haiyan Long; Jianzhong Liu (Geochimica et Cosmochimica Acta, 2026)

Co-exposure effects of arsenite and bisphenol A on zebrafish: A focus on gut microbiota’s role in arsenobetaine biosynthesis-related toxicity - Le Zhang; Weitian Liu; Yingying Tang; Peng Zhang; Huosheng Li; Jianyou Long; Wei Zhang (Aquatic Toxicology, 2026)

Genetic and transcriptomic identification of WPG1 controlling nitrogen allocation-related leaf chlorisis and premature senescence in wheat - Haili Zhang; Li’ao Zhang; Qiang Li; Ling Yi; Juanyu Zhang; Yanyan Tang; Jinhui Wang; Junjun Liang; Tao Li; Fangyan Zhang; Yiran Cheng; Yi Wang; et al. (Theoretical and Applied Genetics, 2026)

Real-time Monitoring Unveils Three Distinct Neuronal Response Patterns to SAW Ultrasound via L-type Calcium Channels - Yiming Chen; Wenxu Tang; Yifan Wang; Ya Gao; Jiaqi Hu; Yixuan Lu; Long Meng; Hairong Zheng; Yi Feng; Liming Cheng; Wenyong Fan; Qian Cheng; et al. (Neuroscience Bulletin, 2026)

Digoxin targets BHLHE40 to inhibit epithelial-mesenchymal transition in cervical cancer cells via downregulation of ANGPTL3 - Canyi Li; Penghua Luo; Lin Tang; Yongqiang Yang; Long Rao; Lijun Zhong (Journal of Natural Medicines, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Algal-bacterial consortia-derived cyanophycin reprograms rice seed metabolism for enhanced abiotic stress resilience - Zirui Zhou; Duoduo Chen; Naif Abdullah Al-Dhabi; Caicheng Long; Taiping Qing; Bo Feng; Wangwang Tang; Peng Zhang (Algal Research, 2026)

Pseudoxanthomonas fibrivorans sp. nov. 10HT, a cellulose-degrading bacterium isolated from soil - Xu Yulei; Luo Liying; Qing Yu; Tang Miao; Long Xiufeng (Antonie van Leeuwenhoek, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

First report of Thraustochytrium caudivorum isolated from the undulated surf clam (Paratapes undulatus): Morphological, molecular, and ecological insights under climate change - Yu Chen; Seung-Hyeon Kim; Jinxia Long; S.D.N.K. Bathige; Hyoun Joong Kim; Sen-Lin Tang; Kyung-Il Park (Protist, 2025)

Research on path tracking and attitude control of airboat with wave disturbance observer based on model predictive control - Chunyin Tang; Wankang Wang; Haijiang Shang; Shuhan Shen; Qiming Bao; Wei Ji; Yefeng Long; Dongxing Yang (Ocean Engineering, 2025)

Petrogenesis of granitic pegmatites in the Chinese Altay: Insights from apatite, garnet, and quartz geochemistry - Xin Zhang; Meng-Tao Wang; Zhan-Long Ma; Zi-Zeng Liu; Jing-Yu Zhao; Zheng-Hang Lv; Hui Zhang; Yong Tang (Lithos, 2025)

Resilience of human mobility in response to unexpected events - Junqing Tang; Jixiang Liu; Jiangping Zhou; Long Cheng; Wenjia Zhang; Mengqi An (Journal of Transport Geography, 2025)

Electronic structure engineering of Fe/Co dual-atom catalysts enhances ultrafast Fenton-like reactions mediated by high-valent iron-oxygen-cobalt bridged complexes for safe pollutant removal - Huan Cheng; Peng Wei; Mingjia Liu; Yunhui Yang; Long Huang; Jian Tang; Rong Hu (Journal of Hazardous Materials, 2025)

Synergistic control of antibiotic resistance via natural illite-activated peroxymonosulfate: Efficiency and mechanism - Xiangqin Zhou; Ting Zhou; Jiuqiang Xiong; Wenjun Wang; Yingbin Li; Long Li; Xiang Tang; Zhuotong Zeng; Biao Song; Chengyun Zhou; Jing Tong (Journal of Hazardous Materials, 2025)

Preparation and characterizations of slow-releasing humic acid fertilizer loaded in starch-based hydrogel - Litao Ma; Jiabao Bai; Long Yu; Qingfei Duan; Yue Song; Zhongjie Tang; Fengwei Xie; Zhongxian Li; Xiaodan liu; Xuejun Yu; Deyi Xie (Journal of Environmental Chemical Engineering, 2025)

Effect of catchment characteristics and water physicochemical parameters on nitrogen and phosphorus concentrations in streams and small reservoirs - Long Chen; Qinghu Jiang; Qiuxiang Tian; Boshen Ren; Bichao Tang; Mengzhen Lu; Xiaoxiang Zhao; Feng Liu (Journal of Environmental Management, 2025)

A conserved Piezo–mRPL2/Jun axis controls reproduction via mitochondrial bioenergetics - Jiangwen Luo; Yaru Lu; Zhiruo Zhang; Qian Zhang; Yunzhu Shang; Yajie Yuan; Xiaohui Duan; Long Zhang; Yuxia Tang; Hai Hu; Xiaoling Tong; Fangyin Dai (Insect Biochemistry and Molecular Biology, 2025)

Performance enhancement strategies for lithium-based battery electrodes via covalent organic frameworks: A review of recent advances - Waheed Ahmad; Muhammad Tahir; Batoul Bibi; Liang He; Hui Tang; Longbing Qu; Fazal Ul Nisa; Mizna Naseem; Habib Ullah; Iram Abdul Ghafar; Saira Manzoor; Yihao Long; et al. (Chemical Engineering Journal, 2025)

Self-calibrating metal-semiconductor heterostructures with photoinduced charge transfer for robust SERS detection of patulin - Wei Zeng; Xuemei Tang; Jiyang Li; Yiping Chen; Long Wu (Chemical Engineering Journal, 2025)

Low-cost amorphous mineral gels for highly efficient and ultrafast ruthenium recovery from wastewater - Hong Yue; Yunchen Long; Jie Zhou; Xinxue Tang; Zhihuan Zhou; Jian Lu; Yang Yang Li (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Photoactivation assisted efficient triplet exciton filling for daylight-visible ultra-bright long lived room temperature phosphorescence - Zhaorun Tang; Lin Ding; Jiyang Long; Zhihao Guan; Xianwen Ke; Ruyi Wei; Xinghai Liu (Chemical Engineering Journal, 2025)

Synergistic reaction of NH3 selective catalytic reduction and CO oxidation on in-situ sulfated CoMn2O4/CeTiOx - Ning Luo; Fengyu Gao; Hengheng Liu; Lei Yi; Zirong Niu; Erhong Duan; Honghong Yi; Long Sun; Shunzheng Zhao; Yuansong Zhou; Shangfeng Du; Xiaolong Tang (Chemical Engineering Journal, 2025)

Effects of gum incorporation on the properties of sodium alginate-based composite hydrogel beads for encapsulating lactic acid bacteria - Ying-Ying Jing; Yun-Cheng Li; Yong-Qi Luo; Long-Hua Zou; Yuan-Mou Tang; Yu-Xi Lin; Fan-Bing Meng (Carbohydrate Polymers, 2025)

Soil organic carbon dynamics in Northeast China under water erosion: Spatiotemporal patterns and driving mechanisms - Qi Tang; Li Hua; Zhe Yang; Long Jiang; Qian Wang; Yunfei Cao; Yanqing Xu; Tianwei Wang; Chongfa Cai (CATENA, 2025)

Actinobacteria mediate anaerobic methane oxidation in iron-rich environment - Shubing Li; Zhenzhen Peng; Shuguang Xie; Weiqi Chen; Ying Zhu; Wenwen Huang; Yi Tang; Mengchen Lu; Xunsen Chen; Teng Guo; Fangrong Wei; Jinshao Ye; et al. (Bioresource Technology, 2025)

Quantitative Evaluation of Incomplete Stent Apposition in Intracranial Aneurysms Using Optical Coherence Tomography: a Porcine Model Study - Zhuangzhuang Wei; Ji Ma; Zhike Zhang; Shuailong Shi; Shuhai Long; Shaofeng Shui; Lei Yan; Yan Song; Yi Tang; Ye Wang; Jie Yang; Yuncai Ran; et al. (Translational Stroke Research, 2025)

A herbaceous peony WRKY transcription factor PlWRKY70 enhances tolerance to salt stress in transgenic Arabidopsis thaliana - Ling Tang; Weili Long; Yanhua Pan; Jiaxuan Ren; Weicheng Wang; Rong Huang; Fei Shen (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Palmitoylation modulates antitumor immunity - Feng Tang; Jia-Long Xu; Qing Zhang; Xi Chen; Ze-Fen Wang; Ya-Di Xu; Zhi-Qiang Li (Molecular Biology Reports, 2025)

Construction of a prognostic risk model for clear cell renal cell carcinomas based on centrosome amplification-related genes - Bingru Zhou; Fengye Liu; Ying Wan; Lin Luo; Zhenzhong Ye; Jinwei He; Long Tang; Wenzhe Ma; Rongyang Dai (Molecular Genetics and Genomics, 2025)

A comprehensive analysis of stroke risk factors and development of a predictive model using machine learning approaches - Songquan Xie; Shuting Peng; Long Zhao; Binbin Yang; Yukun Qu; Xiaoping Tang (Molecular Genetics and Genomics, 2025)

A non-invasive continuous glucose monitoring method based on the Bergman minimal model - Ang Li; Long Zhao; Chenyang Wu; Zhanxiao Geng; Lihui Yang; Fei Tang (Medical & Biological Engineering & Computing, 2025)

Cortical contribution related to top-down regulation in tone perception - Xiaotong Zhang; Yuting Tang; Houmin Wang; Zijian Huang; Wahou Tai; Soitou Wong; Zhuoming Chen; Jinyi Long (Cognitive Neurodynamics, 2025)

Norsesquiterpenoids from terrestrial and marine organisms: Chemistry, activity and possible biosynthetic pathways (1963–2024) - Tao-Tao Xue; Bao-Long Hou; Meng-Meng Yuan; Zhi-Shu Tang; Hong-Bo Xu (Phytochemistry, 2025)

Nanoplastics as carriers of organic pollutants in aquatic systems: Mechanisms, influencing factors, and environmental implications - Long Zhang; Xiaoqi Guo; Zhi Qin; Xi Deng; Chenxi Wang; Jian Liu; Jie Tang; Xinyuan Du (Journal of Water Process Engineering, 2025)

Numerical analysis on energy and exergy performance of cascade electrical-temperature vacuum swing adsorption (C-ETVSA) for direct air capture: A parametric effect study - Lanlan Zhang; Jiayu Lin; Yongzhen Wang; Kai Han; Baojun Tang; Yibo Han; Junyao Wang; Long Jiang (Journal of Cleaner Production, 2025)

Microwave-powered ZnFe2O4/SnS2/bagasse cellulose aerogel: A novel green catalyst for rapid Cr(VI) reduction - Gaoqian Yuan; Zihuan Tang; Jingzhe Zhang; Xin Zhang; Kenian Zhou; Long Dong; Xuefeng Liu; Yage Li; Faliang Li; Haijun Zhang; Shaowei Zhang (Journal of Cleaner Production, 2025)

Response of macroinvertebrate drift to dam-induced flow fluctuations: A field experiment in the Yarlung Zangbo river - Jiaxuan Tang; Qinghui Zeng; Fengbo Zhang; Baolong Zhao; Kang Zhao; Qin Yang; Long Yan; Wenhang Su; Pingfeng Li; Jinliang Zhang; Peng Hu (Journal of Environmental Management, 2025)

Influence of fault properties and fold structures on karst sinkholes formation and evolution: Insights from a multidisciplinary analysis - Weizhi Jiao; Zhenwei Dai; Qijun Song; Yujie Wang; Dandan Liu; Jingjun Tang; Long Yang (Geomorphology, 2025)

Non-volatile metabolite profiles and taste quality of Pu-erh raw tea on different storage years by metabolomics and 1H qNMR - Long Chen; Yaqin Long; Hao Qu; Ziwen Luo; Lixue Long; Hongyun Chen; Qiang Chen; Song Tang; Linbo Chen (Food Research International, 2025)

Electroencephalography (EEG) design for flavor perception of Baijiu: An investigation into the influence of full-bodied mouthfeel on brain rhythms - Panpan Chen; Yubo Yang; Jinyuan Sun; Shui Jiang; Imre Blank; Bohan Zhang; Chao Chen; Tianjun Long; Liangyan Chen; Hongyan Tang; Fan Yang; Yuan Liu (Food Chemistry, 2025)

Toxicity mechanisms of metal ions in sugarcane molasses to Saccharomyces cerevisiae: Integrated physiological and transcriptomic insights - Miao Tang; Ruixiang Yuan; Guangwei Huang; Zhike Long; Xuesong Liang; Hecheng Meng; Xiufeng Long (Food Bioscience, 2025)

Spatial heterogeneity of soil Cd and Pb driven by combined effects of pedogenesis and anthropogenic activities: A case study in the mountainous and hilly region of Fujian Province, China - Weikang Sheng; Qingye Hou; Zhongfang Yang; Tao Yu; Long Zhan; Ming Zhang; Mo Zhou; Guoguang Chen; Zhimin Tang; Ying Wang (Environmental Research, 2025)

Co-exposure to bisphenol a and arsenic enhance hepatotoxicity in zebrafish by targeting the hypothalamic–pituitary–thyroid axis and PPAR pathway - Le Zhang; Qiang Li; Yingying Tang; Peng Zhang; Yan Wang; Jianyou Long; Wei Zhang (Environmental Pollution, 2025)

Interaction evaluation and adjusted design of negative-stiffness friction pendulum systems for aboveground-underground connected system with adjacent aboveground structures - Yuanchen Tang; Zhipeng Zhao; Yixian Li; Long Wang; Qingjun Chen (Engineering Structures, 2025)

Novel insights to the synergistic effects of magnetic biochar in anaerobic digestion while treating synthetic organic wastewater for biomethane recovery - Zhang-Wei He; Yuan-Long Jia; Cong-Cong Tang; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Aijie Wang; Rong Chen (Chemical Engineering Journal, 2025)

Non-wetting-confined construction of triboelectric surface with crocodile skin-inspired cap-like mechanoreceptors for ultrasensitive tactile sensation - Long-Xiang You; Bo Tang; Qiang-Wu Tan; Xi Chen; Jia-Bin Wei; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2025)

A dual-mode response fiber paper-based sensor based on curcumin and sodium alginate for soil moisture monitoring - Yu Zhou; Ruqiang Zhang; Youping Tang; Yifeng Huang; Weidong Zhang; Yulong Hu; Xichao Liang; Wenjun Li; Ling Yang; Zhu Long (Chemical Engineering Journal, 2025)

Dual-function fluorescent nanoplatform for simultaneous detection and inhibition of amyloid-β aggregation in Alzheimer's disease - Qingqing Yang; Qiuxia Tu; Qian Zheng; Hongmei Wu; Guijiang Zhang; Qihang Ao; Xinchen Long; Wen Zheng; Lei Tang; Chunlin Zhang; Li Lei (Chemical Engineering Journal, 2025)

Machine learning-guided discovery and stabilization of anomalous Ni4+ oxides with superior electrocatalysis for flow batteries - Jia-Qi Liu; Deng-Hua Zhang; Li-Xin Yang; Fang Liu; Tong-Tong Shi; Yu-Jia Wang; Yun-Long Tang; Yin-Lian Zhu; Xiu-Liang Ma (Chemical Engineering Journal, 2025)

Mendelian randomization combined with real-world study reveals that Streptococcus anginosus exacerbates dietary triglyceride metabolism disorders in obese mice - Xian-Long Shu; Jia-Ling Xie; Xi Li; Guo Wang; Jie Tang (World Journal of Microbiology and Biotechnology, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

4-Hydroxychalcone alleviated Angiotensin II-induced atrial fibrillation via immunoproteasome-IKK-NF-κB signaling pathway modulation - Yun-Long Zhang; Ze-Yan Xu; Yan Sun; Qian-Qiu Zhu; Sheng-Xing Tang; Qing-Hua Zhong; Xiao Han (Journal of Molecular Medicine, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Quaternary Glaciation Accelerates Speciation in Aquatic Snakes Through Recent Bottlenecks - Jin‐Long Ren; Rui‐Han Li; Ru‐Wan Jia; Zhi‐Tong Lyu; Chaochao Yan; Dechun Jiang; Ying‐Yong Wang; Jia‐Tang Li (Molecular Ecology, 2025)
Climatic fluctuations during glacial periods have profoundly shaped the demographic history and gene flow dynamics of many taxa. This study integrated high‐throughput sequencing of 67 individuals with comprehensive genomic analyses to investigate biogeographic patterns, genetic divergence and demographic trajectories in the Opisthotropis latouchii species complex, a group of mountain stream snakes distributed across Central China. Our analyses revealed substantial genetic divergence, identifying four distinct lineages, each confined to one of the four major mountain ranges in Central China, including one previously unrecognised species. These lineages exhibited distinct demographic signatures, with population bottlenecks occurring during Quaternary glaciations. Initial isolation in the glacial refugia of the southern regions of these mountains during the Late Pliocene was followed by postglacial expansions along a northward trajectory, with further divergence along a latitudinal gradient associated with mountain distribution. Notably, the mountain ranges of Central China acted as critical refugia during glacial periods, promoting rapid speciation, and as dispersal corridors during interglacial periods, facilitating range expansion and enabling recent gene flow. These findings highlight the profound impact of Quaternary climatic oscillations on genetic structure, demographic history and gene flow patterns of these endemic taxa.

Unraveling the role of funnel effect vs. gutter effect in water permeance and antifouling performance of polyamide nanofiltration membranes - Chenyue Wu; Li Long; Zhe Yang; Yaowen Hu; Lu Elfa Peng; Chuyang Y. Tang (Water Research, 2025)

Seismic vulnerability analysis of utility tunnel with oblique incidence of SV waves based on IDA method in horizontal non-homogeneous field - Hui-yue Wang; De-long Huang; Hai-ruo Wang; Yang Ding; Hang Cen; Zi-Yuan Huang; Ai-ping Tang; Xia-xin Tao (Soil Dynamics and Earthquake Engineering, 2025)

Mendelian randomization analysis reveals causal associations between autoimmune diseases and female infertility risk - Jinyuan Wang; Haojun Long; Mingxuan Su; Yichang Cao; Runtang Zhou; Xiang Li; Jiangming Li; Yuxia Tang; Jiayi Tang; Simin Wang; Linyue Tang; Ruxin Chen; et al. (Reproductive Toxicology, 2025)

Hydrogeochemical provenance and evolution in Ganhai Well’s groundwater, Eastern Tibetan Plateau - Guanchun Chen; Liang Tang; Long-Fei Gou; Chuan Jiang; Yang Xu (Ore and Energy Resource Geology, 2025)

Separation and recovery of vanadium from leaching solution of calcium roasting vanadium slag by extraction with P204 extractant - Da-long Wang; Lin Zhang; Jing-wei Li; Chen Chen; Yin-he Lin; Zhi Yang; Da-ya Wang; Huan-jian Hou; Jian Chen; Tang-jie Zhou; Wen-ming Tang (Minerals Engineering, 2025)

Interpretable machine learning models for predicting hormesis of binary antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Pei-Pei Zhang; Yan-Peng Liang; Hong-Hu Zeng; Yong-Hong Zhang; Li-Tang Qin (Journal of Hazardous Materials, 2025)

Non-targeted and suspect screening analysis of non-phthalate ester plasticizers in house and car dust - Ning Zhang; Fengli Zhou; Long Zhang; Bize Lai; Shuqin Tang; Xiaotu Liu; Da Chen (Journal of Hazardous Materials, 2025)

Comparison of activated and non-activated peroxymonosulfate and peroxydisulfate for sulfonamide antibiotics degradation: Oxidation mechanism and degradation pathway - Qingyuan Wang; Juan Tang; Junmiao Yu; Xin Liu; Tianyi Long; Jiaxin Zhai; Zhaoli Liu; Wen Liu; Xuan Xing (Journal of Environmental Chemical Engineering, 2025)

Different Effect of H2 and H-donating Solvent on Aromatic Formation during the Direct Coal Liquefaction of Naomaohu Coal - Ning Zhen; Xiao-Dong Zhou; Xue-Long Yin; Jing-Mei Liu; Ya-Kun Tang; Ting Liu; Lang Liu (Fuel, 2025)

Synergistic spectral-spatial fusion in hyperspectral Imaging: Dual attention-based rice seed varieties identification - Shuqi Tang; Nan Zhong; Yuhao Zhou; Shaobin Chen; Zhibao Dong; Long Qi; Xiao Feng (Food Control, 2025)

Calcium and molybdenum isotopes trace eclogitic crust recycling in formation of unique carbonatite-hosted Mo-REE-U-Nb deposits in orogenic belt - Li Tang; Tao Zeng; Thomas Wagner; Tobias Fusswinkel; Long-Long Chen; Jie Li; Rui Wang (Earth and Planetary Science Letters, 2025)

Targeted gene therapy for intracranial aneurysm using SOX17-CRISPRa - Dujie Xie; Yi Yuan; Panyao Long; Juan Huang; Mi Jiang; Yongzhong Tang; Yuanqiang Luo; Cancan Zhang; Ping Zheng; Liang Yang; Yiwei Chen; Xiaobo Li; et al. (Chemical Engineering Journal, 2025)

Competitive ion driven reversible Cu and Ni electrodeposition for smart windows with synergistic optical and thermal regulation - Wenhao Wang; Long Wang; Gu Liu; Lijun Yang; Tonghao Liu; Yina Cui; Lixuan Zhang; Qingyi Kang; Xu Tang; Lele Ma; Jinwen Ren; Xinyu Zhu; et al. (Chemical Engineering Journal, 2025)

Phytochemical characterization, antioxidant, enzyme inhibitory and anti-inflammatory activities of Hedychium coccineum Buch.-Ham. ex Sm. rhizome - Yuanquan Ran; Dan Xie; Dan Long; Lu Jin; Guo Chen; Bing Yang; Dongxin Tang; Minyi Tian (Biochemical Systematics and Ecology, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Bridging missing GNSS phase measurements through cycle slip detection for improved smartphone positioning - Jiahuan Hu; Wu Chen; Pan Li; Xiaolong Mi; Kai Zheng; Long Tang; Wanke Liu; Jingkai Yuan; Sunil Bisnath (Journal of Geodesy, 2025)

Corrigendum to “Cellular uptake of polystyrene nanoplastics with surface Functionalization: An AIE-based quantitative approach” [Anal. Chim. Acta 1362 (2025) 344184] - Long Zhang; Manyu Xue; Qi Xin; Jie Tang; Yin Liu; Zhengyang Bian; Xiaoping Zheng (Analytica Chimica Acta, 2025)

Genetic influence of the brain on epigenetic age acceleration: evidence of a large‐scale genetic correlation study - Chengcheng Li; Jiaze Tang; Junshuan Cui; Niya Long; Wu Cen; Qibo Wu; Ming Yang; Liangzhao Chu; Xingwang Zhou (Biogerontology, 2025)

Integrated Scheduling of Handling and Spraying Operations in Smart Coal Ports: A MAPPO-Driven Adaptive Micro-Evolutionary Algorithm Framework - Yidi Wu; Shiwei He; Haozhou Tang; Zeyu Long; Aibing Xiang (Journal of Marine Science and Engineering, 2025)
This study explores the integrated scheduling optimization of coal port operations, addressing the dual challenges of handling efficiency and resource conservation by coordinating equipment scheduling with stockyard spraying operations. Through a systematic analysis of operational processes in coal ports, a mixed-integer linear programming (MILP) model is developed to achieve global optimization while explicitly quantifying water and electricity consumption in spraying operations. To address this complex problem, we propose a novel hybrid algorithm that integrates a micro-evolutionary algorithm (MEA) framework with multi-agent proximal policy optimization (MAPPO), enabling adaptive decision-making for large-scale real-time scheduling. Three specialized agents for crossover, mutation, and neighborhood search achieve collaborative optimization by observing population features as states, selecting evolutionary operators as actions, and receiving composite rewards based on both population improvement and individual contributions. This strategy facilitates adaptive operator selection and optimal evolutionary direction derivation, collectively guiding population evolution toward high-quality solutions. Extensive experiments on ten scaled instances of a real-world coal port confirm the proposed algorithm’s superior performance. Compared with four other standard algorithms, it consistently yields higher hypervolume (HV) values and lower inverted generational distance (IGD) metrics, which collectively demonstrate stronger convergence capability and higher solution quality.

Isolation of two new isomers of fusarin D from Fusarium sp. G10, an endophytic fungus of Iris japonica - Ya-Nan An; An-Le Tan; Xiao-Ying Long; Yue Zhou; Man He; Xiao-Long Tang (Natural Product Research, 2025)

The effects of pond purification system on intestinal function of channel catfish (Ictalurus punctatus): a focus on intestinal development, digestion and absorption, and junction integrity - Zhong-Bing Zheng; Yu Yang; Jun Liu; Ming-Cheng Zhou; Ju-Hua Li; Long-Jiang Tang; Hai-Long Nie; Kang-Sheng Chen; Feng Liu; Xiang-Ning He; Zhi-Yuan Lu (Frontiers in Marine Science, 2025)
Pond purification system (PPS) is an outdoor aquaculture system designed based on recirculating aquaculture system (RAS) principles, utilizing recirculating water technology, which can achieve large-scale fish farming in the recirculating water system. The purpose of this experiment is to investigate the alterations in growth performance, intestinal histology, digestion-absorption function, and structural integrity of channel catfish raised in PPS. The findings indicated a significant optimization in water quality indicators pertinent to aquaculture, including total nitrogen, total phosphorus, chemical oxygen demand (COD), ammonia nitrogen, nitrite, and dissolved oxygen. Additionally, the growth performance of channel catfish reared in the PPS group was markedly improved. The intestinal morphology of these channel catfish exhibited increased villus height and a reduced number of mucus cells. Furthermore, serum levels of diamine oxidase and D-lactic acid were significantly decreased in channel catfish raised in the PPS group, while the expression of genes related to the apical junction complex was significantly upregulated, suggesting improved intestinal structural integrity. Moreover, the activities of digestive and absorptive enzymes, such as trypsin, amylase, lipase, and Na + -K + -ATPase, were elevated, indicating enhanced digestive and absorptive functions. In conclusion, based on the conditions of this experiment, the pond purification system module used in this study can effectively improve the quality of the aquaculture water, enhance fish growth performance and improve their intestinal health.

Can environmental system reform enhance firms’ export product quality? Evidence from the environmental vertical reform in China’s prefecture-level cities - Yan Jiang; Long Tang; Xiaotian Wei; Cui Huang (Environment, Development and Sustainability, 2025)

Corrigendum to “Impact of cascade reservoirs on nutrients transported downstream and regulation method based on hydraulic retention time” [Water Research 252 (2024) 121187] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Huan Liu; Long Yan; Zefan Yang; Qin Yang; Fengbo Zhang; Jiaxuan Tang; Peng Hu (Water Research, 2025)

Silicon supplementation via carriers to enhance diatom competition with cyanobacterial blooms and remediate eutrophic waters - Rui Zhou; Bang Xiao; Li Zhao; Yangyang Tang; Wei Yang; Huazu Liu; Xiangdong Zhang; Chaowei Yuan; Xinqi Wang; Xizi Long; Qiang He; Wei Li (Water Research, 2025)

Enhanced removal of organic micropollutants using 2D metal-organic framework interlayered nanofiltration membrane - Ruiying Li; Lingyue Zhang; Shuang Zheng; Wenyu Liu; Li Long; Chuyang Tang (Water Research, 2025)

Corrigendum to “Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River” [Sci. Total Environ. 951 (2024) 175535] - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2025)

Comparative analysis of phytoplankton community structure and stability in the Arabian Sea and Bay of Bengal using eDNA metabarcoding - Changwen Li; Ge Xiao; Han Long; Tongxi Ai; Fenghua Tang; Jianfeng Ju; Shenglong Yang; Yan Pi; Lei Gao; Lingbo Ma; Wei Fan; Ming Zhao; et al. (Marine Environmental Research, 2025)

Integrating morphology, ecology, and genomics: Unraveling the population genetic and evolution within the Rosa graciliflora complex - Jia Miao; Liang-Ying Li; Zhen-Long Liang; Yu Feng; Cheng Zhang; Shi-Qi Li; Heng-Ning Deng; Jian Ru; Zhong-Yu Tang; Xin-Fen Gao (Molecular Phylogenetics and Evolution, 2025)

Petrogenesis of Li-mineralized peraluminous granite and aplite in the Yifeng area, northwestern Jiangxi, South China - Wei Zhang; Shao-Yong Jiang; Jia-Xing Song; Yong-Peng Ouyang; Huai-Jin Zhang; Jia-Long Tang (Lithos, 2025)

Ultrasensitive, portable and multiplexed molecular detection of pathogenic bacteria in a cross-validating manner via Argonaute-triggered and reverse-phase enhanced fluorescent lateral flow bioassay - Xiaoqin Tang; Xinyue Li; Yuhan Tian; Qiang Zhang; Shuli Man; Weipan Peng; Long Ma (Journal of Hazardous Materials, 2025)

Effects of dam regulation on macroinvertebrate communities in the Yarlung Zangbo River: A functional trait perspective - Jiaxuan Tang; Qinghui Zeng; Fengbo Zhang; Qin Yang; Long Yan; Kang Zhao; Baolong Zhao; Jinliang Zhang; Peng Hu (Journal of Environmental Management, 2025)

Impact of economic growth and agricultural expansion on forest cover in ASEAN: New evidence for forest transition theory - Caihong Tang; Yunfei Long; Yu Tang; Yunyi Mao (Forest Policy and Economics, 2025)

A flexible self-powered multimodal sensor with low-coupling temperature, pressure and humidity detecting for physiological monitoring and human-robot collaboration - Long Ye; Zhenhua Tang; Junshu Feng; Yan-Ping Jiang; Xin-Gui Tang; Yi-Chun Zhou; Xiangjun Xing; Ju Gao (Chemical Engineering Journal, 2025)

Effects of Emeishan large igneous province on dolomitization: Hydrothermal versus non-hydrothermal - Di Xiao; Wenjie Yang; Xiucheng Tan; Long Wen; Bing Luo; Minglong Li; Yuxin Tang; Jian Cao (Science China Earth Sciences, 2025)

Calycosin alleviates ovariectomy-induced osteoporosis by promoting BMSCs autophagy via the PI3K/Akt/mTOR pathway - Shouyu Xiang; Yinji Luo; Wei Liu; Cheng Tang; Tianyu Zhu; Lai Tian; Tiansheng Zheng; Long Ling; Mingyang Jia; Xing Li; Yanming Cao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Fast-selective electro-driven membrane reactor in fluoride/silica crystallization for microelectronic wastewaters recycling - Yangbo Qiu; Lei Xia; Long-Fei Ren; Chao Wang; Yiping Wan; Yan Zhao; Raf Dewil; Bart Van der Bruggen; Jiahui Shao; Chuyang Y. Tang (Water Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Mineral prediction research using the Geology-based Cyclic Adversarial Network for Anomaly Detection - Long Tang; Bin Liu; Tonghui Luo; Zhongli Zhou; Xiaoyu Zhang (Journal of Geochemical Exploration, 2025)

High value-added conversion of atmospheric pollutants and greenhouse gases: assessment of bottlenecks and optimization strategies for mainstream catalytic technology - Tao Zhong; Xianhu Long; Zhangnan Yao; Ting Li; Huinan Zhao; Su Tang; Shuanghong Tian; Chun He (Journal of Cleaner Production, 2025)

A machine learning-assisted electrochemical nanosensor based on bimetal-codoped MOF composites for simultaneous detection and removal of multiple fluoroquinolone antibiotics - Suisui He; Jiaheng Zhang; Junlin He; Zhonghui Luo; Wen Chen; Huimin Tang; Jiaqi Long; Jun Wang; Hua Wei; Cui-Yun Yu (Journal of Cleaner Production, 2025)

Efficient adsorption behavior and mechanism of butyl xanthate from gold flotation wastewater using enhanced copper-loaded PVA-SA porous aerogel - Yanhua Cao; Jihong Shi; Shuaishuai Lu; Caie Zhang; Gang Long; Xiayan Qin; Yue Kuang; Xinyu Zhang; Songli Guan; Jie Tang (Journal of Environmental Chemical Engineering, 2025)

TET2 promotes UVB-induced cell death by activating RIPK3-MLKL-necroptosis signaling - Daijing Long; Yangfan Xu; Xuemei Li; Yilan Zeng; Ziting Tang; Lulu Liu; Yuanhong Liu; Xiule Zong; Shengbo Yang; Dan Wang (Chemico-Biological Interactions, 2025)

SPI1 triggers the formation of neutrophil extracellular traps in multiple sclerosis through CXCL4 - Wenying Chai; Yiqiang Cao; Sunjiang Liu; Dang Tang; Yiduo Xu; Jiang Long (Journal of Molecular Histology, 2025)

Genome-wide identification and expression analysis of RWP-RK genes in Pyropia haitanensis reveals their roles in gametogenesis - Hong‑Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Cellular uptake of polystyrene nanoplastics with surface Functionalization: An AIE-based quantitative approach - Long Zhang; Manyu Xue; Qi Xin; Jie Tang; Yin Liu; Zhengyang Bian; Xiaoping Zheng (Analytica Chimica Acta, 2025)

Spatiotemporal estimation and local driver analysis of fractional vegetation coverage in the Three-North region, China - Yi Long; Hua Sun; Fugen Jiang; Song Chen; Jie Tang (Advances in Space Research, 2025)

Analysis of the response mechanism in lipid degradation of key gene LDH1 knockout strains of Saccharomyces cerevisiae under levulinic acid stress - Yulei Chen; Jiaye Tang; Qian Li; Wenli Xin; Ximeng Xiao; Borui Mou; Jialian Li; Fujia Lu; Chun Fu; Wencong Long; Hong Liao; Xuebing Han; et al. (Archives of Microbiology, 2025)

Identification, expression analysis, and functional verification of three opsin genes related to the phototactic behaviour of Ostrinia furnacalis - Mei Huang; Jian‐Yu Meng; Xue Tang; Long‐Long Shan; Chang‐Li Yang; Chang‐Yu Zhang (Molecular Ecology, 2025)
Ostrinia furnacalis is a disreputable herbivorous pest that poses a serious threat to corn crops. Phototaxis in nocturnal moths plays a crucial role in pest prediction and control. Insect opsins are the main component of insect visual system. However, the inherent molecular relationship between phototactic behaviour and vision of insects remains a mystery. Herein, three opsin genes were identified and cloned from O. furnacalis ( OfLW , OfBL , and OfUV ). Bioinformatics analysis revealed that all opsin genes had visual pigment (opsin) retinal binding sites and seven transmembrane domains. Opsin genes were distributed across different developmental stages and tissues, with the highest expression in adults and compound eyes. The photoperiod‐induced assay elucidated that the expression of three opsin genes in females were higher during daytime, while their expression in males tended to increase at night. Under the sustained darkness, the expression of opsin genes increased circularly, although the increasing amplitude in males was lower when compared with females. Furthermore, the expression of OfLW , OfBL , and OfUV was upregulated under green, blue, and ultraviolet light, respectively. The results of RNA interference showed that the knockout of opsin genes decreased the phototaxis efficiency of female and male moths to green, blue, and ultraviolet light. Our results reveal that opsin genes are involved in the phototactic behaviour of moths, providing a potential target gene for pest control and a basis for further investigation on the phototactic behaviour of Lepidoptera insects.

Development of an Ellipsoid Based Chart Datum Around the China Seas - Yanguang Fu; Yanxiong Liu; Mehdi Khaki; Fukai Peng; Xiaolong Mi; Yikai Feng; Xiaoli Deng; Long Yang; Qinghua Tang; Li Cui (Marine Geodesy, 2025)

Context-dependent anaerobic oxidation of methane: Insight for methane emission mitigation - Wenwen Huang; Yi Tang; Mengchen Lu; Zhenzhen Peng; Shubing Li; Xunsen Chen; Fangrong Wei; Teng Guo; JinShao Ye; Yan Long (Journal of Environmental Management, 2025)

Food Coloromics: Multi-spectral strategy incorporated with time slicing method and their colorant-oriented-searching workflows for black tea infusion - Piaopiao Long; Mengya Zhang; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2025)

Experimental and modeling investigation of long-term leachability of nickel in re-molded cement-stabilized sediments - Long Chen; Yong-Hui Chen; Pan-Pan Tang; Wan-Lu Zhang (Environmental Research, 2025)

A new insight into the mechanism of cadmium-induced nephrotoxicity and antagonism of selenium nanoparticles: modulation of MTF1-MT axis dependent metal homeostasis - Yi-Xi Tang; Hui-Lin Cao; Jia-Rong Hou; Jian Chen; Shi-Yong Zhu; Yun-Shuang Liang; Zhou-Yi Yang; Kanwar Kumar Malhi; Xin-Yue Mao; Jin-Long Li (Environmental Pollution, 2025)

Dynamic changes in DNA methylation and correlated expressing genes during somatic embryogenesis in Hevea brasiliensis - Ling Li; Jia Miao; Jin Liu; Ming-Chun Gui; Min Tang; Hai Tian; Wan-Yuan Shi; Guo-Ping Liang; Xiao-Long Sun (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Corrigendum to “Critical role for heat shock protein 70 in viral replication of ALV-J via interaction with gp37 and P32,” [Vet. Microbiol. 303 (2025) 110436] - Kensi Zhu; Yanling Pang; Zhihong Luo; Hanyue Zhang; Shuang Tang; Jinjie Liang; Yuecheng Long; Wencheng Lin (Veterinary Microbiology, 2025)

Advancing food safety with SERS: The role of noble metal nanomaterials in detecting food contaminants - Ruiming Wen; Yu Han; Xuemei Tang; Wei Zeng; Sihang Zhang; Long Wu (Trends in Food Science & Technology, 2025)

Great Oxidation Event was caused by Neoarchean global cratonization: opportunity and challenge from rock and sedimentary records in China - Li-Gang Zhou; Jun-Ping Liu; Jing Li; Zai-Bo Sun; Lu Xiang; Yan-Yan Zhou; Hao-Shu Tang; Yan-Bin Zhang; Xi-Yan Zhu; Hai-Long He; Ming-Guo Zhai (Science Bulletin, 2025)

Cleaner purification of contaminants on cotton substrate interfaced with supercritical carbon capsules for sustainable development in cleaning industries - Meng-Yue Li; Fan Wang; An-Tong Liu; Qing-Cheng Tang; Xue Dong; Jia-Jie Long (Process Safety and Environmental Protection, 2025)

Neoproterozoic metasedimentary rocks in the eastern Songnen Massif, NE China: Implications for the early evolution and tectonic affinity of microcontinental massifs in the eastern Central Asian Orogenic belt - Yi-Ting Xue; Jie Tang; Wen-Li Hao; Jin-Peng Luan; Xin-Yu Long; Shuang Liang; Ji-Shuang Ding; Wen-Liang Xu (Precambrian Research, 2025)

A systematic review on mechanism and regulation strategy of marine hydrodynamic noise: Advances, challenges, and perspectives - Xin Jin; Hua-long Huang; Yuan Tao; Fu-gui Zhang; Min Luo; Chang-yuan Fan; Tao Tang (Ocean Engineering, 2025)

Effect of curvature and taper on the hydrodynamic properties of seal whisker inspired cylinders in uniform flow and wake - Yuanji Yao; Qiao Hu; Long Tang; Tongqiang Fu; Liuhao Shan; Tengyue Li (Ocean Engineering, 2025)

Zircon and apatite constraints on the key factors controlling porphyry Mo mineralization in the Shijiawan deposit: Implication for Mo metallogeny in the Qinling Orogenic Belt - Long-Long Chen; Li Tang; Peng-Rui Lv; Ya-Peng Chen; Tao Zeng (Lithos, 2025)

Alternating electric field as an effective inhibitor of bioavailability and phytotoxicity of heavy metals during electric field-assisted aerobic composting - Tao Fu; Chang Shen; Huan Mi; Jiahuan Tang; Long Li; Hao Lin; Huayuan Shangguan; Zhen Yu (Journal of Hazardous Materials, 2025)

Human-impacted land uses enhance network complexity but impair stability of soil microbial communities - Zhenyu Zhang; Junhao Tang; Long Wang; Jin He (Journal of Cleaner Production, 2025)

Short-term effects and mechanisms of micro/nanoplastics on the degradation of microcystin-LR by Sphingopyxis sp. YF1 - Tangjian Peng; Yanqing Tang; Shengyu Zhang; Lihui Huang; Yali Chen; Ziyuan Yu; Xiaoya Ren; Xizi Long; Fei Yang (Journal of Environmental Chemical Engineering, 2025)

Encapsulation of zeaxanthin dipalmitate emulsion with flaxseed polyphenol and protein isolate improves its stability and bioaccessibility - Long Yang; Xin Tang; Ningxia Bu; Dunhua Liu (Food Research International, 2025)

A three-in-one strategy of molecularly imprinted polymers-based electrochemical SERS for sensitive detection of acetamiprid in vegetables - Xuemei Tang; Ting Wu; Caiying Wang; Wei Zeng; Chengzhen Ji; Jing Wei; Long Wu (Food Chemistry, 2025)

A 7-year feed study on the long-term effects of genetically modified maize containing cry1Ab/cry2Aj and EPSPS genes on gut microbiota and metabolite profiles across two generations of cynomolgus macaques - Chenyun Wang; Shengtao Fan; Minghao Li; Yousong Ye; Zheli Li; Weihu Long; Yongjie Li; Zhangqiong Huang; Qinfang Jiang; Wanjing Yang; Rujia Yang; Donghong Tang (Food and Chemical Toxicology, 2025)

A spatiotemporal mixed-enhanced generative adversarial network for radar-based precipitation nowcasting - Long He; Kun Zheng; Huihua Ruan; Shuo Yang; Jinbiao Zhang; Cong Luo; Siyu Tang; Yunlei Yi; Yugang Tian; Jianmei Cheng (Computers & Geosciences, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

Correction: Genetic dissection of flowering time and fine mapping of qFT.A02‑1 in rapeseed (Brassica napus L.) - Yanling Li; Xin Li; Dezhi Du; Qianru Ma; Zhi Zhao; Long Wang; Yongshun Zhang; Huiqin Shi; Hongping Zhao; Huaxin Li; Damei Pei; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2025)

Long-term fertilization legacy effects and temperatures regulate soil microbial function of crop straw decomposition in a greenhouse vegetable field - Long Ma; Dongming Wu; Ruonan Li; Haoan Luan; Jiwei Tang; Liying Wang; Tengfei Guo; Chao Ai; Shaowen Huang (Applied Soil Ecology, 2025)

Self-assembled TMB-CuO2 nanosheets for dual-mode colorimetric and NIR-II photothermal detection of uranyl ion - Yingying Wu; Xiaofeng Tan; Hongyu Gong; Minghui Wang; Gui-long Wu; Na Li; Fen Liu; Hong Xia; Li Tang; Qinglai Yang (Analytica Chimica Acta, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Height and terrain correction of UAV radioactive measurements based on DEM data - Zhipeng Deng; Liangquan Ge; Long Wen; Shengliang Guo; Chuanfeng Tang; Peng Yu; Zekuan Chen (Journal of Environmental Radioactivity, 2025)

Anaerobic reductive dechlorination of chlorobenzenes by an enrichment culture containing Dehalobacter species - Shaohua Cao; Dexuan Tang; Yang Tian; Lianghua Lu; Wenjing Qiao; Tao Long; Jiandong Jiang (International Biodeterioration & Biodegradation, 2025)

A cationic-ordering NASICON-type cathode with high-capacity and long-life span for sodium-ion batteries - Jinhao Wang; Chenjie Lou; Yidan Lu; Lunhua He; Mingxue Tang; Xing-Long Wu; Fengqi Lu (Chemical Engineering Journal, 2025)

Designed amino acid-based deep eutectic solvents as a platform to functionalize biomedical elastomers by polyaddition reactions - Ao Zhen; Ao Wang; Xirui Long; Xiao Wang; Nan Sheng; Qing Tang; Jiehua Li; Hong Tan; Feng Luo; Zhen Li (Chemical Engineering Journal, 2025)

Characterizing Genetic-Predisposed Proteins Involving Insomnia by Integrating Genome-Wide Association Study Summary Statistics - Jiang Long; Meng Dou; Xiangdong Tang; Xiaojing Gu (Molecular Neurobiology, 2025)

Estimation of SOC using VNIR and MIR hyperspectral data based on spectral-to-image transforming and multi-channel CNN - Aohua Tang; Guijun Yang; Zhenhong Li; Yuchun Pan; Yu Liu; Huiling Long; Weinan Chen; Jing Zhang; Yue Yang; Xiaodong Yang; Bo Xu (Computers and Electronics in Agriculture, 2025)

Development and evaluation of 50 K liquid SNP array for blunt snout bream (Megalobrama amblycephala) - Li-Fei Luo; Yao Wang; Shi-Long Wang; Yue Yu; Yu-Ye Fu; Chun-Hong Nie; De-Wen Tang; Ze-Xia Gao (Aquaculture, 2025)

Reverse osmosis membrane fouling caused by typical surfactants in the integrated circuit industry: Fouling mechanism and control strategies - Yingcai Tang; Yin-Hu Wu; Zhuo-Yuan Xiao; Zhuo Chen; Wen-Long Wang; Ao Xu; Nozomu Ikuno; Kameda Hidekuni (Water Research, 2025)

Critical role for heat shock protein 70 in viral replication of ALV-J via interaction with gp37 and P32 - Kensi Zhu; Yanling Pang; Zhihong Luo; Hanyue Zhang; Shuang Tang; Jinjie Liang; Yuecheng Long; Wencheng Lin (Veterinary Microbiology, 2025)

Intensified excessive wastage of key raw metals with expansion of global wind and solar photovoltaic energy development - Li He; Yun-Long Liu; Zhen-Jie Tang; Tong Sun; Yi-Ming Yan; Yong-Feng Xia; Hu-Shen Feng; Wei Ye (Resources, Conservation and Recycling, 2025)

Flax seed meal improved the meat tenderness, nutritional value of fatty acids, and catalase activity of Hu lambs - Hangyu Zhang; Long Guo; Xueying Zhang; Xiangpeng Yue; Fei Li; Fadi Li; Jianyun Tang; Xinji Wang; Wei Zhang; Pengxia Hou (Meat Science, 2025)

Efficient photoreforming of organic solvents into CH4 over 2D donor-π-acceptor conjugated polymers with tunable symmetry - Guoen Tang; Xiangjing Xie; Guanhui Liu; Ting Song; Xiayi Hu; Bei Long; Guo-Jun Deng; Mahmoud Sayed (Chemical Engineering Journal, 2025)

Genetic dissection of flowering time and fine mapping of qFT.A02-1 in rapeseed (Brassica napus L.) - Yanling Li; Xin Li; Dezhi Du; Qianru Ma; Zhi Zhao; Long Wang; Yongshun Zhang; Huiqin Shi; Hongping Zhao; Huaxin Li; Damei Pei; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2025)

Cyanobacteria for environmental, energy and biomedical application: a review - Xiaoya Ren; Mengqi Feng; Meiyi Mao; Xizi Long; Jiafeng Pan; Yan Tang; Pengji Zhou; Tangjian Peng; Hui Wang; Fei Yang (Environmental Chemistry Letters, 2025)

Equatorial plasma bubble detection based on GNSS Doppler index using support vector machine algorithm - Fenkai Zhang; Wu Chen; Fan Xu; Fang Zou; Yuanfan Deng; Long Tang (GPS Solutions, 2025)

Impact of Maternal Exposure to Trace Metal Mixtures on Bone Mineral Density in Children Aged 3–6: Results from the Guangxi Zhuang Birth Cohort, China - Junwang Gu; Huishen Huang; Jun Liang; Qian Liao; Peng Tang; Ying Tang; Jinghua Long; Jiehua Chen; Dongping Huang; Dongxiang Pan; Xiaoyun Zeng; Xiaoqiang Qiu (Biological Trace Element Research, 2025)

Exploring the advantages of artificial neural networks in predicting children's thermal perception and their potential application - Xiaoyun He; Kerry A. Nice; Yuexing Tang; Long Shao (Urban Climate, 2025)

Research status and prospect of purification technology of sulfur-containing odor gas - Yuhan Long; Shunzheng Zhao; Xiaolong Tang; Qingjun Yu; Fengyu Gao; Jun Liu; Ya Wang; Yuansong Zhou; Honghong Yi (Journal of Environmental Sciences, 2025)

Petrogenesis and geodynamic implications of gabbroic diorites of the early Paleozoic Mijiashan ophiolite in the eastern North Qilian Orogenic Belt, NW China - Jiao-Long Zhao; Liang Liu; Qing-Yan Tang; Jin-Rong Wang; Zhen-Xi Yang; Pei-Qing Hu; Xin-Wei Zhai; Saniye Abdereyimu; Zi-Han Dang (Journal of Asian Earth Sciences, 2025)

Reduction in sediment yields from karst terrain in SW China over the past 600+ years - Yunqi Zhang; Bangrun Guo; Wei Li; Lan Tang; Xinxin Zhang; Yi Long; Xinbao Zhang; Bo Tan; Ziteng Luo; Xun Hu; Yong Wang (Global and Planetary Change, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Multifunctional Fe3O4@ZIF-8@Ag nanocomposites and electro-driven droplet adsorption strategy for SERS detection of acetamiprid - Xuemei Tang; Wei Zeng; Caiying Wang; Fei Pan; Jing Wei; Long Wu (Chemical Engineering Journal, 2025)

The protective effect of wearing hearing protection devices in noise-induced hearing loss and its potential influencing factors in the Chinese adult population - Linyan Shu; Zhixing Fan; Jia Tang; Guoyong Xu; Jianyu Guo; Taihua Long; Junle Wu; Minghui Xiao; Shijie Hu; Bin Xiao (Science of The Total Environment, 2025)

Calcium and iron isotope fractionation during felsic magma differentiation - Qiu-Yun Guan; Jin-Xiang Li; Ya-Li Sun; Shi-Lei Tang; Noreen J. Evans; Zhao-Feng Zhang; Li-Yun Zhang; Fu-Long Cai; Wei-Ming Fan; Lin Ding (Lithos, 2025)

Design and preparation of non-porous amorphous PEI-based polymers and their adsorption properties for anionic dyes - Henglong Tang; Mingyue Qian; Zhu Long; Dan Zhang; Chang Sun (Journal of Hazardous Materials, 2025)

Phosphorus speciation in the hyporheic zone and its response to sediment-water quality-biological activity coupling effect - Yue Qu; Jinxi Song; Yongqing Long; Nan Li; Songzhe Fu; Bin Tang; Qihao Tao; Qifan Cui; Ken Qin (Journal of Environmental Management, 2025)

Application of 3-D inversion of AMT data in exploration of concealed nonmetallic deposits: A Case Study on the Huashitou Mountain fluorite deposit in Beishan metallogenic belt, China - Jianhui Hu; Liuyang Xu; Yaotian Yin; Xu Jia; Ping Qi; Zhan Liang; Peng Su; Cheng Liu; Weidong Tang; Long Chen; Yanzhou Wang; Lin Liu (Journal of Applied Geophysics, 2025)

Weak interaction strategy enables enhanced selectivity and reusability of arginine-functionalized imprinted aerogel for phosphate adsorption - Lidong Feng; Tianxiao Leng; Yangbo Qiu; Chao Wang; Long-Fei Ren; Haoyu Sun; Liang Tang; Jiahui Shao; Minghong Wu (Bioresource Technology, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Identification of Geochemical Anomalies Using a Memory-Augmented Autoencoder Model with Geological Constraint - Tonghui Luo; Zhongli Zhou; Long Tang; Hao Gong; Bin Liu (Natural Resources Research, 2025)

Application of sex-specific markers in identifying the sex of Pyropia haitanensis from different sources - Hong-Chang Ding; Hui-Ping Ma; Long-Chen Tang; Xing‑Hong Yan (Journal of Applied Phycology, 2025)

Plasma Ionomic Profile and Interaction Patterns in Coronary Artery Disease Patients - Qing-Qing Zhao; Xian-Long Shu; Zhen Yuan; Qian Gao; Ying Huang; Yuan-Qing Yang; Li-Ming Peng; Guo Wang; Xiao-Ping Chen; Bi-Lian Chen; Jie Tang (Biological Trace Element Research, 2025)

Divergent roles of landscape and young streamflow fraction in stream water quality over seven catchments - Long Sun; Jianfeng Tang; Hongtao Zhao; Lei Yang; Ranhao Sun; Liding Chen (Water Research, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Centrifuge model tests on pile groups under oblique pullout load for single point mooring system through transparent sand - Guangyu Luo; Zhongtao Wang; Gangqiang Kong; Shuangyang Ma; Zhucheng He; Peng Li; Long Tang; Qing Yang (Ocean Engineering, 2025)

Amplified impacts of human activities: Non-linear responses of riverine microbial communities to distribution of land use - Zhenyu Zhang; Junhao Tang; Long Wang; Chongchong Zhu; Qian Xun; Daniel Rosado (Journal of Environmental Management, 2025)

Interaction and bacterial effects of microplastics pollution on heavy metals in hyporheic sediments of different land-use types in the Beiluo River Basin - Bingjie Li; Zeyu Chen; Yuting Zhang; Ruichen Mao; Jinxi Song; Yongqing Long; Bin Tang; Jiayuan Feng; Myint Myint Nyein (Environmental Pollution, 2025)

Research on systematic analysis and optimization method for ice storage cooling system based on model predictive control: A case study - Wenbo Qiang; Ying Liao; Jiewen Deng; Chenwei Peng; Huier Long; Hecheng Yang; Jie Bai; Yangyang Su; Qingpeng Wei; Xinhua Xu; Xiaoliang Tang; Hui Zhang (Energy and Buildings, 2025)

Ultrahigh energy storage density and efficiency of antiferroelectric AgNbO3-based MLCCs via reducing the off-center cations displacement - Ting Tang; Dong Liu; Long Wang; Jiaze Li; Zheng Zhang; Lei Zhao; Bo-Ping Zhang; Li-Feng Zhu (Chemical Engineering Journal, 2025)

Rapid gelation of mechanical robust, conductive, and self-healing lignocellulosic nanofibrils hydrogel toward flexible sensor over a broad temperature spectrum - Zhi-Chao Xu; Yu-Qin Yang; Xiao-Wen Pang; Baiyu Jiang; Peng-Fei Mao; Li-Xiu Gong; Binghao Wang; Li Peng; Long-Cheng Tang; Shi-Neng Li (Chemical Engineering Journal, 2025)

Intelligent online sensing of lubricating oil debris via dual-electrode oil-driven triboelectric nanogenerator - Long Wang; Jian Yu; Ping Wang; Lei Yang; Xijing Yu; Jianlong Qiu; Kunpeng Tan; Yuanbin Tang; Yanjie Guo (Chemical Engineering Journal, 2025)

A Microbially Induced Magnesia Carbonation (MIMC) Method with Potential Application for Crack Healing of Sandstone Cultural Relics: Improving Interfacial Bonding Strength - Zhi-Hao Dong; Xiao-Hua Pan; Chao-Sheng Tang; Dian-Long Wang; Rui Wang; Bin Shi (Rock Mechanics and Rock Engineering, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Maize/soybean intercropping promoted activation of soil organic phosphorus fractions by enhancing more phosphatase activity in red soil under different phosphorus application rates - Long Zhou; Lizhen Su; Hongmin Zhao; Shirui Wang; Yi Zheng; Li Tang (Plant and Soil, 2025)

Relationship between Th17 cell proportion and IL-17/-18 levels and disease progression in patients with multiple myeloma - Wen Liu; Jing Zhu; JiBing Cheng; Qian Tang; SiQi Long (Molecular & Cellular Toxicology, 2025)

Prediction of available energy and amino acid digestibility in the Chinese paddy rice fed to growing pigs - Rui Li; Ganyi Feng; Qing Ouyang; Xianji Jiang; Gang Yang; Xiaojie Liu; Hui Tang; Mingzhou Tian; Qiang Xiang; Menglong Deng; Cimin Long; Ruilin Huang (Animal Feed Science and Technology, 2025)

Optimizing soil resistance and disturbance of bionic furrow opener for paddy field based on badger claw using the CFD-DEM method - Zhenyu Tang; Zhiwei Zeng; Shuanglong Wu; Dengbin Fu; Jihan He; Yinghu Cai; Ying Chen; Hao Gong; Long Qi (Computers and Electronics in Agriculture, 2024)

Down-regulated BNC1 promotes glioma by inhibiting ferroptosis via TCF21/PI3K signaling pathway BNC1TCF21PI3K - Tao Zhang; Long Zhao; Xiaoping Tang (Tissue and Cell, 2024)

QSAR models for predicting key hormesis parameters of quinolone antibiotic mixtures on Vibrio qinghaiensis sp.-Q67 - Ling-Yun Mo; Si-Tong Long; Xia-Chang-Li Xu; Li-Tang Qin; Fan Jiang (Science of The Total Environment, 2024)

Nonfragile memory-based sampled-data control for Unmanned Surface Vehicles with time-varying coupling delay - Xinyuan Long; Hua Chen; Jinhai Zheng; Jisheng Zhang; Mi-An Xue; Yao Tang; Rui Xu; Yang Zhao (Ocean Engineering, 2024)

Bearing performance and failure mechanisms of HSCM piles in marine soft soil under lateral loads - Hang Cen; Jun-nan Zhao; Zhong-ling Zong; De-long Huang; Ding-wen Zhang; Hui-yue Wang; Ai-ping Tang (Ocean Engineering, 2024)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Metal-support interaction in supported Pt single-atom catalyst promotes lattice oxygen activation to achieve complete oxidation of acetone at low concentrations - Tian Tang; ShunZheng Zhao; YunPeng Liu; XiaoLong Tang; Long Sun; YiMing Ma; RongHui Zhu; HongHong Yi (Journal of Hazardous Materials, 2024)

Detecting bioactive compound contents in Dancong tea using VNIR-SWIR hyperspectral imaging and KRR model with a refined feature wavelength method - Teng Long; Xinyu Tang; Changjiang Liang; Binfang Wu; Binshan Huang; Yubin Lan; Haitao Xu; Shaoqun Liu; Yongbing Long (Food Chemistry, 2024)

An efficient bio-stabilization technology with bio‑carbonation of reactive magnesia for soil improvement in cold regions - Rui Wang; Chao-Sheng Tang; Xiao-Hua Pan; Dian-Long Wang; Zhi-Hao Dong; Xiancai Lu (Engineering Geology, 2024)

Fine mapping and candidate gene mining of QSc/Sl.cib-7H for spike compactness and length and its pleiotropic effects on yield-related traits in barley (Hordeum vulgare L.) - Jinhui Wang; Yanyan Tang; Jin Li; Juanyu Zhang; Furong Huang; Qiang Li; Baowei Chen; Li’ao Zhang; Tao Li; Haili Zhang; Junjun Liang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2024)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

Threshold effects of vegetation cover on production-living-ecological functions coordination in Xiangyang City, China - Chao Liu; Meijing Hao; Niwen Tang; Xun Liang; Long Cheng (Environmental Monitoring and Assessment, 2024)

The determining regions, specific genes and markers of sex in Pyropia haitanensis (Bangiales, Rhodophyta) - Long-chen Tang; Hong-chang Ding; Ye-fan Qiu; Xing-hong Yan (Algal Research, 2024)

Vision-based trajectory generation and tracking algorithm for maneuvering of a paddy field robot - Dengbin Fu; Zhiying Chen; Zhiqiang Yao; Zhanpeng Liang; Yinghu Cai; Chuang Liu; Zhenyu Tang; Caixia Lin; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2024)

Insights into the interaction mechanisms between Microcystin-degrading bacteria and Microcystis aeruginosa - Tangjian Peng; Yanqing Tang; Danping Cai; Yuqing Gu; Jia Wei; Jiajia Zhang; Juan Ni; Jun Liu; Xiaoya Ren; Jiafeng Pan; Xizi Long; Hui Wang; et al. (Water Research, 2024)

Effects of soil microplastic heterogeneity on plant growth vary with species and microplastic types - Xiao-Mei Zhang; Wei-Long Li; Wei Xue; Michael Opoku Adomako; Min Tang; Lin-Xuan He; Fei-Hai Yu (Science of The Total Environment, 2024)

Influence of cascade reservoirs on the distribution, transport, and retention patterns of biogenic elements in the Jinsha River - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Long Yan; Jiaming Hou; Jiaxuan Tang; Fengbo Zhang; Kang Zhao; Xinyu Li; Peng Hu (Science of The Total Environment, 2024)

A new parameter for quantitatively characterizing antibiotic hormesis: QSAR construction and joint toxic action judgment - Haoyu Sun; Jingyi Yao; Zhenheng Long; Ruijia Luo; Jiajun Wang; Shu-Shen Liu; Liang Tang; Minghong Wu (Journal of Hazardous Materials, 2024)

Association between maternal metal exposure during early pregnancy and intelligence in children aged 3–6 years: Results from a Chinese birth cohort - Junwang Gu; Huishen Huang; Peng Tang; Qian Liao; Jun Liang; Ying Tang; Jinghua Long; Jiehua Chen; Dongping Huang; Shun Liu; Dongxiang Pan; Xiaoyun Zeng; et al. (Environmental Research, 2024)

Introducing electron-rich thiophene bridges in hot exciton emitter for efficient non-doped near-infrared OLEDs with low turn-on voltages - Ruming Jiang; Zhangshan Liu; Yuanyuan Han; Jiawei Long; Ting Guo; Xia Lan; Mingguang Yu; Ting Fan; Haijun Ma; Yen Wei; Ben Zhong Tang; Zujin Zhao (Chemical Engineering Journal, 2024)

Kinetic study of methanol oxidation for multiple hydrogen-rich substances blending mode - Yongjian Wang; Wuqiang Long; Yuanyou Tang; Hua Tian; Pengbo Dong; Yang Wang; Mingfei Lu; Chunyang Xie (Chemical Engineering Journal, 2024)

Unexpectedly high wet mercury deposition observed in the Yarlung Tsangpo Grand canyon - Jie Huang; Yi Zhang; Shichang Kang; Wenjun Tang; Jinling Liu; Kaiyun Liu; Long Wang; Junming Guo; Lekhendra Tripathee; Wanglin Zhao (Applied Geochemistry, 2024)

Numerical analysis of turbulent mixed convection heat transfer of molten salt in an inclined cooling tube - Wangsheng Tian; Tianji Peng; Yanze Tang; Xukai Fan; Yifeng Wang; Haiyan Meng; Deliang Fan; Xudong Liu; Long Gu (Annals of Nuclear Energy, 2024)

Thermal environmental and energy effects of vertical greening system under the influence of localized urban climates - Zhi-Dian Jiang; Shu-Long Luo; Xing Shi; Shuo-Ning Tang; Feng Qian; Feng Yang (Urban Forestry & Urban Greening, 2024)

Advancements and challenges on SERS-based multimodal biosensors for biotoxin detection - Xuemei Tang; Huan Jiang; Ruiming Wen; Danni Xue; Wei Zeng; Yu Han; Long Wu (Trends in Food Science & Technology, 2024)

Current state, sources, and potential risk of heavy metals in sediments of typical inner lakes in the Dongting Lake Area - Shilin Tang; Yuannan Long; Juan Li; Xiaofeng Wen; Hongwei Chen; You Zhang; Jianyong Chen (Process Safety and Environmental Protection, 2024)

Model tests on chain-soil interaction of anchor pile for taut mooring system through transparent sand - Guangyu Luo; Zhongtao Wang; Gangqiang Kong; Long Tang; Yunhe Li; Qing Yang (Ocean Engineering, 2024)

Early Cretaceous fayalite-, ferrosilite-, and biotite-bearing rhyolitic porphyries in the Baishuizhai area, South China: Formation by fractional crystallization in the shallow crust - Xiao Liu; Qiang Wang; Xi-Jun Liu; Lin Ma; Derek A. Wyman; Gong-Jian Tang; Wei Dan; Zi-Qi Jiang; Hao Wu; Wan-Long Hu; Jin-Heng Liu; Chuan-Bing Xu; et al. (Lithos, 2024)

Potential powered EC-SERS for sensitive detection of acetamiprid - Ting Wu; Xuemei Tang; Wei Zeng; Yu Han; Sihang Zhang; Jing Wei; Long Wu (Journal of Food Engineering, 2024)

Potentially toxic element source apportionment and risk assessment in agricultural soils around a large-scale Pb-Zn mine in Southwest China - Heng Wei; Xuekui Niu; Minmin Li; Canwen Cui; Zhonghua Wei; Wei Long; Man Tang; Hong Yu; Peng Zhang; Liping He; Bo Pan (Journal of Environmental Chemical Engineering, 2024)

Advancements in electrothermal heterogeneous catalytic pollutants: Efficient conductor selection, novel device design and synergistic mechanism studies - Ronghui Zhu; Shunzheng Zhao; Xiaolong Tang; Fengyu Gao; Weixiao Wang; Long Sun; Honghong Yi (Journal of Environmental Chemical Engineering, 2024)

Effect of lactic acid bacteria fermentation on spray-dried egg yolk powder: Powder characteristics, structural properties and gastrointestinal digestibility - Zhe Li; Yanbin Song; Qinyue Tang; Xiang Duan; Long Sheng (Innovative Food Science & Emerging Technologies, 2024)

Decontamination promotes the release of incorporated organic contaminants in hair: Novel insights into non-invasive biomonitoring - Rui-Xin Qin; Xue Cao; Shi-Yi Zhang; Hong Li; Bin Tang; Qi-Long Liao; Feng-Shan Cai; Xian-Zhi Peng; Jing Zheng (Environmental Pollution, 2024)

Seawater corrosive engineering assisted in-situ room temperature synthesis of Ni/Co/Fe trimetallic composition to achieve polyester plastics upgrading and green hydrogen production - Zhao-Hui Zhang; Zhi-Ran Yu; Yi Zhang; Alexandre Barras; Ahmed Addad; Pascal Roussel; Long-Cheng Tang; Sabine Szunerits; Rabah Boukherroub (Chemical Engineering Journal, 2024)

Enhancing the electromagnetic interference shielding performance of composite paper with corrugated paper-like structure - Jiasheng Wei; Ping He; Yantao Yang; Chunxia Tang; Zhu Long; Xiao Chen; Tingzhou Lei; Lei Dai (Chemical Engineering Journal, 2024)

Review on Mn/zeolite: Active species, influence factors and application in air pollution control - Wenjing Wu; Honghong Yi; Xiaolong Tang; Grandprix T.M. Kadja; Shunzheng Zhao; Yuanyuan Zhang; Fengshi Meng; Long Sun; Yuan Yao; Zirong Niu; Ya Wang; Qingjun Yu (Chemical Engineering Journal, 2024)

Se-vacancy porous ultrathin ZnSe nanosheet/carbon composite for sodium storage via electron beam irradiation strategy - Chaoyan Jiang; Long Zhang; Xinglong Gao; Wenze Yu; Chong Hu; Wenxin Tang; Zhen Li; Lingli Cheng; Minghong Wu (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Melatonin-coated nanofiber cell sheets promote periodontal regeneration through ROS scavenging and preservation of stemness - Weibing Tang; Fangjun Huo; Rongbai Ju; Xinghui Gao; Min He; Jie Long; Jingyi Zhang; Siyuan Zhang; Weidong Tian (Chemical Engineering Journal, 2024)

Promoting charge separation in conjugated polymer for superior photocatalytic decomposition of DMSO to CH4 under sunlight illumination - Guoen Tang; Yizheng Chen; Ting Song; Xiayi Hu; Bei Long; Atif Ali; Guo-Jun Deng (Chemical Engineering Journal, 2024)

Global risk dynamics of Borrelia miyamotoi in the context of climate change - Tian Tang; Hong‐Han Ge; Tian Ma; Meng‐meng Hao; Shuai Chen; Chen‐Long Lv; Yun‐Bo Qiu; Yan‐He Wang; Yao Tian; Jin‐Jin Chen; Shuai Yuan; Qian Wang; et al. (Environmental Microbiology, 2024)
The impact of Borrelia miyamotoi on human health, facilitated by the expanding geographical distribution and increasing population of Ixodes ticks, remains obscure in the context of global climate change. We employed multiple models to evaluate the effect of global climate change on the risk of B. miyamotoi worldwide across various scenarios. The habitat suitability index of four primary vector tick species for B. miyamotoi , including Ixodes persulcatus , Ixodes ricinus, Ixodes pacificus and Ixodes scapularis , was projected using a boosted regression tree model, considering multiple shared socio‐economic pathway scenarios over various time periods. The modelling analysis reveals that, apart from I. scapularis , future global warming will result in a northward shift in the other three vector tick species and a gradual reduction in suitable habitats. Random forest models indicate consistent changes in B. miyamotoi and its primary tick species, with potential risk areas shrinking and shifting northward, particularly in the eastern USA, northeastern and northern Europe and northeast Asia. These findings highlight the urgent need for enhanced active surveillance of B. miyamotoi infection in primary vector tick species across projected potential risk areas. The effect of climate change on B. miyamotoi distribution might have significant implications for public health decision‐making regarding tick‐borne pathogens.

Capture-based hatchery of black tiger shrimp (Penaeus monodon) in Vietnam: an analysis of resource utilisation and challenges - Son Nam Vo; Thuy Thi Le Cu; Tao Tai Chau; Long Thanh Nguyen; Tinh Thien Tang; Hoa Van Au; Khoa Nguyen Duy Tran; Quynh Do Nguyen; Viet Van Ho; Tu Quang Trinh; Tran Bao Phan; Wendy Norden; et al. (Frontiers in Marine Science, 2024)
Introduction This study aimed to evaluate the status, resource use, and challenges of the capture-based hatchery of black tiger shrimp ( Penaeus monodon) (BTS). Methods Data was obtained through the investigation of 15 broodstock fishing boats and 60 capture-based BTS broodstock hatcheries. Resource use index (RUI) of the capture-based BTS hatchery, calculated from 1,000 female brooders to produce 15-day-old post-larvae (PL 15 ) (production efficiency of PL 15 , or PE-PL 15 ), was analysed. Results The results indicated that the fishing boats captured an average of 5,900 brooders.boat -1 .year -1 , 20,856 kg of by catch.boat -1 .year -1 , and the PE-PL 15 production of 937 million for 1,000 female brooders. In the hatchery stage, the use of larger body weight female brooders had benefits in terms of higher survival rate and better efficiency of labour use, Artemia cyst, and probiotic products, but it reduced the efficiency use of chemicals, pellets, and total tank volume of the hatchery. Discussion There is increasing use of domesticated brooder sources, but wild-caught brooders still play an important role in producing low-cost PL 15 for traditional shrimp farming systems, accounting for most farmed BTS production. Therefore, the certification of good practices should be implemented to capture-based BTS hatcheries for the reasonable use of this brooder resource to sustain BTS farming in Vietnam.

The time-advance effect of China's rooftop solar photovoltaics program on the dual carbon targets and its implication on the globe - Hong-Wei Lu; Yi-Ming Yan; Dong-Zhe Liang; Xu Duan; Heng-Chen Li; Yun-Long Liu; Zhen-Jie Tang (Sustainable Cities and Society, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Risk of hydrogen sulfide pollution from pressure release resulting from landfill mining - Haomin Zhou; Jia Jia; Lu Tang; Dongsheng Shen; Lifang Hu; Yuyang Long (Journal of Hazardous Materials, 2024)

Disinfection-residual bacteria (DRB) after chlorine dioxide treatment: Microbial community structure, regrowth potential, and secretion characteristics - Yingcai Tang; Yin-Hu Wu; Hao-Bin Wang; Zhuo Chen; Wen-Long Wang; Xin-Ye Ni; Ao Xu; Hong-Ying Hu (Journal of Hazardous Materials, 2024)

Hydrothermal enrichment of rare earth elements in the Lower Permian Lijiatian bauxite deposit, southern China - Kunyue Ling; Yongzhen Long; Suxiong Guo; Yanwen Tang; Zhihui Dai; Hanjie Wen (Journal of Geochemical Exploration, 2024)

Numerical simulation of fault activity in the Qilian tectonic belt and dynamic background of Menyuan earthquake series - Yuan Li; Xia Liu; Anfu Niu; Wei Zhan; Long Feng; Zheng Tang (Journal of Geodynamics, 2024)

Cellular damage and response mechanisms of Candida tropicalis SHC-03 induced by toxic byproducts in corn stover hydrolysate - Zhengyue Zhang; Lan Wu; Qian Li; Baichao Shu; Dang Li; Yulei Chen; Jiaye Tang; Siyi Long; Jie Liao; Yifan Zhao; Hanyu Wang; Menggen Ma (International Biodeterioration & Biodegradation, 2024)

Different activation of STAT1 and STAT2 phosphorylation by IFNc, IFNd, and IFNh in tilapia - Qingqing Wen; Shaoshuai Tang; Jingyi Mo; Meiling Zhang; Meng Long; Yishan Lu; Zhen Gan (Fish & Shellfish Immunology, 2024)

Efficient removal of perrhenate/pertechnetate by a pyridinium-based porous polymer - Miaomiao He; Yuxuan Chen; Guangyuan Chen; Wenhao Li; Mingxing Zhang; Chao Zhang; Hao Zhang; Xingyi Long; Kui Tang; Tao Duan; Lin Zhu (Environmental Pollution, 2024)

Defect detection within filling layer of subway slab ballastless track based on impulse response method - Jiebo Peng; Xiaohui Zeng; Zhuo Tang; Guangcheng Long; Youjun Xie (Engineering Structures, 2024)

Simulation of the physiological and photosynthetic characteristics of C3 and C4 plants under elevated temperature and CO2 concentration - Wei Tian; Chenfei Su; Nan Zhang; Yuwei Zhao; Long Tang (Ecological Modelling, 2024)

Revealing La doping activation or inhibition of crystal facet effects in Co3O4 for catalytic combustion and water resistance improvement - Erhong Duan; Yahan Wang; Saifei Wang; Jingyu Bai; Dongsheng Li; Long Zhang; Jiguang Deng; Xiaolong Tang (Chemical Engineering Journal, 2024)

Adsorption-desorption of copper(II) by temperature-sensitive nano-biochar@PNIPAM/alginate double-network composite hydrogel: Enhanced mechanisms and application potentials - Haolin Chen; Yiwei Pan; Wei Zhang; Anlin Long; Mengqi Chen; Xinxin Xiao; Ziyi Wang; Meiyi Tang; Yazhou Peng; Shiquan Sun; Huining Zhang; Qiulai He (Chemical Engineering Journal, 2024)

Photothermal flows activated CsPbBr3 ⊆ Pb-TCPP S-scheme heterojunction: In-situ converted interface for robust CO2 reduction coupling with benzylamine oxidation - You-Guo Luo; Cheng-Long Peng; Luo-Bing Tang; Jian-Yong Zhang; Hao-Zhi Wang; Yu-Feng Liu; Qin-Fei Ke; Yong-Zheng Fang; Na Zhang (Chemical Engineering Journal, 2024)

Diaporpyrone E, an undescribed α-pyrone from the endophytic fungus Diaporthe sp. CB10100 - Hong Pu; Dian Peng; Genyun Tang; Qingxian Ma; Huaiyi Huang; Yani Zhong; Jiayao Long; Xueshuang Huang; Yanwen Duan; Yong Huang (Natural Product Research, 2024)

Kurarinone, a flavonoid from Radix Sophorae Flavescentis, inhibits RANKL-induced osteoclastogenesis in mouse bone marrow–derived monocyte/macrophages - Ling Long; Hao Luo; Yi Wang; Jiaxiang Gu; Jiachao Xiong; Xiaokai Tang; Hao Lv; Faxin Zhou; Kai Cao; Sijian Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Microglia in Microbiota-Gut-Brain Axis: A Hub in Epilepsy - Yuyang Liu; Ningkang Jia; Chuqi Tang; Hao Long; Jun Wang (Molecular Neurobiology, 2024)

Assessing the causal relationship between immune cells and prostatitis: evidence from bidirectional mendelian randomization analysis - Genyi Qu; Weimin Jiang; Zhaohui Long; Xing Zhou; Yijie Wang; Guang Yang; Cheng Tang; Yong Xu (Mammalian Genome, 2024)

Reclassification of Streptomyces violarus (Artamonova and Krassilnikov 1960) Pridham 1970 as a Later Heterotypic Synonym of Streptomyces violaceus (Rossi Doria 1891) Waksman 1953 using a Polyphasic Approach - Pei-Lan Long; Yin-Feng Wang; Li Fu; Yan Xiao; Shan-Guang Tang; Jian Gao (Current Microbiology, 2024)

High resolution regional climate simulation over CORDEX East Asia phase II domain using the COAWST Ocean-atmosphere coupled model - Mengyuan Long; Ke Yu; Yutong Lu; Shuyu Wang; Jianping Tang (Climate Dynamics, 2024)

Curcumin Inhibits the Development of Pancreatic Cancer by Targeting the circ_0079440/miR-522-3p/EIF4A1 Pathway - Ruiying Luo; Shuang Li; Chi Yang; Baoyuan Tang; Long Li; Changjiang Luo (Cell Biochemistry and Biophysics, 2024)

Prenylated dihydroflavones from the root barks of Morus alba - Jun-Yu Zhu; Han-Zhuang Weng; Di-Kai Tang; Jin-Chen Long; Zhuo-Ya Tang; Ye Chen; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2024)

Design and test of target application system between rice plants based on light and tactile sensing - Xueshen Chen; Chonggang Tao; Cunyao Tang; Yanxue Chen; Enzao Zhang; Long Qi (Crop Protection, 2024)

Deciphering how promoting land consolidation for village revitalization in rural China: A comparison study - Yanfeng Jiang; Hualou Long; Yu-ting Tang; Wu Deng (Journal of Rural Studies, 2024)

Glucose isomerization into fructose with CaO-MgO mixed oxides and dolomite(ore)-derived base CaO/MgO catalysts in water under mild conditions - Siyu Long; Zhangbao Huang; Qishi Du; Peiduo Tang; Xuequan Xian; Fangli Du; Yanming Li (Fuel, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Role of NiO in wide-bandgap perovskite solar cells based on self-assembled monolayers - Afei Zhang; Mingyu Li; Chong Dong; Wenjiang Ye; Yongxin Zhu; Jiakuan Yang; Long Hu; Xiong Li; Ling Xu; Ying Zhou; Haisheng Song; Chao Chen; et al. (Chemical Engineering Journal, 2024)

Smart nodding duck: A hybrid Halbach electromagnetic piezoelectric self-powered sensor for smart fisheries - Long Wang; Hongjie Tang; Zutao Zhang; Yajia Pan; Dabing Luo; Bendong Xiong; Tengfei Liu; Congcong Zhang; Hao Wang; Weihua Kong (Chemical Engineering Journal, 2024)

Suspended sediment-discharge hysteresis characteristics and controlling factors in a small watershed of southern China - Yu Long; Ming Lei; Taoxi Li; Peiyao Xiao; Siyuan Liu; Jiaming Xu; Fang Tang; Xuexiang Hu; Xizhong Hu; Xiaodong Nie; Zhongwu Li; Yaojun Liu (CATENA, 2024)

A sustainable method to increase the strength of warm permafrost: Ice nucleation active bacteria-based - Juanjuan Zheng; Liyun Tang; Peiyong Qiu; Jianguo Zheng; Li Han; Gaosen Zhang; Long Jin; Tao Zhao; Yongtang Yu; Hailiang Jia (Cold Regions Science and Technology, 2024)

Total Flavonoids of Aurantii Fructus Immaturus Regulate miR-5100 to Improve Constipation by Targeting Fzd2 to Alleviate Calcium Balance and Autophagy in Interstitial Cells of Cajal - Yong Wen; Yu Zhan; Taiyu Chen; Jun Li; Qing Long; Fan Zheng; Shiyu Tang; Xuegui Tang (Molecular Neurobiology, 2024)

Identification of candidate genes associated with blade length in Pyropia haitanensis based on BSA-seq and RNA-seq analysis - He-Ye Liu; Hong-Chang Ding; Long-Chen Tang; Ye-Fan Qiu; Xing-Hong Yan (Journal of Applied Phycology, 2024)

Simplified Calculation of Earthquake Energy Transfer of Different Pipe Supports Inside Utility Tunnel at Horizontal Non-Homogeneous Field - De-long Huang; Hang Cen; Jin Wang; Hui-yue Wang; Qiang Liu; Zhong-ling Zong; Ai-ping Tang; Song-ling Xue (Geotechnical and Geological Engineering, 2024)

Establishment and characterization of the PDAC-X3 cell line: a novel Chinese-origin pancreatic ductal adenocarcinoma cell line - Changpeng Chai; Huan Tang; Xin Miao; Yuanhui Su; Lu Li; Cheng Yu; Jianfeng Yi; Zhenzhen Ye; Long Miao; Bo Zhang; Zhengfeng Wang; Wei Luo; et al. (Human Cell, 2024)

Associations between maternal exposure to multiple metals and metalloids and blood pressure in preschool children: A mixture-based approach - Jinghua Long; Huishen Huang; Peng Tang; Jun Liang; Qian Liao; Jiehua Chen; Lixiang Pang; Kaiqi Yang; Huanni Wei; Manlin Chen; Xiaolin Wu; Dongping Huang; et al. (Journal of Trace Elements in Medicine and Biology, 2024)

Fabrication of bimetallic Ag@ZnO nanocomposite and its anti-cancer activity on cervical cancer via impeding PI3K/AKT/mTOR pathway - Qinghua Yin; Qiang Zhou; Jianbing Hu; Jie Weng; Songlian Liu; Leilan Yin; Ling Long; Yajun Tong; Kewei Tang; Site Bai; Ludi Ou (Journal of Trace Elements in Medicine and Biology, 2024)

Engineering of molecularly imprinted cavity within 3D covalent organic frameworks: An innovation for enhanced extraction and removal of microcystins - Yu-Hong Tang; Tian-Tian Ma; Xu-Qin Ran; Yukun Yang; Hai-Long Qian; Xiu-Ping Yan (Journal of Hazardous Materials, 2024)

A comparative study on hydrocarbon detection using cepstrum–based methods - Cong Tang; Kang Chen; Qing-Lin He; Long Wen; Qi Ran; Bin Luo; Jing-Hui Chang; Ya-Juan Xue (Journal of Applied Geophysics, 2024)

Construction of blackberry polysaccharide nano-selenium particles: Structure features and regulation effects of glucose/lipid metabolism in HepG2 cells - Dou Zu-Man; Zhang Yu-Long; Tang Chun-Yang; Liu Chuang; Fang Jia-Qin; Huang Qiang; Chen Chun; You Li-Jun; Tan Chin-Ping; Niu Hui; Fu Xiong (Food Research International, 2024)

Chemical, sensory and biological variations of black tea under different drying temperatures - Shengxiao Su; Piaopiao Long; Qing Zhang; Mingchun Wen; Zisheng Han; Feng Zhou; Jiaping Ke; Xiaochun Wan; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2024)

Study of the dynamic interactions between helix-stiffened cement mixing piles and soft soil under oblique incidence of SV waves in arbitrary space - Hang Cen; Zhong-ling Zong; De-long Huang; Hui-yue Wang; Xiao-xuan Zhuang; Zi-yuan Huang; Ai-ping Tang (Computers and Geotechnics, 2024)

Large-scale and facile fabrication of phenyl-containing silicone foam materials with lightweight, wide-temperature flexibility and tunable pore structure for exceptional thermal insulation - Yu-Yue Wu; Zhi-Hao Wu; Zuan-Yu Chen; Li-Dong Peng; Zi-Qi Guan; Yang Li; Cheng-Fei Cao; Guo-Dong Zhang; Jie-Feng Gao; Pingan Song; Yong-Qian Shi; Long-Cheng Tang (Chemical Engineering Journal, 2024)

Chronic Fluoride Exposure Induces Ovarian Dysfunction and Potential Association with Premature Ovarian Failure in Female Rats - Xiaoke Tang; Hongjuan Li; Yali Wang; Li Zeng; Ling Long; Yajun Qu; Hui Yang; Xiaolin Zhang; Yanmin Li; Yanni Yu; Qi Zhou; Man Luo (Biological Trace Element Research, 2024)

Effects of equatorial plasma bubble-induced ionospheric gradients on GNSS PPP-RTK - Long Tang; Fenkai Zhang; Pan Li; Yuanfan Deng; Wu Chen (GPS Solutions, 2024)
Equatorial plasma bubble (EPB) exerts a severe threat to global navigation satellite system (GNSS) technique. It not only can lead to ionospheric scintillation, but also can create strong plasma gradients in ionosphere. In this study, we investigate the effects of EPB-induced ionospheric gradients on GNSS precise point positioning with real-time kinematic (PPP-RTK) technique for the first time. A common medium-scale EPB event occurred in ionosphere over the southern U.S. on May 28, 2017 is served as a case. The results show, during the period of the EPB event, the interpolated ionospheric residuals are very large with maximum 7.5 TECU without EPB correction while the counterparts are generally below 1 TECU with EPB correction. As for the 3D positions, EPB-induced ionospheric gradients mainly affect the initialization or re-initialization process of PPP-RTK solutions, which significantly increase the estimated errors and lengthen the convergence times. This study can help the GNSS community understand EPB’s impacts on GNSS PPP-RTK more deeply and provide support for its mitigation in the next work.

Thioclava litoralis sp. nov., a novel species of alphaproteobacterium, isolated from surface seawater - Dakun Chen; Huimin Fan; Shaoshuai Tang; Zhen Gan; Yishan Lu; Meng Long (Archives of Microbiology, 2024)

Photochemically induced aging of polystyrene nanoplastics and its impact on norfloxacin adsorption behavior - Long Zhang; Zhi Qin; He Bai; Manyu Xue; Jie Tang (Science of The Total Environment, 2024)

Simultaneous characterization and quantification of 25 flavonoid compounds in Actinidia arguta Miq. leaves by HPLC-DAD and screening for their inhibitory activity on α‑glucosidase - Yu-Fei Hou; Lu Bai; Shao-Jing Liu; Sen Guo; Ya-Long Wang; Chi-Tang Ho; Nai-Sheng Bai (Phytochemistry Letters, 2024)

3D visualization of oil-abundant limon flavedo layer under drying - Sara Shamim; Zhenting Wu; Yuling Tang; Jingru Jia; Chunju Liu; Haiou Wang; Fangcheng Zheng; Long Ba (Journal of Food Engineering, 2024)

Early warning for thermal runaway in lithium-ion batteries during various charging rates: Insights from expansion force analysis - Kuijie Li; Long Chen; Xuebing Han; Xinlei Gao; Yao Lu; Depeng Wang; Shun Tang; Weixin Zhang; Weixiong Wu; Yuan-cheng Cao; Languang Lu; Jinyu Wen; et al. (Journal of Cleaner Production, 2024)

Geometric and electronic engineering of cobalt, manganese oxide sites in porous nitrogen-doped carbon for boosted oxygen reduction activity in microbial fuel cell - Wenyi Wang; Long Tang; Cheng Chen; Wencong Sun; Yuanyuan Wang; Xueqin Wang (Journal of Environmental Chemical Engineering, 2024)

Research on oxidation mechanism of hydrogen/syngas-methanol and its application on engine performance prediction - Yongjian Wang; Wuqiang Long; Hua Tian; Pengbo Dong; Mingfei Lu; Yuanyou Tang; Yang Wang; Weiqi Zhang (Fuel, 2024)

Locally released H2 and O2 from an artificial periosteum modulate the survival and reparative activities of stem cells derived from the aged human nasal mucosa after transplantation - Wentao Shi; Sainan Chen; Xuan Zhang; Lu Bian; Mengyuan Yu; Jun Wang; Suyin Feng; Long Lv; Yunduan Que; Hong Tang; Qing Wang; Xuechao Wu; et al. (Chemical Engineering Journal, 2024)

High-precision microcline 40Ar/39Ar dating by combined techniques - Xiu-Juan Bai; Yi-Long Li; Rong-Guo Hu; Xiao Liu; Bin Tang; Xiang-Ping Gu; Hua-Ning Qiu (Chemical Geology, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Retraction Note: Comparison of preoperative ultrasound and MRI in the diagnosis of microvascular invasion in hepatocellular carcinoma - Yunmin Long; Zheng Lv; Shaoyi Wang; Bing Tang; Qin Li; Wei Zhang (Functional & Integrative Genomics, 2024)

Single-Cell Sequencing Technology and Its Application in the Study of Central Nervous System Diseases - Yang Ding; Yu-Yuan Peng; Sen Li; Can Tang; Jie Gao; Hai-Yan Wang; Zai-Yun Long; Xiu-Min Lu; Yong-Tang Wang (Cell Biochemistry and Biophysics, 2024)

New sight in arginine-improved flesh quality: Role of MRFs, cyclins, and WNT signaling in grass carp (Ctenopharyngodon idellus) - Yu-Long Ma; Xiao-Qiu Zhou; Pei Wu; Wei-Dan Jiang; Yang Liu; Hong-Mei Ren; Rui-Nan Zhang; Shu-Wei Li; Ling Tang; Lin Feng (Aquaculture, 2024)

Non-fragile control associated with exponential stability for unmanned surface vessels with the rudder failure and dynamic event-trigger - Xinyuan Long; Hua Chen; Jinhai Zheng; Mi-An Xue; Rui Xu; Yao Tang; Yang Zhao (Ocean Engineering, 2024)

Aniline antioxidants in road dust, parking lot dust, and green-belt soil in Harbin, a megacity in China: Occurrence, profile, and seasonal variation - Ye Zhang; Jin-Nong Li; Jian-Xin Wang; Jie Hu; Jia-Lin Sun; Yi-Fan Li; Wen-Long Li; Zhong-Hua Tang; Zi-Feng Zhang (Journal of Hazardous Materials, 2024)

Photothermal performance of vitreous products from high-temperature melting of hazardous waste - Mengxiong Yu; Lu Tang; Dongsheng Shen; Foquan Gu; Lulu Wang; Yuyang Long (Journal of Cleaner Production, 2024)

Preparation of microencapsulated coagulants and application to oil–water separation under gravity coagulation conditions - Hailin Yu; Huili Zhang; Gang Liu; Xin Chen; Xuyu Chen; Yihai Yang; Zhengnan Sun; Long Tang; Long Dong; Yingjun Wang; Hongsheng Liu (Fuel, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

A creep model for soil-rock mixture considering the effect of rock contents and freeze-thaw cycles - Peiyong Qiu; Liyun Tang; Pengyu Wang; Jianguo Zheng; Weibing Wang; Yongqiang Li; Guoyu Li; Long Jin; Yongtang Yu; Xu Duan (Engineering Geology, 2024)

A siloxane-based self-healing gel electrolyte with deep eutectic solvents for safe quasi-solid-state lithium metal batteries - Yuxin Chen; Canhui Ling; Kecheng Long; Xinsheng Liu; Pengfei Xiao; Ying-Zhi Yu; Weifeng Wei; Xiaobo Ji; Wenyan Tang; Gui-Chao Kuang; Libao Chen (Chemical Engineering Journal, 2024)

Methylmercury photodegradation in paddy water: An overlooked process mitigating methylmercury risks - Huan Zhong; Hangyu Zhou; Yanbin Li; Chengjun Li; Martin Tsz-Ki Tsui; Carl P.J. Mitchell; Yang Zhou; Yanan Yang; Long Chen; Hongqiang Ren; Wenli Tang (Water Research, 2024)

Recent advances in catalytic oxidation of VOCs by two-dimensional ultra-thin nanomaterials - Long Sun; Shunzheng Zhao; Xiaolong Tang; Qingjun Yu; Fengyu Gao; Jun Liu; Ya Wang; Yuansong Zhou; Honghong Yi (Science of The Total Environment, 2024)

Occurrence, distribution, and risk assessment of antibiotics in a typical aquaculture area around the Dongzhai Harbor mangrove forest on Hainan Island - Tuan-Tuan Wang; Shuai Shao; Shi-Di Fan; Wang-Qing Tang; Jiang-Wei Miao; Sai Wang; Xiao-Cong Cao; Chuan Liu; Guang-Guo Ying; Zhong-Bing Chen; Hai-Long Zhou; Xiao-Ping Diao; et al. (Science of The Total Environment, 2024)

Enhanced removal of toluene in heterogeneous aquifers through injecting encapsulated ozone micro-nano bubble water - Dongsheng Shen; Lili Li; Jian Luo; Jia Jia; Lu Tang; Yuyang Long; Jiali Shentu; Li Lu; Weilin Liu; Shengqi Qi (Journal of Hazardous Materials, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Host-guest synergistic hydrogen bond triggered signal amplification for visualizing the plant hormone salicylic acid - A-Ling Tang; Li-Long Zhang; Shuai Tan; Ping Yang; Wei Niu; Mei-Hong Ge; Lin-Lin Yang; Pei-Yi Wang; Li-Wei Liu; Xiang Zhou; Song Yang (Chemical Engineering Journal, 2024)

Regional climate model intercomparison over the Tibetan Plateau in the GEWEX/LS4P Phase I - Jianping Tang; Yongkang Xue; Mengyuan Long; Mengnan Ma; Xin-Zhong Liang; Shiori Sugimoto; Kun Yang; Zhenming Ji; Jinkyu Hong; Jeongwon Kim; Haoran Xu; Xu Zhou; et al. (Climate Dynamics, 2024)

Metabolomics-based study of chemical compositions in cellulase additives derived from a tobacco-origin Bacillus subtilis and their impact on tobacco sensory attributes - Xiaofeng Chen; Teng Long; Shixin Huang; Yiqiang Chen; Hongliang Lu; Zhenkun Jiang; Cheng Cheng; Jingjing Li; Shanyi Chen; Wei He; Xu Tang; Jianqiang Fan (Archives of Microbiology, 2024)

Impact of cascade reservoirs on nutrients transported downstream and regulation method based on hydraulic retention time - Baolong Zhao; Qinghui Zeng; Jianhua Wang; Yunzhong Jiang; Huan Liu; Long Yan; Zefan Yang; Qin Yang; Fengbo Zhang; Jiaxuan Tang; Peng Hu (Water Research, 2024)

Sodium caseinate medium promotes the in vitro digestion of starch: An insight into the macromolecular crowding effect - Yu-Long Sun; Yi-Fan Tang; Lei Wang; Mi-Zhuan Li; Zhong-Xiu Chen (Food Chemistry, 2024)

Exploring xylitol as a low-salt alternative for effective inhibition of gelation in frozen egg yolks - Xiaoli Xu; Zhe Li; Qinyue Tang; Bao Chen; Haobo Jin; Yaqin Yang; Dewei Shu; Zhaoxia Cai; Long Sheng (Food Chemistry, 2024)

Exploring the Deformation and Failure Characteristics of Interbedded Anti-inclined Rock Slopes: Insights from Physical Modelling Tests - Bocheng Zhang; Huiming Tang; Siddiqua Sumi; Bingdong Ding; Long Zhang; Yibing Ning (Rock Mechanics and Rock Engineering, 2024)

MiR-26b-3p Promotes Intestinal Motility Disorder by Targeting FZD10 to Inhibit GSK3β/β-Catenin Signaling and Induce Enteric Glial Cell Apoptosis - Yu Zhan; Yong Wen; Fan Zheng; Li-juan Du; Tai-yu Chen; Xu-long Shen; Rong Wu; Xue-gui Tang (Molecular Neurobiology, 2024)

CCL2 Knockdown Attenuates Inflammatory Response After Spinal Cord Injury Through the PI3K/Akt Signaling Pathway: Bioinformatics Analysis and Experimental Validation - Sheng Fang; Hao Tang; Hai-long Li; Ti-Chao Han; Zi-Jie Li; Zong-Sheng Yin; Jian-Jun Chu (Molecular Neurobiology, 2024)

A complete analysis of the link uncertainty budget for pulsed laser time transfer on China space station - Renfang Geng; Zhibo Wu; Yong Huang; Zhien Cheng; Rongzong Yu; Kai Tang; Haifeng Zhang; Wendong Meng; Huarong Deng; Mingliang Long; Si Qin; Zhongping Zhang (Advances in Space Research, 2024)

Spatial–temporal characteristics and driving factors’ contribution and evolution of agricultural non-CO2 greenhouse gas emissions in China: 1995–2021 - Yuan-yue Chu; Xi-ling Zhang; Yang-chen Guo; Li-juan Tang; Chao-yong Zhong; Ji-wen Zhang; Xin-long Li; De-wen Qiao (Environmental Science and Pollution Research, 2024)

Identification and characterization of β3 integrin in Crassostrea hongkongensis - Lei Tang; Shu-Quan Guo; Ting-Long Hou; Yao-Wu Fu; Qi-Zhong Zhang (Aquaculture, 2024)

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Complete genome sequence analysis of Bacillus velezensis A5, a promising biocontrol agent from the Pacific Ocean - Shunhua Ji; Yin Tian; Guangxin Xu; Yiqiang Chen; Jingjing Li; Teng Long; Wei He; Jianqiang Fan; Xixiang Tang (Marine Genomics, 2024)

Enhanced atmospheric water harvesting (AWH) by Co-based MOF with abundant hydrophilic groups and open metal sites - Sihan Li; Peng Wu; Long Chen; Yiwen Tang; Yanhe Zhang; Ling Qin; Xiaofei Qin; Haibo Li (Journal of Water Process Engineering, 2024)

Analysis of forestry management based on dynamic life cycle assessment of biogenic carbon: A case study of a forestry resource-based city in Northeast China - Bo Song; Jin Tang; Feng Long; Yuqing Peng; Fenfen Bi; Yueao Kang; Dayi Qian (Journal of Cleaner Production, 2024)

Decoupling the effects of air temperature change on soil erosion in Northeast China - Yunfei Cao; Li Hua; Danying Peng; Yuhang Liu; Long Jiang; Qi Tang; Chongfa Cai (Journal of Environmental Management, 2024)

Sustainable, efficient, and synergistic photocatalytic degradation toward organic dyes and formaldehyde gas via Cu2O NPs@wood - Lingling Wang; Maojie Tang; Haiqiu Jiang; Jiahui Dai; Ruifeng Cheng; Bei Luo; Long Yang; Guanben Du; Wei Gao (Journal of Environmental Management, 2024)

Experimental and computational insight into the role of cobalt and phosphorus in boosting Volmer and Heyrovsky steps of Ni in alkaline hydrogen evolution reaction - Wei Xu; Xian-Qing Tang; Zhen Zhang; Yi-Ran Wang; Jian-Long Luo; Isack Bulugu; Wen-Jie Yin; Xin Tang; Yu Shen (Fuel, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Field and numerical investigation of soil hydro-thermal response to the climatic conditions in southern China considering soil heterogeneity - Zhao-Jun Zeng; Chao-Sheng Tang; Qing Cheng; Ni An; Zhan-Ming Yang; Xu-Long Gong; Xiao-Ying Chen (Engineering Geology, 2024)

Design of D-A conjugated polymers for simultaneous selective bond breaking/formation and syngas production under visible light illumination - Guoen Tang; Guanhui Liu; Ting Song; Xiayi (Eric) Hu; Bei Long; Guo-Jun Deng (Chemical Engineering Journal, 2024)

Tracking of Stem Cells in Chronic Liver Diseases: Current Trends and Developments - Jin-Long He; Yi-Xian You; Xiong Pei; Wei Jiang; Qing-Min Zeng; Bin Chen; Yong-Hong Wang; En-Qiang Chen; Hong Tang; Xiu-Feng Gao; Dong-Bo Wu (Stem Cell Reviews and Reports, 2024)

Establishment and characterization of DPC-X4: a novel mixed-type ampullary cancer cell line - Changpeng Chai; Huan Tang; Jianfeng Yi; Lu Li; Cheng Yu; Yuanhui Su; Long Miao; Zhenzhen Ye; Zhengfeng Wang; Wei Luo; Jinjing Hu; Hui Zhang; et al. (Human Cell, 2024)

Overexpression of PtoMYB99 diminishes poplar tolerance to osmotic stress by suppressing ABA and JA biosynthesis - Tao Long; Fengming Yang; Zihao Chen; Yuhang Xing; Xia Tang; Banglan Chen; Wenli Cui; Lucas Gutierrez Rodriguez; Lijun Wang; Yongfeng Gao; Yinan Yao (Journal of Plant Physiology, 2024)

With spatial distribution, risk evaluation of heavy metals and microplastics to emphasize the composite mechanism in hyporheic sediments of Beiluo River - Bingjie Li; Jinxi Song; Mingchang Guan; Zeyu Chen; Bin Tang; Yongqing Long; Ruichen Mao; Jiawei Zhao; Wenjin Xu; Yuting Zhang (Journal of Hazardous Materials, 2024)

A novel lightweight CF decision-making approach for highway reconstruction and operation - Zigeng Fang; Feng Jiang; Jiayi Yan; Qiuchen Lu; Long Chen; Junqing Tang; Jingke Hong; Tim Broyd (Journal of Cleaner Production, 2024)

Discovery of color compounds: Integrated multispectral omics on exploring critical colorant compounds of black tea infusion - Piaopiao Long; Yaxin Li; Zisheng Han; Mengting Zhu; Xiaoting Zhai; Zongde Jiang; Mingchun Wen; Chi-Tang Ho; Liang Zhang (Food Chemistry, 2024)

Achieving ultrahigh energy storage density and efficiency above 90% via reducing defect concentrations for AgNbO3-based multilayer capacitors - Dekai Shi; Dong Liu; Lei Zhao; Qi Wang; Ting Tang; Xinyue Long; Liqin Yan; Bo-Ping Zhang; He Qi; Li-Feng Zhu (Chemical Engineering Journal, 2024)

Exploring strength deterioration mechanism of soil-rock mixture based on pore structure characteristics under freeze–thaw cycles - Liyun Tang; Zihan Lu; Tao Zhao; Zhuo Li; Peiyong Qiu; Yongtang Yu; Long Jin; Yongqiang Li; Hailiang Jia (Cold Regions Science and Technology, 2024)

Experimental investigations on the shear strength and creep properties of soil-rock mixture under freeze-thaw cycles - Peiyong Qiu; Liyun Tang; Jianguo Zheng; Weibing Wang; Yongqiang Li; Guoyu Li; Long Jin; Yongtang Yu; Xu Duan (Cold Regions Science and Technology, 2024)

Development of a highly sensitive aptamer-based electrochemical sensor for detecting saxitoxin based on K3Fe(CN)6 regulated silver nanoparticles - Wei Zeng; Xuemei Tang; Ting Wu; Bingjun Han; Long Wu (Analytica Chimica Acta, 2024)

Thermoelectrics and thermocells for fire warning applications - Zhaofu Ding; Chunyu Du; Wujian Long; Cheng-Fei Cao; Lirong Liang; Long-Cheng Tang; Guangming Chen (Science Bulletin, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Does environmental regulation improve firms' export product quality? Empirical evidence based on China's key regional air pollution and control policy - Yan Jiang; Long Tang; Cui Huang (Journal of Cleaner Production, 2023)

Experimental study of coal rank effect on carbon dioxide injection to enhance CBM recovery - Jun Tang; Yonghan Long; Lei Zhang; Shipan Zeng; Shixiang Tian; Cun Zhang (Fuel, 2023)

Enhancing stability of 1,3-dioleic acid-2-palmitate (OPO) through microencapsulation: A comparative study of single- and double-layer microcapsules - Qinyue Tang; Zhe Li; Xiaoli Xu; Panpan Wang; Bao Chen; Yaqin Yang; Guofeng Jin; Long Sheng (Food Hydrocolloids, 2023)

Development of injectable hyaluronic acid-based hydrogels with antioxidant activity for the treatment of corneal neovascularization - Linyu Long; Zhengwei Ge; Fanjun Zhang; Ruiqi Dong; Li Yang; Zhongping Chen; Shibo Tang; Yunbing Wang (Chemical Engineering Journal, 2023)

Compositionally complex doping for low-V Ti-Cr-V hydrogen storage alloys - Yongyang Zhu; Xubo Li; Xu-Sheng Yang; Pengyun Chen; Gary Chi-Pong Tsui; Zheng-Long Xu; Renheng Tang; Fangming Xiao; Kangcheung Chan (Chemical Engineering Journal, 2023)

Integration of genome-wide association studies reveal loci associated with salt tolerance score of rice at the seedling stage - Nhung Thi Hong Phan; Cuong Van Pham; Hanh Thi Tang; Loc Van Nguyen; Long Viet Nguyen; Pierre Bertin (Journal of Applied Genetics, 2023)

Expressions of electron escape probability and photo-emission from metals - Yi-Fan Liu; Ai-Gen Xie; Jing Tang; Hong-Jie Dong; Yun-Long Xie (Annals of Nuclear Energy, 2023)

Experimental study on the flow characteristics of 7-pin hexagonal bundle assembly with grid spacers - Rongjie Li; Dajun Fan; Minghan He; Yang Liu; Qianwan Shi; Yanze Tang; Wangsheng Tian; Deliang Fan; Long Gu (Annals of Nuclear Energy, 2023)

Fluviispira vulneris sp. nov., isolated from human wound secretions - Peijuan Tang; Na Peng; Pengwen Ouyang; Sheng Long; Zhenhua Wei; Xingchun Chen; Pinghua Qu; Liangyi Xie (Antonie van Leeuwenhoek, 2023)
Human infections by environmental bacteria is becoming an increasing problem and has become a matter of great concern due to the adverse effects worldwide. In this study, we reported a new environmental pathogen. Isolate GX5518 T was a novel Gram-negative, aerobic, non-motile, pleomorphic and red-pigmented bacterium, was isolated from human wound secretions (GuangXi, People’s Republic of China). Growth occurred at pH 6.0–8.0 (optimum, pH 7.0) and 10–37 °C (optimum, 28–32 °C) with 0–1.5% (w/v) NaCl in R2A agar. Comparative analysis of the 16S rRNA gene sequences revealed that isolate GX5518 T was closely related to Fluviispira sanaruensis JCM 31447 T (99.73%) and Fluviispira multicolorata 33A1-SZDP T (98.49%). However, the estimated ANI values of the isolate GX5518 T compared to the F. sanaruensis JCM 31447 T and F. multicolorata 33A1-SZDP T were 88.67% and 77.35%, respectively. The estimated dDDH, ANI and AAI values between isolate GX5518 T and its closely related strains were below the threshold values generally considered for recognizing a new species. The genome size was 3.6 Mbp and the DNA G + C content was 33.1%. The predominant fatty acids (> 5%) in GX5518 T cells were iso-C 15:0 , C 16:0 , C 17:0 , C 17:1 ω 8 c and C 16:1 ω 7 c /C 16:1 ω 6 c . The major menaquinone was MK-8 (86.9%). The polar lipids were phosphatidylethanolamine (PE), phosphatidylglycerol (PG) and three unknown lipids (L1-3). The chemical composition was different from that of the F. sanaruensis JCM 31447 T . Comparative genomics analysis between isolate GX5518 T and its related strains revealed that there were a number of genes involved in resistance to antibiotics and toxic compounds in isolate GX5518 T , which were responsible for the copper homeostasis, cobalt-zinc-cadmium resistance, resistance to fluoroquinolones, and zinc resistance. Based on the phenotypic, chemotaxonomic, and genomic analyses, isolate GX5518 T (= CGMCC 1.18685 T = KCTC 82149 T ) represents a novel species of the genus Fluviispira , for which the name Fluviispira vulneris sp. nov. is proposed.

New benzofuran neolignans with neuroprotective activity from Phyllanthodendron breynioides - Tong Su; Mei-Cen Pu; Di-Kai Tang; Jin-Chen Long; Fang-Yu Yuan; Ai-Ping Yin; Shu-Qi Wu; Sheng Yin; Gui-Hua Tang (Natural Product Research, 2023)

Monoterpenoids from the root bark of Acanthopanax gracilistylus and their inhibitory effects on neutrophil elastase, 5-lipoxygenase, andcyclooxygenase-2 in vitro - Hao-Dong Yang; Zhi-Shu Tang; Tao-Tao Xue; Huai-Li Xu; Bao-Long Hou; Ya-Ya Zhu; Zeng-Hu Su; Hong-Bo Xu (Phytochemistry, 2023)

Evaluating main drivers of terrestrial water storage depletion in the agro-pastoral ecotone of northern China - Yang Xu; Dawen Yang; Lihua Tang; Zixu Qiao; Long Ma; Min Chen (Journal of Hydrology, 2023)

Proteomic characterization of extracellular vesicles derived from lactic acid bacteria - Bao-Hong Lee; You-Zuo Chen; Tang-Long Shen; Tzu-Ming Pan; Wei-Hsuan Hsu (Food Chemistry, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Research progress on the adsorption of sulfocompounds in flue gas - Siming Guo; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang; Ya Wang; Yiming Ma; Yuhan Long; Honghong Yi (Chemical Engineering Journal, 2023)

Utilizing internal resonant scattering to improve photoluminescence energy outcoupling of CsPbBr3/Cs4PbBr6 perovskite phosphor - Zong-Tao Li; Bo-Jia Li; Jia-Sheng Li; Cun-Jiang Song; Xin-Rui Ding; Hai-Long Yuan; Bin-Hai Yu; Yong Tang; Jian-Zhen Ou; Romain Gautier; Hong-Lei Ji; Hao-Chung Kuo (Chemical Engineering Journal, 2023)

Assessing the suitability of three purple soils for aquaculture by physiological responses in freshwater bivalves (Hyriopsis cumingii) - Qinglin Yang; Jing Mei; Xiaoqi Tang; Tao Wang; Kai Long; Yang Liu; Yanhong Li; Xiaobo Yu; Weizhi Yao; Zhengli Wu (Aquaculture, 2023)

Enhancing the removal of organic micropollutants by nanofiltration membrane with Fe (III)–tannic acid interlayer: Mechanisms and environmental implications - Wenyu Liu; Li Long; Zhe Yang; Li Wang; Qimao Gan; Shenghua Zhou; Pulak Sarkar; Hao Guo; Chuyang Y. Tang (Water Research, 2023)

Retrieval of nighttime aerosol optical depth by simultaneous consideration of artificial and natural light sources - Yizhen Meng; Ji Zhou; Ziwei Wang; Wenbin Tang; Jin Ma; Tao Zhang; Zhiyong Long (Science of The Total Environment, 2023)

Analysis and simulation of the driving mechanism and ecological effects of land cover change in the Weihe River basin, China - Wenjin Xu; Jinxi Song; Yongqing Long; Ruichen Mao; Bin Tang; Bingjie Li (Journal of Environmental Management, 2023)

Donor-acceptor 2D polymer for simultaneous photocatalytic CO2 reduction and carbonylation reaction - Guoen Tang; Xiaoyan Huang; Ting Song; Nailiang Wang; Bei Long; Atif Ali; Guo-Jun Deng (Chemical Engineering Journal, 2023)

LncRNA XIST Exacerbates Oxygen-Glucose Deprivation/Reoxygenation-Induced Cerebral Injury Through the miR-25-3p/TRAF3 Axis - You Li; Ji-Kun Zhang; Zheng-Tao Yu; Jun-Wen Jiang; Hong Tang; Guo-Long Tu; Ying Xia (Molecular Neurobiology, 2023)

Highly stable natural zeolite/montmorillonite hybrid microspheres with green preparation process for efficient adsorption of ammonia nitrogen in wastewater - Qihang Zhao; Chenhui Long; Zhiyi Jiang; Weiwei Yin; Aidong Tang; Huaming Yang (Applied Clay Science, 2023)

Preparation and application of a novel imine-linked covalent organic framework@silica composite for reversed-phase and hydrophilic interaction chromatographic separations - Wanjiao Wei; Haoyu Long; Yanjuan Liu; Yuefei Zhang; Wei Chen; Sheng Tang (Analytica Chimica Acta, 2023)

Improving children's outdoor thermal comfort: A field study in China's severely cold regions - Xiaoyun He; Long Shao; Yuexing Tang; Shenglong Wu (Urban Climate, 2023)

Time-dependent hormetic effects of polypeptide antibiotics and two antibacterial agents contribute to time-dependent cross-phenomena of their binary mixtures - Haoyu Sun; Yulian Zhang; Jing Wang; Long-Fei Ren; Danqing Tong; Jiajun Wang; Liang Tang (Science of The Total Environment, 2023)

Expression of three neuropeptide genes (SfEH, SfETH, and SfCCAP) in response to insecticide stress on the white-backed planthopper Sogatella furcifera (Hemiptera: Delphacidae) - Gui-yun Long; Zhao Wang; Jia-peng Yang; Chen-hong Tang; Dao-chao Jin; Hong Yang; Cao Zhou; Xi-bin Yang (Journal of Asia-Pacific Entomology, 2023)

Full life circle of micro-nano bubbles: Generation, characterization and applications - Jianguang Jia; Zhaoxu Zhu; Hao Chen; Hongyu Pan; Long Jiang; Wen-Hao Su; Qiang Chen; Yingwen Tang; Jianming Pan; Kai Yu (Chemical Engineering Journal, 2023)

Multimodal data-driven prognostic model for predicting new-onset ST-elevation myocardial infarction following emergency percutaneous coronary intervention - Long Tang; Min Wu; Yanan Xu; Tongjian Zhu; Cunming Fang; Kezhong Ma; Jun Wang (Inflammation Research, 2023)

Calcium homeostasis dysregulation and muscle atrophy: multidimensional regulation from excitatory contractile coupling to sarcoplasmic reticulum stress - Yuli Huang; Long Chen; Lifeng Tang; Yanlin Wu; Wenjuan Wu; Yanbiao Zhong; Yun Luo; Maoyuan Wang (Neurophysiology, 2023)

Description and genomic characterization of Gallaecimonas kandeliae sp. nov., isolated from the sediments of mangrove plant Kandelia obovate - Meng Long; Shaoshuai Tang; Huimin Fan; Zhen Gan; Hongli Xia; Yishan Lu (Antonie van Leeuwenhoek, 2023)

MRI-based brain age prediction model for children under 3 years old using deep residual network - Lianting Hu; Qirong Wan; Li Huang; Jiajie Tang; Shuai Huang; Xuanhui Chen; Xiaohe Bai; Lingcong Kong; Jingyi Deng; Huiying Liang; Guangjian Liu; Hongsheng Liu; et al. (Brain Structure and Function, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Effect of Bacillus cereus mutant strain S458-M on active phosphorus and crucian carp in culture systems - Xicheng Zhou; Qinglin Yang; Kai Long; Xiaoqi Tang; Lijun Luo; Zhengli Wu; Yanhong Li (Aquaculture, 2023)

NaHCO3 addition enhances water permeance and Ca/haloacetic acids selectivity of nanofiltration membranes for drinking water treatment - Li Long; Lu Elfa Peng; Shenghua Zhou; Qimao Gan; Xianhui Li; Jingyi Jiang; Jiarui Han; Xiangru Zhang; Hao Guo; Chuyang Y. Tang (Water Research, 2023)

A quantitative study of nanoplastics within cells using magnetic resonance imaging - Long Zhang; Haonan Liu; Qi Xin; Lijuan Tang; Jie Tang; Yin Liu; Le Hu (Science of The Total Environment, 2023)

Climate feedbacks associated with land-use and land-cover change on hydrological extremes over the Yangtze River Delta Region, China - Qiang Wang; Xitian Cai; Jinyun Tang; Long Yang; Jie Wang; Youpeng Xu (Journal of Hydrology, 2023)

Boosting photocatalysis of hydrazone-linked covalent organic frameworks through introducing electron-rich conjugated aldehyde - Qingqing Tang; Ying-Ying Gu; Jing Ning; Yingkui Yan; Li Shi; Mengshi Zhou; Hongtao Wei; Xiaohui Ren; Xuehui Li; Junxia Wang; Chao Tang; Long Hao; et al. (Chemical Engineering Journal, 2023)

Well Interference Model of Multi-fractured Horizontal Wells Considering Non-uniform Fracture Conductivity in Fractured Porous Media - Jiazheng Qin; Jichang Long; Yong Tang; Zhiyue He (Transport in Porous Media, 2023)

Rockfall feature investigation and kinematic simulation based on nap-of-the-object photogrammetry and GIS spatial modeling - Xude Li; Fu-zhen Liu; Li Zhao; Na Deng; Long Chen; Jing-shen Pan; Guo-qiang Tang (Natural Hazards, 2023)

Recyling manganese-rich electrolytic residues: a review - Fan Wang; Guangcheng Long; Kunlin Ma; Xiaohui Zeng; Zhuo Tang; Rongzhen Dong; Jionghuang He; Minghui Shangguan; Qingchun Hu; Rock Keey Liew; Yang Li; John Zhou (Environmental Chemistry Letters, 2023)

The threshold analysis of economic growth, FDI and trade on environment pollution in China using provincial panel data - Caihong Tang; Anitha Rosland; Rizwana Yasmeen; Yunfei Long (Environment, Development and Sustainability, 2023)

An electronic sense-based machine learning model to predict formulas and processes for vegetable-fruit beverages - Hai-Bin Ren; Bao-Long Feng; Hong-Yue Wang; Jing-Jian Zhang; Xiao-Sen Bai; Fei Gao; Yan Yang; Qi Zhang; Ye-Hui Wang; Li-Li Wang; Ya-Ting Rong; Yu-Lin Sun; et al. (Computers and Electronics in Agriculture, 2023)

A review on current progress of Raman-based techniques in food safety: From normal Raman spectroscopy to SESORS - Long Wu; Xuemei Tang; Ting Wu; Wei Zeng; Xiangwei Zhu; Bing Hu; Sihang Zhang (Food Research International, 2023)

Comparative study of ionospheric sporadic E occurrence rates using SNRnstd and S4 derived from GPS radio occultation - Long Tang; Jiaxing Li; Fenkai Zhang; Fang Zou (GPS Solutions, 2023)

Source apportionment of nitrate in the Pearl River Estuary using δ15N and δ18O values and isotope mixing model - Ran Long; Fei Tian; Jian-hua Chen; Yan-bo Zhou; Xue-fei Li; Yi-tong Li; Hai-wei Tang; Hai-gang Chen (Marine Pollution Bulletin, 2023)

Grazing reduces plant sexual reproduction but increases asexual reproduction: A global meta-analysis - Mi Wentao; Tang Shiming; Qi Le; Ren Weibo; Ellen L. Fry; Jonathan R. De Long; Reuben C.P. Margerison; Chi Yuan; Liu Xiaomin (Science of The Total Environment, 2023)

Potential of remote sensing surface temperature- and evapotranspiration-based land-atmosphere coupling metrics for land surface model calibration - Jianhong Zhou; Kun Yang; Wade T. Crow; Jianzhi Dong; Long Zhao; Huihui Feng; Mijun Zou; Hui Lu; Ronglin Tang; Yaozhi Jiang (Remote Sensing of Environment, 2023)

Experimental and numerical investigations on the explosions nearby a free surface from both sides - Hao Tang; Zhao-Li Tian; Xin-Yang Ju; Ji-Tuan Feng; Yun-Long Liu; A-Man Zhang (Ocean Engineering, 2023)

Ultra-superhydrophobic MOFs coated on polydopamine-modified polyethylene terephthalate for efficient removal of particulate matter - Wei Dong; Qingda Gao; Shian Zhou; Gang Tang; Tengfei Xiang; Tiejun Chun; Kui Zhang; Hong-ming Long; Fuping Qian; Gang Li (Chemical Engineering Journal, 2023)

Metformin Alleviates Delayed Hydrocephalus after Intraventricular Hemorrhage by Inhibiting Inflammation and Fibrosis - Yi Cao; Chang Liu; Gaowei Li; Weina Gao; Hui Tang; Shuanmin Fan; Xin Tang; Long Zhao; Haoxiang Wang; Aijun Peng; Chao You; Aiping Tong; et al. (Translational Stroke Research, 2023)

Design, synthesis, and anti-aging effect evaluation of urolithin B and its amide derivatives on nematode Caenorhabditis elegans - Xi Chen; Xiaoqing Feng; Xiangming Kong; Hecheng Wang; Tianwen Liu; Long Tang; Ziheng Zhuang (Medicinal Chemistry Research, 2023)

RETRACTED ARTICLE: Comparison of preoperative ultrasound and MRI in the diagnosis of microvascular invasion in hepatocellular carcinoma - Yunmin Long; Zheng Lv; Shaoyi Wang; Bing Tang; Qin Li; Wei Zhang (Functional & Integrative Genomics, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

A LSSVR Interactive Network for AUV Motion Control - Chunmeng Jiang; Lei Wan; Hongrui Zhang; Jian Tang; Jianguo Wang; Shupeng Li; Long Chen; Gongxing Wu; Bin He (Journal of Marine Science and Engineering, 2023)
In view of the requirements on control precision of autonomous underwater vehicles (AUVs) in different operations, the improvement of AUV motion control accuracy is the focus of this paper. In regard to the unsatisfying robustness of traditional control methods, an interactive network based on Least Square Support Vector Regression (LSSVR) is therefore put forward. The network completed the identification of the strong nonlinear AUV dynamic characteristics based on the LSSVR theory and by virtue of the interactions between the offline and online modules, it achieved offline design and online optimization of the AUV control law. In addition to contrastive numerical simulations and sea trials with the classic S-plane method in AUV velocity and heading control, the LSSVR network was also tested in path following and long-range cruise. The precision and robustness and of the proposed network were verified by the high-accuracy control results of the aforesaid simulations and trials. The network can be of practical use in AUV control especially under unfamiliar water conditions with access to a limited number of control samples or little information of the operation site.

Molecular Characterization of U6 Promoters from Orange-Spotted Grouper (Epinephelus coioides) and Its Application in DNA Vector-Based RNAi Technology - Fengying Yan; Xinxun Xiao; Chen Long; Lin Tang; Chongwei Wang; Mingqing Zhang; Jin Zhang; Haoran Lin; Hai Huang; Yong Zhang; Shuisheng Li (Marine Biotechnology, 2023)

Characteristics of inverse dispersion curve of Rayleigh wave in pavement shallow structure with engineering application - Bo Yang; Chao Shen; Yuewen Tang; Meng Zhang; Youming Long (Journal of Applied Geophysics, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

Coupling effect of fiber reinforcement and MICP stabilization on the tensile behavior of calcareous sand - Dian-Long Wang; Chao-Sheng Tang; Xiao-Hua Pan; Bo Liu; Bin Shi (Engineering Geology, 2023)

CD71/CD44 dual-aptamer-gemcitabine conjugate for tumor co-targeting treatment of bladder cancer - Biao Liu; Jinrong Wang; Yongbo Peng; Hongliang Zeng; Qun Zhang; Minhua Deng; Wei Xiang; Jiahao Liu; Xing Hu; Xuewen Liu; Jianfei Xie; Weibin Hou; et al. (Chemical Engineering Journal, 2023)

Rational design of molecular phototheranostic platform for NIR-II fluorescence imaging guided chemodynamic-photothermal combined therapy - Gui-long Wu; Bin Sun; Yuxuan He; Xiaofeng Tan; Qi Pan; Sha Yang; Na Li; Minghui Wang; Peixian Wu; Fen Liu; Hao Xiao; Li Tang; et al. (Chemical Engineering Journal, 2023)

Comparative review on microbial electrochemical technologies for resource recovery from wastewater towards circular economy and carbon neutrality - Shihai Deng; Chaoqi Wang; Huu Hao Ngo; Wenshan Guo; Na You; Hao Tang; Hongbin Yu; Long Tang; Jie Han (Bioresource Technology, 2023)

Comparative genomic analysis provides insights into taxonomy and temperature adaption of Aeromonas salmonicida - Meng Long; Huimin Fan; Zhen Gan; Zenghai Jiang; Shaoshuai Tang; Hongli Xia; Yishan Lu (Journal of Fish Diseases, 2023)
Aeromonas salmonicida has long been known as psychrophiles since it is mainly isolated from cold water fish, and recent reports have revealed the existence of mesophilic strains isolated from warm sources. However, the genetic differences between mesophilic and psychrophilic strains remain unclear due to few complete genomes of mesophilic strain are available. In this study, six A. salmonicida (2 mesophilic and 4 psychrophilic) were genome‐sequenced, and comparative analyses of 25 A. salmonicida complete genomes were conducted. The ANI values and phylogenetic analysis revealed that 25 strains formed three independent clades, which were referred as typical psychrophilic, atypical psychrophilic and mesophilic groups. Comparative genomic analysis showed that two chromosomal gene clusters, related to lateral flagella and outer membrane proteins (A‐layer and T2SS proteins), and insertion sequences (ISAs4, ISAs7 and ISAs29) were unique to the psychrophilic groups, while the complete MSH type IV pili were unique to the mesophilic group, all of which may be considered as lifestyle‐related factors. The results of this study not only provide new insights into the classification, lifestyle adaption and pathogenic mechanism of different strains of A. salmonicida , but also contributes to the prevention and control of disease caused by psychrophilic and mesophilic A. salmonicida.

Diversity of sesquiterpenoids from Stellera chamaejasme with neuroprotective effects - Fang-Yu Yuan; Zhuo-Ya Tang; Xue-Long Yan; Dong Huang; Han-Zhuang Weng; Jia-Luo Huang; Run-Zhu Fan; Ye Chen; Sheng Yin; Gui-Hua Tang (Phytochemistry, 2023)

Translatomics and physiological analyses of the detoxification mechanism of green alga Chlamydomonas reinhardtii to cadmium toxicity - Baolong Zhang; Yuxin Tang; Fei Yu; Zhao Peng; Sheng Yao; Xuan Deng; Huan Long; Xun Wang; Kaiyao Huang (Journal of Hazardous Materials, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Association between maternal exposure to per- and polyfluoroalkyl substances and serum markers of liver function during pregnancy in China: A mixture-based approach - Qian Liao; Peng Tang; Haoran Fan; Yanye Song; Jun Liang; Huishen Huang; Dongxiang Pan; Meile Mo; LeiLei; Mengrui Lin; Jiehua Chen; Huanni Wei; et al. (Environmental Pollution, 2023)

Effect of composted pig manure, biochar, and their combination on antibiotic resistome dissipation in swine wastewater-treated soil - Likun Sun; Defu Tang; Xisheng Tai; Jiali Wang; Min Long; Tingting Xian; Haofan Jia; Renfei Wu; Yongqi Ma; Yunpeng Jiang (Environmental Pollution, 2023)

Production of MSTN knockout porcine cells using adenine base-editing-mediated exon skipping - Shuai-peng Yang; Xiang-xing Zhu; Zi-xiao Qu; Cai-yue Chen; Yao-bing Wu; Yue Wu; Zi-dan Luo; Xin-yi Wang; Chu-yu He; Jia-wen Fang; Ling-qi Wang; Guang-long Hong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2023)

Thearubigins: Formation, structure, health benefit and sensory property - Piaopiao Long; Kanyasiri Rakariyatham; Chi-Tang Ho; Liang Zhang (Trends in Food Science & Technology, 2023)

Benefits of mechanical weeding for weed control, rice growth characteristics and yield in paddy fields - Chuang Liu; Kaiqiang Yang; Yong Chen; Hao Gong; Xiao Feng; Zhenyu Tang; Dengbin Fu; Long Qi (Field Crops Research, 2023)

Denitrification efficiency, microbial communities and metabolic mechanisms of corn cob hydrolysate as denitrifying carbon source - Yingping Long; Yongwen Ma; Jinquan Wan; Yan Wang; Min Tang; Hao Fu; Jianye Cao (Environmental Research, 2023)

An internally damped inertial platform for marine gravimetry and a test case in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

A marine gravimeter based on electromagnetic damping and its tests in the South China Sea - Pengfei Wu; Lin Wu; Lifeng Bao; Long Wang; Bo Wang; Danling Tang (Journal of Oceanology and Limnology, 2023)

The involvement of an HMG-box gene in germ cell genesis in Pyropia haitanensis - Hong-Chang Ding; Long-Chen Tang; Da-Hai Gao; Xing-Hong Yan (Algal Research, 2023)

Comparison of bacterial community structure in PM2.5 during hazy and non-hazy periods in Guilin, South China - Tengfa Long; Ziwei Ye; Yanchun Tang; Jiaxin Shi; Jianhui Wen; Chunqiang Chen; Qiang Huo (Aerobiologia, 2023)

Genomic evidence reveals intraspecific divergence of the hot‐spring snake ( Thermophis baileyi ), an endangered reptile endemic to the Qinghai‐Tibet plateau - Chaochao Yan; Meng‐Huan Song; Dechun Jiang; Jin‐Long Ren; Yunyun Lv; Jiang Chang; Song Huang; Hussam Zaher; Jia‐Tang Li (Molecular Ecology, 2023)
Understanding how and why species evolve requires knowledge on intraspecific divergence. In this study, we examined intraspecific divergence in the endangered hot‐spring snake ( Thermophis baileyi ), an endemic species on the Qinghai‐Tibet Plateau (QTP). Whole‐genome resequencing of 58 sampled individuals from 15 populations was performed to identify the drivers of intraspecific divergence and explore the potential roles of genes under selection. Our analyses resolved three groups, with major intergroup admixture occurring in regions of group contact. Divergence probably occurred during the Pleistocene as a result of glacial climatic oscillations, Yadong‐Gulu rift, and geothermal fields differentiation, while complex gene flow between group pairs reflected a unique intraspecific divergence pattern on the QTP. Intergroup fixed loci involved selected genes functionally related to divergence and local adaptation, especially adaptation to hot spring microenvironments in different geothermal fields. Analysis of structural variants, genetic diversity, inbreeding, and genetic load indicated that the hot‐spring snake population has declined to a low level with decreased diversity, which is important for the conservation management of this endangered species. Our study demonstrated that the integration of demographic history, gene flow, genomic divergence genes, and other information is necessary to distinguish the evolutionary processes involved in speciation.

Adverse impacts of high-density microplastics on juvenile growth and behaviour of the endangered tri-spine horseshoe crab Tachypleus tridentatus - James Kar-Hei Fang; Tsz Wan Tse; Elizaldy Acebu Maboloc; Ryan Kar-Long Leung; Matthew Ming-Lok Leung; Max Wang-Tang Wong; Apple Pui-Yi Chui; Youji Wang; Menghong Hu; Kit Yue Kwan; Siu Gin Cheung (Marine Pollution Bulletin, 2023)

Ionic resource recovery for carbon neutral papermaking wastewater reclamation by a chemical self-sufficiency zero liquid discharge system - Yangbo Qiu; Sifan Wu; Lei Xia; Long-Fei Ren; Jiahui Shao; Jiangnan Shen; Zhe Yang; Chuyang Y. Tang; Chao Wu; Bart Van der Bruggen; Yan Zhao (Water Research, 2023)

Modelling of paddy soil using the CFD-DEM coupling method - Zhenyu Tang; Hao Gong; Shuanglong Wu; Zhiwei Zeng; Zhiqi Wang; Yuhao Zhou; Dengbin Fu; Chuang Liu; Yinghu Cai; Long Qi (Soil and Tillage Research, 2023)

A 40 % paddy surface soil organic carbon increase after 5-year no-tillage is linked with shifts in soil bacterial composition and functions - Jian-Ying Qi; Xiang-Bin Yao; Jian Lu; Long-Xin He; Jun-Li Cao; Zheng-Rong Kan; Xing Wang; Sheng-Gang Pan; Xiang-Ru Tang (Science of The Total Environment, 2023)

Transcriptomic data recover a new superfamily-level phylogeny of Cucujiformia (Coleoptera, Polyphaga) - Ming-Long Yuan; Wen-Ting Chen; Qi-Lin Zhang; Min Li; Li Zhang; Pei-An Tang (Molecular Phylogenetics and Evolution, 2023)

Hydrolysate from the enzymatic treatment of corn cob as a carbon source for heterotrophic denitrification process - Yingping Long; Yongwen Ma; Jinquan Wan; Yan Wang; Min Tang; Qi Zheng; Yang Ma (Journal of Water Process Engineering, 2023)

Water deficit aggravated the inhibition of photosynthetic performance of maize under mercury stress but is alleviated by brassinosteroids - Yulou Tang; Junjie Zhang; Lijuan Wang; Hao Wang; Haochi Long; Liuyang Yang; Gengwei Li; Jiameng Guo; Yongchao Wang; Yuling Li; Qinghua Yang; Weiyu Shi; et al. (Journal of Hazardous Materials, 2023)

Secular trend in water discharge transport in the Lower Mekong River-delta: Effects of multiple anthropogenic stressors, rainfall, and tropical cyclones - Runan Tang; Zhijun Dai; Xuefei Mei; Xiaoyan Zhou; Chuqi Long; Cong Mai Van (Estuarine, Coastal and Shelf Science, 2023)

Age, formation mechanisms, spatial extent, and geodynamic effects of the eastern and northeastern Asian big mantle wedges - Jie Tang; Feng Wang; Yi-Ni Wang; Xin-Yu Long; Wen-Liang Xu (Earth-Science Reviews, 2023)

Portal vein tumor thrombosis in hepatocellular carcinoma: molecular mechanism and therapy - Xing-Hao Zhou; Jing-Ru Li; Tang-Hui Zheng; Hong Chen; Chen Cai; Sheng-Long Ye; Bo Gao; Tong-Chun Xue (Clinical & Experimental Metastasis, 2023)

The Effect of Food Deprivation on Foraging Behavior and Digestive and Metabolic Capacities of the Chinese Mitten Crab, Eriocheir sinensis - Qiaolin Long; Jian Liu; Yunfei Sun; Zhigang Yang; Boping Tang; Yongxu Cheng (Fishes, 2023)
Food deprivation is a common stress in crustaceans that can affect their behavior and physiology. In this study, a video recording analysis system was used to compare the predation rate and behavior of the Chinese mitten crab, Eriocheir sinensis, foraging on the freshwater snail, Bellamya quadrata, under different degrees of food deprivation. The activities of lactate dehydrogenase, α-amylase, pepsin, and lipase in the hepatopancreas of crabs were determined after food deprivation for 0, 3, 9, and 15 days. The results showed that the predation and encounter rates of E. sinensis increased and then decreased with an increase in food deprivation time. The proportion of stationary time of E. sinensis initially decreased and then increased, whereas the proportion of searching and handling time increased initially and then decreased. There was a significant difference in the probability of capture upon encountering; however, food deprivation did not significantly affect the probability of consumption upon capture. Under food deprivation, the proportion of E. sinensis crushing tactics after nine-day food deprivation was significantly lower than that in the first nine days. Lactate dehydrogenase activity in the E. sinensis hepatopancreas after food deprivation was significantly higher than that in those not subjected to food deprivation, and the activities of α-amylase and pepsin in the hepatopancreas were consistent with the predation rate trend, showing an initial increase followed by a decrease. In conclusion, different degrees of food deprivation significantly affected the predation cycle of E. sinensis on B. quadrata. These results lay a solid foundation for further studies on the foraging behavioral ecology of E. sinensis and provide important information for improving E. sinensis production.

A detection approach for late-autumn shoots of litchi based on unmanned aerial vehicle (UAV) remote sensing - Juntao Liang; Xin Chen; Changjiang Liang; Teng Long; Xinyu Tang; Zhenmiao Shi; Ming Zhou; Jing Zhao; Yubin Lan; Yongbing Long (Computers and Electronics in Agriculture, 2023)

Efficient Cu/CeO2 composites for hydrogen production from photothermal methanol steam reforming: The utility of synergism of photo and thermal catalysis - Long Zhao; Mengran Tang; Fagen Wang; Xinping Qiu (Fuel, 2023)

Nonoxidative propane dehydrogenation by isolated Co2+ in BEA zeolite: Dealumination-determined key steps of propane C H activation and propylene desorption - Sheng Wei; Hua Dai; Jiangping Long; Hongqiao Lin; Junkun Gu; Xupeng Zong; Dan Yang; Yu Tang; Yanhui Yang; Yihu Dai (Chemical Engineering Journal, 2023)

Robust MXene adding enables the stable interface of silicon anodes for high-performance Li-ion batteries - Jie Tang; Fuzhong Wu; Xinyi Dai; Jiawang Zhou; Huixia Pang; Xingyu Duan; Bo Xiao; Dongjia Li; Junliang Long (Chemical Engineering Journal, 2023)

Donor-acceptor organic polymer with sulfur bridge for superior photocatalytic CO2 reduction to CH4 under visible light illumination - Guoen Tang; Jingrong Li; Yanling Lu; Ting Song; Shiheng Yin; Guojiang Mao; Bei Long; Atif Ali; Guo-Jun Deng (Chemical Engineering Journal, 2023)

microRNAs shape social immunity: a potential target for biological control of the termite Reticulitermes chinensis - Long Liu; Feng-Ming Yan; Chen-Chen Zhao; Li-Juan Su; Qiu-Ying Huang; Qing-Bo Tang (Journal of Pest Science, 2023)
Eusocial insects can employ various behavioural and physiological disease defences to avoid, resist and tolerate pathogen infections in their closely related and packed colonies, termed social immunity. Recent studies have shown that several molecules serve insect social immunity, including chemical odours, insect venoms, immune-related proteins, etc. However, whether and how microRNAs (miRNAs), whose precursors are processed by Dicer-1 , drive social immunity in insect colonies is still unknown. Here, we used a ‘host–pathogen’ system (host: Reticulitermes chinensis ; pathogen: Metarhizium anisopliae ) to explore the impact of miRNAs on social immunity in termite colonies. We found that RNAi-mediated silencing of Dicer-1 led to decreased miRNA concentration, significantly inhibited carbohydrate and energy metabolism and affected other life processes, such as the immune response and oxidation–reduction reactions, in whole body of the termite. In behavioural defence, silencing Dicer-1 significantly diminished defensive social behaviours such as locomotion, grooming, cannibalism and burial in termite groups when encountering fungal contamination. In physiological defence, Dicer-1 silencing and miR-71-5 stimulation resulted in significantly decreased antifungal activities of termites. Furthermore, both Dicer-1 -silenced and miR-71-5 stimulant-treated termite groups exhibited a high level of mortality during fungal contamination. Our findings demonstrated the important role of miRNAs in shaping social immunity in termite colonies, providing insights necessary to understand the potential mechanisms underlying behavioural and physiological disease defences in insects and hence laying the groundwork for miRNA-based pest control.

Ionospheric disturbances of the January 15, 2022, Tonga volcanic eruption observed using the GNSS network in New Zealand - Long Tang (GPS Solutions, 2023)

Long-term partial substitution of chemical fertilizer by organic amendments influences soil microbial functional diversity of phosphorus cycling and improves phosphorus availability in greenhouse vegetable production - Yinjie Zhang; Wei Gao; Long Ma; Haoan Luan; Jiwei Tang; Ruonan Li; Mingyue Li; Shaowen Huang; Lei Wang (Agriculture, Ecosystems & Environment, 2023)

Associations of bisphenol exposure with thyroid hormones in pregnant women: a prospective birth cohort study in China - Huishen Huang; Jun Liang; Peng Tang; Chuanxiang Yu; Haoran Fan; Qian Liao; Jinghua Long; Dongxiang Pan; Xiaoyun Zeng; Shun Liu; Dongping Huang; Xiaoqiang Qiu (Environmental Science and Pollution Research, 2022)

Gender-specific effects of prenatal mixed exposure to serum phthalates on neurodevelopment of children aged 2–3 years:the Guangxi Birth Cohort Study - Yuan Zheng; Longman Li; Hong Cheng; Shengzhu Huang; Xiuming Feng; Lulu Huang; Luyun Wei; Dehao Cao; Sida Wang; Long Tian; Weijun Tang; Caitong He; et al. (Environmental Science and Pollution Research, 2022)

Comprehensive multi-omics analysis of the m7G in pan-cancer from the perspective of predictive, preventive, and personalized medicine - Xiaoliang Huang; Zuyuan Chen; Xiaoyun Xiang; Yanling Liu; Xingqing Long; Kezhen Li; Mingjian Qin; Chenyan Long; Xianwei Mo; Weizhong Tang; Jungang Liu (EPMA Journal, 2022)

Microbial succession and its effect on key aroma components during light-aroma-type Xiaoqu Baijiu brewing process - Bin Lin; Jie Tang; Qiang Yang; Zhixin Su; Liping Zhu; Qun Li; Wei Jiang; Long Zhang; Yuancai Liu; Shenxi Chen (World Journal of Microbiology and Biotechnology, 2022)

Does living alone increase the consumption of social resources? - Houyin Long; Susu Shi; Zhenpeng Tang; Shunming Zhang (Environmental Science and Pollution Research, 2022)

Effect of geomorphologic features and climate change on vegetation distribution in the arid hot valleys of Jinsha River, Southwest China - Yang Zhou; Yu-jun Yi; Hong-xi Liu; Cai-hong Tang; Yu-long Zhu; Shang-hong Zhang (Journal of Mountain Science, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

Plant Hormone Metabolome and Transcriptome Analysis of Dwarf and Wild-type Banana - Biao Deng; Xuan Wang; Xing Long; Ren Fang; Shuangyun Zhou; Ji Zhang; Xiaolu Peng; Zhenyu An; Weixiong Huang; Wenzhong Tang; Yining Gao; Jinyan Yao (Journal of Plant Growth Regulation, 2022)
Gibberellin (GA), auxin (IAA) and brassinosteroid (BR) are indispensable in the process of plant growth and development. Currently, research on the regulatory mechanism of phytohormones in banana dwarfism is mainly focused on GA, and few studies are focused on IAA and BR. In this study, we measured the contents of endogenous GA, IAA and BR and compared the transcriptomes of wild-type Williams banana and its dwarf mutant across five successive growth periods. We investigated the relationship between hormones and banana dwarfism and explored differential gene expression through transcriptome analysis, thus revealing the possible metabolic regulatory mechanism. We inferred a complex regulatory network of banana dwarfing. In terms of endogenous hormone levels, GA and IAA had significant effects on banana dwarfing, while BR had little effect. The key gene in GA biosynthesis of is GA2ox , and the key genes in IAA biosynthesis are TDC and YUCCA . The differential expression of these genes might be the main factor affecting hormone levels and plant height. In terms of hormone signal transduction, DELLA and AUX/IAA repressor proteins were the core regulators of GA and IAA, respectively. They inhibited the process of signal transduction and had feedback regulation on hormone levels. Finally, the transporter protein PIN, AUX1/LAX protein family and ABCB subfamily played supplementary roles in the transport of IAA. These results provide new insights into GA and IAA regulation of banana growth and a reliable foundation for the improvement of dwarf varieties.

The relationship between short-term PM2.5 exposure and outpatient visits for acne vulgaris in Chongqing, China: a time-series study - Xiang Li; Lai-Xin Zhou; Li-Li Yang; Xiao-Long Huang; Nan Wang; Yue-Gu Hu; En-Jie Tang; Hua Xiao; Yu-Meng Zhou; Ya-Fei Li; Yuan-Gang Lu; Tong-Jian Cai (Environmental Science and Pollution Research, 2022)

Mental health conditions and academic burnout among medical and non-medical undergraduates during the mitigation of COVID-19 pandemic in China - Qian Yang; Yueheng Liu; Winson Fuzun Yang; Pu Peng; Shubao Chen; Yunfei Wang; Xin Wang; Manyun Li; Yingying Wang; Yuzhu Hao; Li He; Qianjin Wang; et al. (Environmental Science and Pollution Research, 2022)
The outbreak of the novel coronavirus disease 2019 (COVID-19) has posed a great impact on people’s mental health, especially for undergraduate students. This study aimed to compare the mental health conditions and academic burnout between medical and non-medical undergraduates in China when the COVID-19 pandemic is mitigating. A cross-sectional online survey was conducted among 4,972 undergraduates between October 2020 and April 2021, when the pandemic was basically under control. The survey included basic demographics information and standardized scales to evaluate depression, anxiety, perceived stress, daytime sleepiness, alcohol abuse/dependence, quality of life, fatigue, and academic burnout. Compared with medical undergraduates, non-medical undergraduates had higher rates of moderate to severe depression symptoms (29.1% vs. 17.9%, P < 0.001), moderate to severe anxiety symptoms (19.7% vs. 8.9%, P < 0.001), alcohol abuse/dependence (16.3% vs.10.3%, P < 0.001), excessive daytime sleepiness (47.4% vs. 43.4%, P = 0.018), high perceived stress (34.7% vs. 22.2%, P < 0.001), high level of fatigue (51.8% vs. 42.2%, P < 0.001), low QOL (35.8% vs. 21.4%, P < 0.001), and higher academic burnout score (59.4 vs. 57.5, P < 0.001). Being non-medical undergraduates, depression, alcohol abuse/dependence, excessive daytime sleepiness, and high perceived stress were positively associated with academic burnout, while high QOL was negatively associated with the burnout (all P < 0.001). Excessive daytime sleepiness was the strongest predictor for academic burnout.

Simulating the development of resilient human settlement in Changsha - Lisha Tang; Hualou Long (Journal of Geographical Sciences, 2022)

Genetic and transcriptomic dissection of an artificially induced paired spikelets mutant of wheat (Triticum aestivum L.) - Juanyu Zhang; Yanyan Tang; Xi Pu; Xuebing Qiu; Jinhui Wang; Tao Li; Zhao Yang; Yao Zhou; Yuxiao Chang; Junjun Liang; Haili Zhang; Guangbing Deng; et al. (Theoretical and Applied Genetics, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

High-normal blood pressure (prehypertension) is associated with PM2.5 exposure in young adults - Huaze Ye; Jie Tang; Leiqin Luo; Tianjian Yang; Kedi Fan; Long Xu (Environmental Science and Pollution Research, 2022)

Marker-assisted pyramiding of QTLs for heat tolerance and escape upgrades heat resilience in rice (Oryza sativa L.) - Changrong Ye; Tsutomu Ishimaru; Leslie Lambio; Le Li; Yu Long; Zhizhou He; Than Myint Htun; Shunxue Tang; Zhenxi Su (Theoretical and Applied Genetics, 2022)

Short-form OPA1 is a molecular chaperone in mitochondrial intermembrane space - Deyang Yao; Yukun Li; Sheng Zeng; Zhifan Li; Zahir Shah; Bigui Song; Jinglei Liu; Yi Wu; Liang Yang; Qi Long; Wenqian Wang; Zhijuan Hu; et al. (Science China Life Sciences, 2022)

Euphopanes A–C, three new diterpenoids from Euphorbia pekinensis - Xue-Long Yan; Jia-Luo Huang; Ya-Qi Tang; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2022)

Genetic dissection of quantitative trait loci for grain size and weight by high-resolution genetic mapping in bread wheat (Triticum aestivum L.) - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Juanyu Zhang; Xvebing Qiu; Xi Pu; Wuyun Yang; Jun Li; Zehou Liu; et al. (Theoretical and Applied Genetics, 2022)

MAPK5 and MAPK10 overexpression influences strawberry fruit ripening, antioxidant capacity and resistance to Botrytis cinerea - Yunting Zhang; Yu Long; Yiting Liu; Min Yang; Liangxin Wang; Xiaoyang Liu; Yong Zhang; Qing Chen; Mengyao Li; Yuanxiu Lin; Haoru Tang; Ya Luo (Planta, 2022)

Standard litterbags underestimate early-stage lower-order root decomposition rate in a subtropical forest, China - Guan-tao Chen; Yu-qin Chen; Yong Peng; Hong-ling Hu; Jiu-long Xie; Gang Chen; Yin-long Xiao; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2021)

Mineralogical characteristics and sedimentary envrionment significance of water-insoluble minerals in potash deposits of Vientiane Basin of Laos - Tang Qi-liang; Zhang Xi-ying; Miao Wei-liang; Ma Hai-zhou; Li Yong-shou; Li Wen-xia; Yuan Xiao-long (Carbonates and Evaporites, 2021)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

Experimental study of the frozen soil–structure interface shear strength deterioration mechanism during thawing - Liyun Tang; Yang Du; Lang Liu; Long Jin; Liujun Yang; Yongtang Yu (Arabian Journal of Geosciences, 2021)

Euphanoids A and B, two new lathyrane diterpenoids with nitric oxide (NO) inhibitory activity from Euphorbia kansuensis - Xue-Long Yan; Run-Zhu Fan; Jun Sang; Xing-Lin Xie; Gui-Hua Tang; Sheng Yin (Natural Product Research, 2021)

Identification and validation of two major QTLs for spike compactness and length in bread wheat (Triticum aestivum L.) showing pleiotropic effects on yield-related traits - Tao Li; Guangbing Deng; Yan Su; Zhao Yang; Yanyan Tang; Jinhui Wang; Xvebing Qiu; Xi Pu; Jun Li; Zehou Liu; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

New types of ATP ‐grasp ligase are associated with the novel pathway for complicated mycosporine‐like amino acid production in desiccation‐tolerant cyanobacteria - Zhong‐Chun Zhang; Kai Wang; Fu‐Hua Hao; Jin‐Long Shang; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2021)
Summary Mycosporine‐like amino acids (MAAs) were widespread in diverse organisms to attenuate UV radiation. We recently characterized the large, complicated MAA mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) in desert cyanobacterium Nostoc flagelliforme . Synthesis of this MAA requires the five‐gene cluster mysABDC2C3 . Here, bioinformatic analysis indicated that mysC duplication within five‐gene mys clusters is strictly limited to drought‐tolerant cyanobacteria. Phylogenic analysis distinguished these duplicated MysCs into two clades that separated from canonical MysCs. Heterologous expression of N. flagelliforme mys genes in Escherichia coli showed that MysAB produces 4‐deoxygadusol. The ATP‐grasp ligase of MysC3 catalyses the linkage of the δ‐ or ε‐amino group of ornithine/lysine to 4‐deoxygadusol, yielding mycosporine‐ornithine or mycosporine‐lysine respectively. The ATP‐grasp ligase of MysC2 strictly condenses the α‐amino group of mycosporine‐ornithine to another 4‐deoxygadusol. MysD (D‐Ala–D‐Ala ligase) functions following MysC2 to catalyse the formation of mycosporine‐2‐(4‐deoxygadusolyl‐ornithine). High arginine content likely provides a greater pool of ornithine over other amino acids during rehydration of desiccated N. flagelliforme . Duplication of ATP‐grasp ligases is specific for the use of substrates that have two amino groups (such as ornithine) for the production of complicated MAAs with multiple chromophores. This five‐enzyme biosynthesis pathway for complicated MAAs is a novel adaptation of cyanobacteria for UV tolerance in drought environments.

Correction to: Biomimetic Biphasic Electrospun Scaffold for Anterior Cruciate Ligament Tissue Engineering - Ya Tang; Jialiang Tian; Long Li; Lin Huang; Quan Shen; Shanzhu Guo; Yue Jiang (Tissue Engineering and Regenerative Medicine, 2021)

Biomimetic Biphasic Electrospun Scaffold for Anterior Cruciate Ligament Tissue Engineering - Ya Tang; Jialiang Tian; Long Li; Lin Huang; Quan Shen; Shanzhu Guo; Yue Jiang (Tissue Engineering and Regenerative Medicine, 2021)

Genetic and molecular characterization of determinant of six-rowed spike of barley carrying vrs1.a4 - Jin-Hui Wang; Zhen-Mei Xu; Xue-Bing Qiu; Li-Lan Li; Shui-Yang Yu; Tao Li; Yan-Yan Tang; Xi Pu; Juan-Yu Zhang; Hai-Li Zhang; Jun-Jun Liang; Ya-Wei Tang; et al. (Theoretical and Applied Genetics, 2021)

LncRNA LINC00689 Promotes the Tumorigenesis of Glioma via Mediation of miR-526b-3p/IGF2BP1 Axis - Wen-Liang Zhan; Ning Gao; Guo-Long Tu; Hong Tang; Ling Gao; Ying Xia (NeuroMolecular Medicine, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Creep characteristics and constitutive model for frozen mixed soils - Bing-tang Song; En-long Liu; Zhao-yun Shi; Pan Wang; Qi-hao Yu (Journal of Mountain Science, 2021)

Development and use of a reverse transcription insulated isothermal PCR assay for detection and characterization of bovine torovirus in yaks - Long Zhao; Guoqing Shao; Cheng Tang; Hua Yue (Archives of Virology, 2021)

Simulated Sensitivity of Ozone Generation to Precursors in Beijing during a High O3 Episode - Meng Cui; Xingqin An; Li Xing; Guohui Li; Guiqian Tang; Jianjun He; Xin Long; Shuman Zhao (Advances in Atmospheric Sciences, 2021)

Correction to: Shear properties and pore structure characteristics of soil–rock mixture under freeze–thaw cycles - Liyun Tang; Gang Li; Zhen Li; Long Jin; Gengshe Yang (Bulletin of Engineering Geology and the Environment, 2021)

Shear properties and pore structure characteristics of soil–rock mixture under freeze–thaw cycles - Liyun Tang; Gang Li; Zhen Li; Long Jin; Gengshe Yang (Bulletin of Engineering Geology and the Environment, 2021)

Correction to: Bio-electrospraying is a safe technology for delivering human adipose-derived stem cells - Chuan Ye; Zhixu He; Yunfeng Lin; Yi Zhang; Jin Tang; Bo Sun; Minxian Ma; Jielin Liu; Long Yang; Houxiang Ren; Baoping Zhao (Biotechnology Letters, 2021)

2,3,5,6-Tetramethylpyrazine protects retinal photoreceptors against endoplasmic reticulum stress by modulating ATF4-mediated inhibition of PRP aggregation - Hao Huang; Xiaobo Zhu; Hao Cheng; Xielan Kuang; Chongde Long; Xizhi Deng; Yuxiu Zou; Han Zhang; Yue Xing; Xiangtian Ling; Renchun Wang; Han Tang; et al. (Journal of Molecular Medicine, 2021)

Comprehensive analysis of coding sequence architecture features and gene expression in Arachis duranensis - Shuwei Dong; Long Zhang; Wenhui Pang; Yongli Zhang; Chang Wang; Zhenyi Li; Lichao Ma; Wei Tang; Guofeng Yang; Hui Song (Physiology and Molecular Biology of Plants, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

The geological characteristics of the large- and medium-sized gas fields in the South China Sea - Gongcheng Zhang; Dongdong Wang; Lei Lan; Shixiang Liu; Long Su; Long Wang; Wu Tang; Jia Guo; Rui Sun (Acta Oceanologica Sinica, 2021)

Resazurin as an indicator of reducing capacity for analyzing the physiologic status of deep-sea bacterium Photobacterium phosphoreum ANT-2200 - Jie Dai; Hongzhi Tang; Xuegong Li; Claire-Lise Santini; Wenpeng Cui; Na Liu; Xiaoqing Qi; Xuehua Cui; Alain Grossi; Philippe Notareschi; Wei-Jia Zhang; Long-Fei Wu (Journal of Oceanology and Limnology, 2021)

Adakitic rocks at convergent plate boundaries: Compositions and petrogenesis - Qiang Wang; Lulu Hao; Xiuzheng Zhang; Jinsheng Zhou; Jun Wang; Qiwei Li; Lin Ma; Long Zhang; Yue Qi; Gongjian Tang; Wei Dan; Jingjing Fan (Science China Earth Sciences, 2020)

Nitrogen Regulates the Grain Yield, Antioxidant Attributes, and Nitrogen Metabolism in Fragrant Rice Grown Under Lead-Contaminated Soil - Huoyi Feng; Yuzhan Li; Yangfan Yan; Xinhang Wei; Yihan Yang; Long Zhang; Lin Ma; Wu Li; Xiangru Tang; Zhaowen Mo (Journal of Soil Science and Plant Nutrition, 2020)

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

An emerging novel bovine coronavirus with a 4-amino-acid insertion in the receptor-binding domain of the hemagglutinin-esterase gene - Keha-mo Abi; Qi Zhang; Bin Zhang; Long Zhou; Hua Yue; Cheng Tang (Archives of Virology, 2020)

AMPKα2 deficiency exacerbates hypoxia-induced pulmonary hypertension by promoting pulmonary arterial smooth muscle cell proliferation - Hai-Long Wang; Fu-Qin Tang; Yun-Han Jiang; Yu Zhu; Zhao Jian; Ying-Bin Xiao (Journal of Physiology and Biochemistry, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Efficacy of amisulpride on postoperative nausea and vomiting: a systematic review and meta-analysis - Lu-Feng Zhang; Chao-Fan Zhang; Wen-Xin Tang; Long He; Yang Liu; Dan-Dan Tian; Yan-Qiu Ai (European Journal of Clinical Pharmacology, 2020)

Spatial Distribution and Source of Inorganic Elements in PM2.5 During a Typical Winter Haze Episode in Guilin, China - Tengfa Long; Bin Peng; Zhihui Yang; Chongjian Tang; Ziwei Ye; Ning Zhao; Chunqiang Chen (Archives of Environmental Contamination and Toxicology, 2020)

Variation in root growth responses of sweet potato to hypoxia and waterlogging - Loc Van Nguyen; Tri Manh Le; Phuong Diep Vien Ta; Giang Hoai Tran; Mbaraka Saidi Rumanzi; Hanh Thi Tang; Long Viet Nguyen (Vegetos, 2020)

Prevalence and molecular characterization of parechovirus A in children with acute gastroenteritis in Shenzhen, 2016–2018 - Ya-Nan Zhu; Yu-Hui Ye; Zhen Zhang; Yan-Jie Wu; Long Chen; Jing Wang; Yi-Jun Tang; Jun Meng; Hai-Long Zhang; Gui-Fang Hu (Archives of Virology, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Building a sequence map of the pig pan-genome from multiple de novo assemblies and Hi-C data - Xiaomeng Tian; Ran Li; Weiwei Fu; Yan Li; Xihong Wang; Ming Li; Duo Du; Qianzi Tang; Yudong Cai; Yiming Long; Yue Zhao; Mingzhou Li; et al. (Science China Life Sciences, 2020)

Role of Metallothionein-1 and Metallothionein-2 in the Neuroprotective Mechanism of Sevoflurane Preconditioning in Mice - Jitong Liu; Suhong Tan; Yongsheng Wang; Jia Luo; Yi Long; Xiping Mei; Yixun Tang (Journal of Molecular Neuroscience, 2020)

Effect of different biological solutions on microbially induced carbonate precipitation and reinforcement of sand - Zhi-Feng Tian; Xiaowei Tang; Zhi-Long Xiu; Zhi-Jia Xue (Marine Georesources & Geotechnology, 2020)

Fine mapping of the qHTB1-1QTL, which confers heat tolerance at the booting stage, using an Oryza rufipogon Griff. introgression line - Zhibin Cao; Yao Li; Huiwu Tang; Bohong Zeng; Xiuying Tang; Qizhang Long; Xiaofeng Wu; Yaohui Cai; Linfeng Yuan; Jianlin Wan (Theoretical and Applied Genetics, 2020)

Calculation Model of Supporting System for Tunnel Under Shallow and Weak Surrounding Rock Considering the Synergistic Effects - Haorong Cao; Limin Peng; Mingfeng Lei; Qianlong Tang; Long Peng; Fudong Chen (Geotechnical and Geological Engineering, 2020)

Spatial Distribution and Formation Mechanism of Water-soluble Inorganic Ions in PM2.5 During a Typical Winter Haze Episode in Guilin, China - Tengfa Long; Bin Peng; Zhihui Yang; Cynthia Sabrine Ishimwe; Chongjian Tang; Ning Zhao; Hong Lin; Kai Zhong; Shan Zhong (Archives of Environmental Contamination and Toxicology, 2020)

Two novel strains, Bacillus albus JK-XZ3 and B. velezensis JK-XZ8, with activity against Cerasus crown gall disease in Xuzhou, China - Peng Yan; Xi-Tang Zhang; Long-Jiao Hu; Ya-Hui Wang; Mei-Ling Zhu; Xiao-Qin Wu; Fei Chen (Australasian Plant Pathology, 2020)

Cardioprotective Effects and Duration of Beta Blocker Therapy in Anthracycline-Treated Patients: A Systematic Review and Meta-analysis - Liuyue Xu; Yaoying Long; Xiaoqiong Tang; Nan Zhang (Cardiovascular Toxicology, 2020)

Influence of humic acid and its different molecular weight fractions on sedimentation of nanoscale zero-valent iron - Yanan Wu; Haoran Dong; Lin Tang; Long Li; Yaoyao Wang; Qin Ning; Bin Wang; Guangming Zeng (Environmental Science and Pollution Research, 2020)

Insights into the regulatory characteristics of silkworm fibroin gene promoters using a modified Gal4/UAS system - Rongpeng Liu; Wenhui Zeng; Tingting Tan; Tao Chen; Qin Luo; Dawei Qu; Yiyun Tang; Dingpei Long; Hanfu Xu (Transgenic Research, 2019)

Combining potassium chloride leaching with vertical electrokinetics to remediate cadmium-contaminated soils - Qiang Ma; Jun Li; Charles C. C. Lee; Xinxian Long; Yongmao Liu; Qi-Tang Wu (Environmental Geochemistry and Health, 2019)

Protective Effects of 1-Methylnicotinamide on Aβ1–42-Induced Cognitive Deficits, Neuroinflammation and Apoptosis in Mice - Lili Fu; Caihong Liu; Liang Chen; Yangge Lv; Guoliang Meng; Mei Hu; Yan Long; Hao Hong; Susu Tang (Journal of Neuroimmune Pharmacology, 2019)

Changes in bacterial community structure and humic acid composition in response to enhanced extracellular electron transfer process in coastal sediment - Jiulong Zhao; Long Wang; Lili Tang; Rui Ren; Wuxin You; Robina Farooq; Zejie Wang; Yongyu Zhang (Archives of Microbiology, 2019)

Implementation of quasi-real-time estimation of BDS clock - Wei Ning; Jian-Bo Wang; Long-Jiang Tang (Acta Geophysica, 2019)

Heavy metal distribution, translocation, and human health risk assessment in the soil-rice system around Dongting Lake area, China - Lin Tang; Sihan Deng; Di Tan; Jiumei Long; Ming Lei (Environmental Science and Pollution Research, 2019)

Evoked potential study of the inferior collicular response to constant frequency-frequency modulation (CF-FM) sounds in FM and CF-FM bats - Ziying Fu; Na Xu; Guimin Zhang; Dandan Zhou; Long Liu; Jia Tang; Philip Hung-Sun Jen; Qicai Chen (Journal of Comparative Physiology A, 2019)

Surface Dissolution UV Imaging for Investigation of Dissolution of Poorly Soluble Drugs and Their Amorphous Formulation - Chiau Ming Long; Kin Tang; Hitesh Chokshi; Nikoletta Fotaki (AAPS PharmSciTech, 2019)
The aim of this study is to investigate the dissolution properties of poorly soluble drugs from their pure form and their amorphous formulation under physiological relevant conditions for oral administration based on surface dissolution ultraviolet (UV) imaging. Dissolution of two poorly soluble drugs (cefuroxime axetil and itraconazole) and their amorphous formulations (Zinnat ® and Sporanox ® ) was studied with the Sirius Surface Dissolution Imager (SDI). Media simulating the fasted state conditions (compendial and biorelevant) with sequential media/flow rate change were used. The dissolution mechanism of cefuroxime axetil in simulated gastric fluid (SGF), fasted state simulated gastric fluid (FaSSGF) and simulated intestinal fluid (SIF) is predominantly swelling as opposed to the convective flow in fasted state simulated intestinal fluid (FaSSIF-V1), attributed to the effect of mixed micelles. For the itraconazole compact in biorelevant media, a clear upward diffusion of the dissolved itraconazole into the bulk buffer solution is observed. Dissolution of itraconazole from the Sporanox ® compact is affected by the polyethylene glycol (PEG) gelling layer and hydroxypropyl methylcellulose (HPMC) matrix, and a steady diffusional dissolution pattern is revealed. A visual representation and a quantitative assessment of dissolution properties of poorly soluble compounds and their amorphous formulation can be obtained with the use of surface dissolution imaging under in vivo relevant conditions.

The effects of ethoxyquin and Angelica sinensis extracts on lipid oxidation in fish feeds and growth, digestive and absorptive capacities and antioxidant status in juvenile red carp (Cyprinus carpio var. xingguonensis): a comparative study - HuaTao Li; SiYi Tang; WenHao Du; Jun Jiang; PeiYuan Peng; Ping Yuan; YiHong Liao; Jiao Long; SiShun Zhou (Fish Physiology and Biochemistry, 2019)

Studies on Factors Influencing Hydrodynamic Characteristics of Plates Used in Artificial Reefs - Yanli Tang; Wenzhao Yang; Liyuan Sun; Fenfang Zhao; Xiangyu Long; Gang Wang (Journal of Ocean University of China, 2019)

A new surface gliding species of Chironomidae: An independent invasion of marine environments and its evolutionary implications - Xin Qi; Xiao‐Long Lin; Torbjørn Ekrem; Rolf Georg Beutel; Chao Song; Igor Orlov; Chun‐Tang Chen; Xin‐Hua Wang (Zoologica Scripta, 2019)
Insects have invaded marine habitats only rarely and secondarily. Recently, we discovered a flightless dipteran species skating rapidly on the surface of seawater ponds at the Pacific coast of eastern China. Morphological analyses initially suggested an isolated position of the non‐biting midge, suggesting the erection of a new genus within Chironomini (Diptera: Chironomidae). However, an analysis of molecular data revealed that the marine species is in fact nested within the species‐rich genus Dicrotendipes . The apparent conflict between molecular and morphological data can be easily explained. It is likely that the new species has evolved a series of autapomorphic adaptations. These traits clearly distinguish the taxon from other species of the genus but do not justify the erection of a new supraspecific taxon, which would render Dicrotendipes paraphyletic. The switch to marine environments was likely a trigger for various morphological modifications resulting from increased selective pressure. Molecular data suggest that the potential speciation event occurred around 19–29 Ma, linked with a migration from freshwater to seawater ponds along the Pacific Ocean. Considering the results of our analysis, we place the flightless marine skater in the genus Dicrotendipes . All life stages of Dicrotendipes sinicus Qi & Lin sp. n. are described and illustrated, associated with larvae obtained by rearing or confirmed through association with DNA barcodes. The biology and ecology of the species are outlined based on collection data and in situ observations. Evolutionary patterns linked with repeated invasions of marine habitats are discussed.

Garnet amphibolites from the Ganzi–Litang fault zone, eastern Tibetan Plateau: mineralogy, geochemistry, and implications for evolution of the eastern Palaeo-Tethys Realm - Qiu-Huan Li; Yu-Xiu Zhang; Kai-Jun Zhang; Li-Long Yan; Lu Zeng; Xin Jin; Jin-Feng Sun; Xiao-Yao Zhou; Xian-Chun Tang; Lu Lu (International Geology Review, 2018)

Retraction Note to: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

Rapid dephosphorylation of glyphosate by Cu-catalyzed sulfite oxidation involving sulfate and hydroxyl radicals - Long Chen; Xingyun Huang; Min Tang; Danna Zhou; Feng Wu (Environmental Chemistry Letters, 2018)

Potential impacts of climate change on storage conditions for commercial agriculture: an example for potato production in Michigan - Julie A. Winkler; Logan Soldo; Ying Tang; Todd Forbush; David S. Douches; Chris M. Long; Courtney P. Leisner; C. Robin Buell (Climatic Change, 2018)

Role of peroxisome proliferator-activated receptor alpha (PPARα) and PPARα-mediated species differences in triclosan-induced liver toxicity - Yangshun Tang; Michelle M. Vanlandingham; Yuanfeng Wu; Frederick A. Beland; Greg R. Olson; Jia-Long Fang (Archives of Toxicology, 2018)

Large-area tsunami signatures in ionosphere observed by GPS TEC after the 2011 Tohoku earthquake - Long Tang; Zhe Li; Boyang Zhou (GPS Solutions, 2018)

RETRACTED ARTICLE: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

New views and possibilities of antidiabetic drugs in treating and/or preventing mild cognitive impairment and Alzheimer’s Disease - Kai Long Zhong; Fang Chen; Hao Hong; Xuan Ke; Yang Ge Lv; Su Su Tang; Yu Bing Zhu (Metabolic Brain Disease, 2018)

Identifying the driving factors of sediment delivery ratio on individual flood events in a long-term monitoring headwater basin - Ling-ling Wang; Wen-yi Yao; Jia-liang Tang; Wen-long Wang; Xin-xin Hou (Journal of Mountain Science, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

Sedimentary chronology reinterpreted from Changshou Lake of the Three Gorges Reservoir Area reveals natural and anthropogenic controls on sediment production - Raheel Anjum; Qiang Tang; Adrian L. Collins; Jinzhang Gao; Yi Long; Xinbao Zhang; Xiubin He; Zhonglin Shi; Anbang Wen; Jie Wei (Environmental Science and Pollution Research, 2018)

Photosynthetic tolerance to non‐resource stress influences competition importance and intensity in an invaded estuary - Long Tang; Amelia A. Wolf; Yang Gao; Cheng Huan Wang (Ecology, 2018)
In an attempt to clarify the role of environmental and biotic interactions on plant growth, there has been a long‐running ecological debate over whether the intensity and importance of competition stabilizes, increases or decreases across environmental gradients. We conducted an experiment in a Chinese estuary to investigate the effects of a non‐resource stress gradient, soil salinity (from 1.4‰ to 19.0‰ salinity), on the competitive interactions between native Phragmites australis and invasive Spartina alterniflora . We linked these effects to measurements of photosynthetic activities to further elucidate the underlying physiological mechanism behind the competitive interactions and the driver of invasion. The experiments revealed that while biomass of both species decreased in the presence of the other, competition did not alter photosynthetic activity of either species over time. P. australis exhibited high photosynthetic activity, including low chlorophyllase activity, high chlorophyll content, high stomatal conductance and high net photosynthetic rate, at low salinity. Under these conditions, P. australis experienced low competitive intensity, leading to high biomass production and competitive exclusion of S. alterniflora . The opposite was observed for S. alterniflora : while competitive intensity experienced by P. australis increased with increasing salinity, and photosynthetic activity, biomass, competitive dominance and the importance of competition for P. australis growth decreased, those of S. alterniflora were stable. These findings demonstrate that S. alterniflora invasion driven by competitive exclusion are likely to occur and expand in high salinity zones. The change in the nature of competition along a non‐resource stress gradient differs between competitors likely due to differences in photosynthetic tolerance to salinity. The driver of growth of the less‐tolerant species changes from competition to non‐resource stress factors with increasing stress levels, whereas competition is constantly important for growth of the more‐tolerant species. Incorporating metrics of both competition intensity and importance, as well as linking these competitive outcomes with physiological mechanisms, is crucial to understanding, predicting, and mediating the effects of invasive species in the future.

Optimization and characterization of biosurfactant production from kitchen waste oil using Pseudomonas aeruginosa - Chunyan Chen; Ni Sun; Dongsheng Li; Sihua Long; Xiaoyu Tang; Guoqing Xiao; Linyuan Wang (Environmental Science and Pollution Research, 2018)

Signaling molecule methylglyoxal-induced thermotolerance is partly mediated by hydrogen sulfide in maize (Zea mays L.) seedlings - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang (Acta Physiologiae Plantarum, 2018)

The effect of electron competition on chromate reduction using methane as electron donor - Pan-Long Lv; Liang Zhong; Qiu-Yi Dong; Shi-Lei Yang; Wei-Wei Shen; Quan-Song Zhu; Chun-Yu Lai; An-Cheng Luo; Youneng Tang; He-Ping Zhao (Environmental Science and Pollution Research, 2018)

RAGE-NF-κB-PPARγ Signaling is Involved in AGEs-Induced Upregulation of Amyloid-β Influx Transport in an In Vitro BBB Model - Fang Chen; Arijit Ghosh; Mei Hu; Yan Long; Hongbin Sun; Lingyi Kong; Hao Hong; Susu Tang (Neurotoxicity Research, 2018)

Expression profiles of microRNAs in oxidized low-density lipoprotein-stimulated RAW 264.7 cells - Xiaokai Li; Siyuan Feng; Yi Luo; Keren Long; Zhenghao Lin; Jideng Ma; Anan Jiang; Long Jin; Qianzi Tang; Mingzhou Li; Xun Wang (In Vitro Cellular & Developmental Biology - Animal, 2018)

Correction to: Age at menarche and age at natural menopause in East Asian women: a genome-wide association study - Jiajun Shi; Ben Zhang; Ji-Yeob Choi; Yu-Tang Gao; Huaixing Li; Wei Lu; Jirong Long; Daehee Kang; Yong-Bing Xiang; Wanqing Wen; Sue K. Park; Xingwang Ye; et al. (GeroScience, 2018)

Controlling mechanism of absence seizures by deep brain stimulus applied on subthalamic nucleus - Bing Hu; Yu Guo; Xiaoqiang Zou; Jing Dong; Long Pan; Min Yu; Zhejia Yang; Chaowei Zhou; Zhang Cheng; Wanyue Tang; Haochen Sun (Cognitive Neurodynamics, 2018)

Effects of different fertilizer application methods on the community of nitrifiers and denitrifiers in a paddy soil - Ran Duan; Xi-En Long; Yue-feng Tang; Jiong Wen; Shiming Su; Lingyu Bai; Rongle Liu; Xibai Zeng (Journal of Soils and Sediments, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Impacts of soil properties on phosphorus adsorption and fractions in purple soils - Yi Xiao; Jia-liang Tang; Ming-kuang Wang; Long-bo Zhai; Xi-feng Zhang (Journal of Mountain Science, 2017)

Tectonic subsidence of the Zhu 1 Sub-basin in the Pearl River Mouth Basin, northern South China Sea - Xiaoyin Tang; Shuchun Yang; Junzhang Zhu; Zulie Long; Guangzheng Jiang; Shaopeng Huang; Shengbiao Hu (Frontiers of Earth Science, 2017)

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

A new indole alkaloid with anti-inflammatory activity from Nauclea officinalis - Qing-Long Liu; A-Hong Chen; Jin-Ying Tang; Yan-Lei Ma; Zhi-Hua Jiang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Increasing the application of gas engines to decrease China’s GHG emissions - Liyan Feng; Jun Zhai; Lei Chen; Wuqiang Long; Jiangping Tian; Bin Tang (Mitigation and Adaptation Strategies for Global Change, 2017)

A new monoterpenoid indole alkaloid from Ochrosia elliptica - A-Hong Chen; Qing-Long Liu; Yan-Lei Ma; Zhi-Hua Jiang; Jin-Ying Tang; Yan-Ping Liu; Guang-Ying Chen; Yan-Hui Fu; Wei Xu (Natural Product Research, 2017)

Dynamic assessment of rainfall-induced shallow landslide hazard - Yang Tang; Kun-long Yin; Lei Liu; Ling Zhang; Xiao-lin Fu (Journal of Mountain Science, 2017)

Analysis of geometry-free residuals in case of traveling ionosphere disturbances and their impact cycle slip detection - Long Tang; Kai Zheng; Xingxing Li (GPS Solutions, 2017)

Comprehensive Analysis of R2R3-MYB Genes During Adventitious Root Formation in Cuttings of Morus alba - Xiao Long Du; Xu Cao; Chao Rui Yin; Zhuang Tang; Wei Du; Yue Yuan Ban; Jia Ling Cheng (Journal of Plant Growth Regulation, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Two eisosome proteins play opposite roles in autophagic control and sustain cell integrity, function and pathogenicity in Beauveria bassiana - Long‐Bin Zhang; Li Tang; Sheng‐Hua Ying; Ming‐Guang Feng (Environmental Microbiology, 2017)
Summary Pil1A and Pil1B are two core eisosome proteins that are homologous to yeast Pil1/Lsp1 or filamentous fungal Pil1A/Pil1B but have been unexplored in entomopathogenic fungi. Here we examined subcellular localization and functions of Pil1A and Pil1B in Beauveria bassiana , a fungal insect pathogen. Either localization or co‐localization experiments of the two proteins demonstrated that Pil1A and Pil1B were simultaneously localized at the periphery of hyphal cells for formation of stable, punctuate spots in B. bassiana . This is different from a reliance of proper Lsp1/Pil1B localization upon Pil1/Pil1A in other fungi. Deletions of pil1A and pil1B caused opposite changes in expression of many autophagy‐related genes and formation of intravacuolar autophagosomes. Such opposite changes were restored to nearly normal status by exogenous rapamycin, implicating a link of Pil1A/B to the target of rapamycin signalling pathway. All single/double deletion mutants of pil1A and pil1B lost almost all pathogenicity due to reduced ability to secrete Pr1 proteases for cuticle degradation. They also showed differential changes in cell wall integrity and multiple stress responses. These findings unveil opposite roles for Pil1A and Pil1B in autophagic regulation and an essentiality of both for cell integrity, function and pathogenicity of the fungal entomopathogen.

A cascading flash flood guidance system: development and application in Yunnan Province, China - Ziyue Zeng; Guoqiang Tang; Di Long; Chao Zeng; Meihong Ma; Yang Hong; Hui Xu; Jing Xu (Natural Hazards, 2016)

Contra-directional Coupling of Nur77 and Nurr1 in Neurodegeneration: A Novel Mechanism for Memantine-Induced Anti-inflammation and Anti-mitochondrial Impairment - Xiaobo Wei; Huimin Gao; Jing Zou; Xu Liu; Dan Chen; Jinchi Liao; Yunqi Xu; Long Ma; Beisha Tang; Zhuohua Zhang; Xiang Cai; Kunling Jin; et al. (Molecular Neurobiology, 2016)

NK cells contribute to persistent airway inflammation and AHR during the later stage of RSV infection in mice - Xiaoru Long; Jun Xie; Keting Zhao; Wei Li; Wei Tang; Sisi Chen; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Lijia Wang; Zhou Fu; et al. (Medical Microbiology and Immunology, 2016)

Geochemical fingerprints and pebbles zircon geochronology: Implications for the provenance and tectonic setting of Lower Cretaceous sediments in the Zhucheng Basin (Jiaodong peninsula, North China) - JIN-LONG NI; JUN-LAI LIU; XIAO-LING TANG; XIAO-XIAO SHI; HONG ZHANG; SHUAI HAN (Journal of Earth System Science, 2016)

Association between genetic risk score for telomere length and risk of breast cancer - Hung N. Luu; Jirong Long; Wanqing Wen; Ying Zheng; Qiuyin Cai; Yu-Tang Gao; Wei Zheng; Xiao-Ou Shu (Cancer Causes & Control, 2016)

Detachment folding in a Lower Cambrian–Upper Permian karst reservoir: 3D model of the Yubei 3D area (eastern Markit Slope, Tarim Basin, Northwest China) - JiuMei Li; LiangJie Tang; Yong Yue; Meng Li; ShengLong Zhang; Yu Long; ShaoHui Luo (Arabian Journal of Geosciences, 2016)

Hairy root induction and polysaccharide production of medicinal plant Callerya speciosa Champ. - Shao-chang Yao; Long-hua Bai; Zu-zai Lan; Mei-qiong Tang; Yong-jin Zhai; Hao Huang; Rong-chang Wei (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

PPARδ agonist GW0742 ameliorates Aβ1–42-induced hippocampal neurotoxicity in mice - Yun-Qi An; Chun Teng Zhang; Yong Du; Ming Zhang; Su Su Tang; Mei Hu; Yan Long; Hong Bing Sun; Hao Hong (Metabolic Brain Disease, 2016)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

Biosorption and degradation of decabromodiphenyl ether by Brevibacillus brevis and the influence of decabromodiphenyl ether on cellular metabolic responses - Linlin Wang; Litao Tang; Ran Wang; Xiaoya Wang; Jinshao Ye; Yan Long (Environmental Science and Pollution Research, 2016)

A Single Nucleotide Polymorphism of Nud Converts the Caryopsis Type of Barley (Hordeum Vulgare L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Xingquan Zeng; Yawei Tang; Nyima Tashi; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

The Ephrin-A5/EphA4 Interaction Modulates Neurogenesis and Angiogenesis by the p-Akt and p-ERK Pathways in a Mouse Model of TLE - Yi Shu; Bo Xiao; Qian Wu; Tiantian Liu; Yang Du; Haiyun Tang; Si Chen; Li Feng; Lili Long; Yi Li (Molecular Neurobiology, 2016)

Ameliorative Effects of p75NTR-ED-Fc on Axonal Regeneration and Functional Recovery in Spinal Cord-Injured Rats - Yong-Tang Wang; Xiu-Min Lu; Feng Zhu; Peng Huang; Ying Yu; Zai-Yun Long; Ya-Min Wu (Molecular Neurobiology, 2015)

Selenocystine-induced cell apoptosis and S-phase arrest inhibit human triple-negative breast cancer cell proliferation - Meijun Long; Juekun Wu; Junwen Hao; Wei Liu; Yong Tang; Xi Li; Hang Su; Wanshou Qiu (In Vitro Cellular & Developmental Biology - Animal, 2015)

Selenoprotein Genes Exhibit Differential Expression Patterns Between Hepatoma HepG2 and Normal Hepatocytes LO2 Cell Lines - Hua Zhao; Jiayong Tang; Jingyang Xu; Lei Cao; Gang Jia; Dingbiao Long; Guangmang Liu; Xiaoling Chen; Kangning Wang (Biological Trace Element Research, 2015)

Endogenous hydrogen sulfide regulated by calcium is involved in thermotolerance in tobacco Nicotiana tabacum L. suspension cell cultures - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Ling Wen; Bing-Yu Zhu; Xiong Min (Acta Physiologiae Plantarum, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Involvement of sulfhydryl compounds and antioxidant enzymes in H2S-induced heat tolerance in tobacco (Nicotiana tabacum L.) suspension-cultured cells - Zhong-Guang Li; Wei-Biao Long; Shi-Zhong Yang; Yang-Cai Wang; Ji-Hong Tang; Tao Chen (In Vitro Cellular & Developmental Biology - Plant, 2015)

A MicroRNA Profile in Fmr1 Knockout Mice Reveals MicroRNA Expression Alterations with Possible Roles in Fragile X Syndrome - Ting Liu; Rui-Ping Wan; Ling-Jia Tang; Shu-Jing Liu; Hai-Jun Li; Qi-Hua Zhao; Wei-Ping Liao; Xiao-Fang Sun; Yong-Hong Yi; Yue-Sheng Long (Molecular Neurobiology, 2015)

Changes in agricultural system as farmers adapt to economic-social and climatic changes in the min upriver rural areas in western Sichuan, southwestern China - Long-jiang Zhang; Ya Tang; Ben-hong Liu (Journal of Mountain Science, 2015)

Direct and indirect effects of nitrogen additions on fine root decomposition in a subtropical bamboo forest - Li-hua Tu; Yong Peng; Gang Chen; Hong-ling Hu; Yin-long Xiao; Ting-xing Hu; Li Liu; Yi Tang (Plant and Soil, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Bio-electrospraying is a safe technology for delivering human adipose-derived stem cells - Chuan Ye; Zhixu He; Yunfeng Lin; Yi Zhang; Jin Tang; Bo Sun; Minxian Ma; Jielin Liu; Long Yang; Houxiang Ren; Baoping Zhao (Biotechnology Letters, 2015)

Cognitive disorders in HIV-infected and AIDS patients in Guangxi, China - Tingting Zhao; Bo Wei; Jianxiong Long; Xianyan Tang; Mengxiao Zhou; Chao Dang (Journal of NeuroVirology, 2015)

Stress signaling in response to polycyclic aromatic hydrocarbon exposure in Arabidopsis thaliana involves a nucleoside diphosphate kinase, NDPK-3 - Hong Liu; David Weisman; Ling Tang; Long Tan; Wen-ke Zhang; Zong-hua Wang; Yan-he Huang; Wen-xiong Lin; Xuan-ming Liu; Adán Colón-Carmona (Planta, 2015)

Effects of management on vegetation dynamics and associated nutrient cycling in a karst area, Yunnan, SW China - Cindy Q. Tang; Yu-Hui Li; Zhi-Ying Zhang; Xiuli Hou; Keitarou Hara; Mizuki Tomita; Long-Yuan He; Xiao-Shuang Li (Landscape and Ecological Engineering, 2015)

Mechanical Model for Predicting Closure Behavior of Rock Joints Under Normal Stress - Zhi-Cheng Tang; Quan-Sheng Liu; Cai-Chu Xia; Ying-Long Song; Ji-Hui Huang; Chun-Bo Wang (Rock Mechanics and Rock Engineering, 2014)

Transcription of the Human Sodium Channel SCN1A Gene Is Repressed by a Scaffolding Protein RACK1 - Zhao-Fei Dong; Ling-Jia Tang; Guang-Fei Deng; Tao Zeng; Shu-Jing Liu; Rui-Ping Wan; Ting Liu; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2014)

Origin area and migration route: Chloroplast DNA diversity in the arctic-alpine plant Koenigia islandica - Cong Long; YunJiang Min; XiuXia Zhao; ChunLei Yany; Hang Sun; HouYuan Lü; LingYu Tang; ZhongZe Zhou (Science China Earth Sciences, 2014)

Response of artificial grassland carbon stock to management in mountain region of Southern Ningxia, China - Long Tang; Xiaohu Dang; Guobin Liu; Chuanke Shao; Sha Xue (Chinese Geographical Science, 2014)

Historical sediment record of 137Cs, δ-HCH, and δ 13C reflects the impact of land use on soil erosion - Xiang-Yu Tang; Xin-Bao Zhang; Zhuo Guan; Yi Long; Qiang Tang; Yu-Juan Lü (Journal of Mountain Science, 2014)

A novel variant in the 3′ UTR of human SCN1A gene from a patient with Dravet syndrome decreases mRNA stability mediated by GAPDH’s binding - Tao Zeng; Zhao-Fei Dong; Shu-Jing Liu; Rui-Ping Wan; Ling-Jia Tang; Ting Liu; Qi-Hua Zhao; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Human Genetics, 2014)

Adipose-derived stem cells transfected with pEGFP-OSX enhance bone formation during distraction osteogenesis - Qing-guo Lai; Shao-long Sun; Xiao-hong Zhou; Chen-ping Zhang; Kui-feng Yuan; Zhong-jun Yang; Sheng-lei Luo; Xiao-peng Tang; Jiang-bo Ci (Journal of Zhejiang University-SCIENCE B, 2014)

Inhibitory Effect of Gallic Acid on CCl4-Mediated Liver Fibrosis in Mice - Jing Wang; Long Tang; James White; Jing Fang (Cell Biochemistry and Biophysics, 2014)

A method developed for determination of heptachlor and its metabolites from pork - Hai Gen Zuo; Jian Xin Zhu; Chun Rui Zhan; Guo Yan Tang; Ping Guo; Yuan Long Wei; Hai Long Zeng; Hong Yang (Environmental Monitoring and Assessment, 2014)

Sema4D Knockdown in Oligodendrocytes Promotes Functional Recovery After Spinal Cord Injury - Hong-Lei Zhang; Jing Wang; Long Tang (Cell Biochemistry and Biophysics, 2014)

New Peak Shear Strength Criterion of Rock Joints Based on Quantified Surface Description - Cai-Chu Xia; Zhi-Cheng Tang; Wei-Min Xiao; Ying-Long Song (Rock Mechanics and Rock Engineering, 2014)

A comparative study of bioactive secondary metabolite production in diploid and tetraploid Echinacea purpurea (L.) Moench - Chuan-gui Xu; Tie-xin Tang; Rong Chen; Chun-hui Liang; Xiang-yu Liu; Chuan-long Wu; Yue-sheng Yang; De-po Yang; Hong Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Combined effect of five single nucleotide polymorphisms related to IL23/Th17 pathway in the risk of psoriasis - Xianyong Yin; Hui Cheng; Ran Zhang; Xing Fan; Fusheng Zhou; Long Jiang; Xianfa Tang; Gang Chen; Xianbo Zuo; Xiaodong Zheng; Sen Yang; Xuejun Zhang (Immunogenetics, 2014)

Development and characterization of thirteen polymorphic microsatellite markers in the fish Osteochilus salsburyi - Li-Wei Su; Zhi-Zhi Liu; Wen-Qiao Tang; Bao-Long Bao; Dong Liu; Jin-Quan Yang (Conservation Genetics Resources, 2014)

Heat exchanger network synthesis based on environmental impact minimization - Zun-Long Jin; Xiao-Tang Chen; Yong-Qing Wang; Min-Shan Liu (Clean Technologies and Environmental Policy, 2014)

Overweight and Obesity Associated With Increased Total Serum Calcium Level: Comparison of Cross-sectional Data in the Health Screening for Teaching Faculty - Xiao-hua Ren; Ying-shui Yao; Lian-ping He; Yue-long Jin; Wei-wei Chang; Jie Li; Yan Chen; Xiu-li Song; Hui Tang; Ling-ling Ding; Dao-xia Guo; Chao-ping Li (Biological Trace Element Research, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

Microbiota Regulates the TLR7 Signaling Pathway Against Respiratory Tract Influenza A Virus Infection - Sha Wu; Zhen-You Jiang; Yi-Fan Sun; Bin Yu; Jia Chen; Cong-Qi Dai; Xian-Lin Wu; Xiao-Long Tang; Xiao-Yin Chen (Current Microbiology, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Biomass evaluation of concealed insect pests at parasitism based on allometric scaling laws - Xiao-yi Wang; Yan-long Tang; Ji-fang Lu; Zhong-qi Yang (Phytoparasitica, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

Effects of rosuvastatin on the production and activation of matrix metalloproteinase-2 and migration of cultured rat vascular smooth muscle cells induced by homocysteine - Ya-fei Shi; Ju-fang Chi; Wei-liang Tang; Fu-kang Xu; Long-bin Liu; Zheng Ji; Hai-tao Lv; Hang-yuan Guo (Journal of Zhejiang University-SCIENCE B, 2013)

Effects of Different Selenium Levels on Gene Expression of a Subset of Selenoproteins and Antioxidative Capacity in Mice - Qin Zhang; Long Chen; Kai Guo; Liangyan Zheng; Bitao Liu; Wenlan Yu; Cuili Guo; Zhengwei Liu; Ye Chen; Zhaoxin Tang (Biological Trace Element Research, 2013)

QTL Analysis for Grain Pentosans and Hardness Index in a Chinese 1RS.1BL × non-1RS.1BL Wheat Cross - Hong-Min Li; Heng Liang; Zong-Xiang Tang; Huai-Qiong Zhang; Ben-Ju Yan; Zheng-Long Ren (Plant Molecular Biology Reporter, 2013)

Effects of PGR and ESRα genotypes on the pregnancy rates after embryo transfer in Luxi cattle - Ke-Qiong Tang; Wu-Cai Yang; Bin Pai; Shu-Jing Li; Long Chen; Li-Guo Yang (Molecular Biology Reports, 2013)

Determination of methylmercury in marine fish from coastal areas of Zhejiang, China - Zhu Huang; Xiao-Dong Pan; Jian-Long Han; Ping-Gu Wu; Jun Tang; Ying Tan (Food Additives & Contaminants Part B-Surveillance, 2012)

Effect of Copper Chloride Exposure on the Membrane Potential and Cytosolic Free Calcium in Primary Cultured Chicken Hepatocytes - Xuexia Jia; Long Chen; Jingtao Li; Rongsheng Su; Dayou Shi; Zhaoxin Tang (Biological Trace Element Research, 2012)

Quercetin-induced apoptosis of HL-60 cells by reducing PI3K/Akt - Zhang Yuan; Chen Long; Tang Junming; Liu Qihuan; Zhang Youshun; Zou Chan (Molecular Biology Reports, 2012)

Parameterizing soil organic carbon’s impacts on soil porosity and thermal parameters for Eastern Tibet grasslands - YingYing Chen; Kun Yang; WenJun Tang; Jun Qin; Long Zhao (Science China Earth Sciences, 2012)

One-Step Bulk Preparation of Calcium Carbonate Nanotubes and Its Application in Anticancer Drug Delivery - Jing Tang; Dong-Mei Sun; Wen-Yu Qian; Rong-Rong Zhu; Xiao-Yu Sun; Wen-Rui Wang; Kun Li; Shi-Long Wang (Biological Trace Element Research, 2012)

Effects of Selenoprotein W gene expression by selenium involves regulation of mRNA stability in chicken embryos neurons - Jin-Long Li; Hui-Xin Li; Shu Li; Xue-Jiao Gao; Shi-Wen Xu; Zhao-Xin Tang (BioMetals, 2012)

Literature and patent analysis of the cloning and identification of human functional genes in China - Yan Xia; LiSha Tang; Lei Yao; Bo Wan; XianMei Yang; Long Yu (Science China Life Sciences, 2012)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Enhanced biodesulfurization by expression of dibenzothiophene uptake genes in Rhodococcus erythropolis - Ze-long Wang; Dan Wang; Qiang Li; Wang-liang Li; Huang Tang; Jian-min Xing (World Journal of Microbiology and Biotechnology, 2011)

Molecular cloning, characterization and mRNA expression analysis of a novel selenoprotein: avian selenoprotein W from chicken - Jin-Long Li; Hong-Feng Ruan; Hui-Xin Li; Shu Li; Shi-Wen Xu; Zhao-Xin Tang (Molecular Biology Reports, 2011)

c-Myc influences olaquindox-induced apoptosis in human hepatoma G2 cells - Ting Zhang; Shu-Sheng Tang; Xi Jin; Feng-Ying Liu; Chao-Ming Zhang; Wen-Xia Zhao; Shen Zhang; Chun-Di Sun; Xi-Long Xiao (Molecular and Cellular Biochemistry, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Monitoring and identification of spatiotemporal landscape changes in multiple remote sensing images by using a stratified conditional Latin hypercube sampling approach and geostatistical simulation - Yu-Pin Lin; Hone-Jay Chu; Yu-Long Huang; Chia-Hsi Tang; Shahrokh Rouhani (Environmental Monitoring and Assessment, 2011)

Differential expression of signaling pathways in odontogenic differentiation of ectomesenchymal cells isolated from the first branchial arch - Yongchun Yu; Mingheng Li; Jie Sun; Miaomiao Yang; Jie Long; Weidong Tian; Wei Tang; Tangxin Li; Lei Liu (Molecular and Cellular Biochemistry, 2011)

Selenoprotein W gene expression in the gastrointestinal tract of chicken is affected by dietary selenium - Jin-Long Li; Hui-Xin Li; Shu Li; Zhi-Hui Jiang; Shi-Wen Xu; Zhao-Xin Tang (BioMetals, 2011)

Exploring characteristics of bioelectricity generation and dye decolorization of mixed and pure bacterial cultures from wine-bearing wastewater treatment - Jing-Long Han; Ying Liu; Chang-Tang Chang; Bor-Yann Chen; Wen-Ming Chen; Hui-Zhong Xu (Biodegradation, 2011)

Novel 1-alkyl-tryptophan derivatives downregulate IDO1 and IDO2 mRNA expression induced by interferon-gamma in dendritic cells - Ting Sun; Xiang-Hua Chen; Zheng-De Tang; Jiong Cai; Xiao-Yan Wang; Shih-Chen Wang; Zhao-Long Li (Molecular and Cellular Biochemistry, 2010)

Testicular toxicity induced by dietary cadmium in cocks and ameliorative effect by selenium - Jin-Long Li; Rui Gao; Shu Li; Jin-Tao Wang; Zhao-Xin Tang; Shi-Wen Xu (BioMetals, 2010)

Zhihengliuella salsuginis sp. nov., a moderately halophilic actinobacterium from a subterranean brine - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhu-Xiang Liu; Qi-Hui Chen; Jian-Wu He; Xiao-Long Cui; Wen-Jun Li (Extremophiles, 2010)

Phytochemical analysis of an antiviral fraction of Radix astragali using HPLC–DAD–ESI–MS/MS - Li Tang; Ying Liu; Yeling Wang; Chunlin Long (Journal of Natural Medicines, 2010)

How tidal regime and treatment timing influence the clipping frequency for controlling invasive Spartina alterniflora: implications for reducing management costs - Long Tang; Yang Gao; Chenghuan Wang; Jinqing Wang; Bo Li; Jiakuan Chen; Bin Zhao (Biological Invasions, 2010)

Sequencing of Part of the Goat agouti Gene and SNP Identification - Xiang-long Li; Jing-wen Zhao; Chun-juan Tang; Rong-yan Zhou; Guiru Zheng; Lan-hui Li; Xiu-li Guo (Biochemical Genetics, 2010)

Virgibacillus litoralis sp. nov., a moderately halophilic bacterium isolated from saline soil - Yi-Guang Chen; Zhu-Xiang Liu; De-Jiao Peng; Yu-Qin Zhang; Yong-Xia Wang; Shu-Kun Tang; Wen-Jun Li; Xiao-Long Cui; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Alteromonas halophila sp. nov., a new moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Huai-Dong Xiao; Shu-Kun Tang; Yu-Qin Zhang; Entomack Borrathybay; Xiao-Long Cui; Wen-Jun Li; Yan-Qi Liu (Antonie van Leeuwenhoek, 2009)

Marinobacter zhanjiangensis sp. nov., a marine bacterium isolated from sea water of a tidal flat of the South China Sea - Da-Chun Zhuang; Yi-Guang Chen; Yu-Qin Zhang; Shu-Kun Tang; Xiao-Lei Wu; Zhou-Cai Tan; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Halobacillus naozhouensis sp. nov., a moderately halophilic bacterium isolated from a sea anemone - Yi-Guang Chen; Zhi-Xiong Liu; Yu-Qin Zhang; You-Xiang Zhang; Shu-Kun Tang; Entomack Borrathybay; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Arthrobacter halodurans sp. nov., a new halotolerant bacterium isolated from sea water - Yi-Guang Chen; Shu-Kun Tang; Yu-Qin Zhang; Zhao-Yang Li; Lang-Bo Yi; Yong-Xia Wang; Wen-Jun Li; Xiao-Long Cui (Antonie van Leeuwenhoek, 2009)

Identification of a novel human lactate dehydrogenase gene LDHAL6A, which activates transcriptional activities of AP1(PMA) - Xinya Chen; Xiuting Gu; Yuxi Shan; Wenwen Tang; Jian Yuan; Zhaomin Zhong; Yingli Wang; Weixue Huang; Bo Wan; Long Yu (Molecular Biology Reports, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Halomonas sediminis sp. nov., a new halophilic bacterium isolated from salt-lake sediment in China - Heng-Yu Huang; Yi-Guang Chen; Yong-Xia Wang; Ji-Hui Liu; Shu-Kun Tang; Qian Peng; Meng-Liang Wen; Hong Yu; Xiao-Long Cui (Extremophiles, 2008)

Cloning and characterization of a human GDPD domain-containing protein GDPD5 - Qingyu Lang; Haoxing Zhang; Jie Li; Hongkun Yin; Yifeng Zhang; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2008)

Bone regeneration by BMP-2 enhanced adipose stem cells loading on alginate gel - Yunfeng Lin; Wei Tang; Ling Wu; Wei Jing; Xiaoyu Li; Yao Wu; Lei Liu; Jie Long; Weidong Tian (Histochemistry and Cell Biology, 2008)

Cloning and characterization of the human gene RAP2C, a novel member of Ras family, which activates transcriptional activities of SRE - Zekun Guo; Jian Yuan; Wenwen Tang; Xinya Chen; Xiuting Gu; Kuntian Luo; Yingli Wang; Bo Wan; Long Yu (Molecular Biology Reports, 2007)

Identification and characteristics of a novel testis-specific gene, Tsc21, in mice and human - Zhendong Yu; Aifa Tang; Yaoting Gui; Xin Guo; Hui Zhu; Yun Long; Zeting Li; Zhiming Cai (Molecular Biology Reports, 2007)

Wheat powdery mildew and foliar N concentrations as influenced by N fertilization and belowground interactions with intercropped faba bean - Yuanxue Chen; Fusuo Zhang; Li Tang; Yi Zheng; Yongjie Li; Peter Christie; Long Li (Plant and Soil, 2007)

Cloning and characterization of the human gene DERP6, which activates transcriptional activities of p53 - Jian Yuan; Wenwen Tang; Kuntian Luo; Xinya Chen; Xiuting Gu; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Identification and Characterization of the Human SCAN Domain Zinc-Finger Gene ZNF449 - Kuntian Luo; Jie Li; Yanhui Cui; Meng Xu; Jian Yuan; Wenwen Tang; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Identification and Characterization of RHEBL1, a Novel Member of Ras Family, which Activates Transcriptional Activities of NF-Kappa B - Jian Yuan; Yuxi Shan; Xinya Chen; Wenwen Tang; Kuntian Luo; Jun Ni; Bo Wan; Long Yu (Molecular Biology Reports, 2005)

Cloning, Expression and Characterization of the Human NOB1 gene - Yue Zhang; Jun Ni; Guangjin Zhou; Jian Yuan; Weihua Ren; Yuxi Shan; Wenwen Tang; Long Yu; Shouyuan Zhao (Molecular Biology Reports, 2005)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Effect of manganese spatial distribution in the soil profile on wheat growth in rice–wheat rotation - Shihua Lu; Xuejun Liu; Long Li; Fusuo Zhang; Xiangzhong Zeng; Caixian Tang (Plant and Soil, 2004)

Chickpea facilitates phosphorus uptake by intercropped wheat from an organic phosphorus source - Long Li; Caixian Tang; Zdenko Rengel; Fusuo Zhang (Plant and Soil, 2003)

Interspecific facilitation of nutrient uptake by intercropped maize and faba bean - Long Li; Fusuo Zhang; Xiaolin Li; Peter Christie; Jianhao Sun; Sicun Yang; Caixian Tang (Nutrient Cycling in Agroecosystems, 2003)

The morphological changes of wheat genotypes as affected by the levels of localized phosphate supply - Haiguo Sun; Fusuo Zhang; Long Li; Caixian Tang (Plant and Soil, 2002)

Cloning of human myeloid-associated differentiation marker (MYADM) gene whose expression was up-regulated in NB4 cells induced by all-trans retinoic acid - Wanchang Cui; Long Yu; Hua He; Yaya Chu; Jie Gao; Bo Wan; Lisha Tang; Shouyuan Zhao (Molecular Biology Reports, 2001)

Effect of the neuroprotective agent riluzole on intracellular Ca 2+ levels in IMR32 neuroblastoma cells - Jue-Long Wang; Kam-Chung Lee; Kwong-Yui Tang; Ti Lu; Cheng-Ho Chang; Chik-Keung Chow; Wei-Chuan Chen; Warren Su; Yee-Ping Law; Chung-Ren Jan (Archives of Toxicology, 2001)

Tamoxifen-induced Ca 2+ mobilization in bladder female transitional carcinoma cells - Hong-Tai Chang; Jong-Khing Huang; Jue-Long Wang; Jin-Shiung Cheng; Kam-Chung Lee; Yuk-Keung Lo; Muh-Chiou Lin; Kwong-Yui Tang; Chung-Ren Jan (Archives of Toxicology, 2001)